Laminated body, electrolytic cell and method for producing the same, electrode renewal method, laminate renewal method and wound body production method

By bonding with an electrolysis electrode with a small mass and moderate porosity rate to the ion exchange membrane or microporous membrane, the electrode renewal operation is simplified, the electrolytic performance is improved, and the membrane damage is prevented.

CN114540853BActive Publication Date: 2025-04-01ASAHI KASEI KOGYO KABUSHIKI KAISHA

Patent Information

Application Number
CN202210236925.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-03-20
Filing Date
2018-03-22
Publication Date
2025-04-01
Estimated Expiration
2038-03-22

AI Technical Summary

Technical Problem

The electrode renewal operation in existing electrolytic cells is cumbersome, and the separator and electrode are easily damaged during the electrolysis process, resulting in a degradation of electrolytic performance.

Method used

Electrolytic electrodes with small mass and moderate porosity are adopted to bond to the ion exchange membrane or microporous membrane through weak forces to simplify the electrode renewal operation, and improve the operating efficiency of electrode renewal through the design of the laminate.

Benefits of technology

The electrode update operation is simplified, the electrolytic performance is improved, and the diaphragm is prevented.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003540268670003121
    Figure BDA0003540268670003121
  • Figure BDA0003540268670003501
    Figure BDA0003540268670003501
  • Figure BDA0003540268670003591
    Figure BDA0003540268670003591
Patent Text Reader

Abstract

The present invention relates to a laminate, an electrolytic cell and a method for manufacturing the same, a method for renewing an electrode, a method for renewing a laminate, and a method for manufacturing a wound body. A laminate comprises a separator and an electrolysis electrode fixed to at least one region on the surface of the separator, wherein the ratio of the region on the surface of the separator is greater than 0% and less than 93%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The international application number of the original application is PCT / JP2018 / 011535, the international application date is March 22, 2018, the Chinese national application number is 201880015823.8, the entry date into China is September 4, 2019, and the invention title is "Electrode for Electrolysis, Laminated Body, Winded Body, Electrolytic Cell, Method for Manufacturing Electrolytic Cell, Method for Renewing Electrode, Method for Renewing Laminated Body, and Method for Manufacturing Winded Body". Technical Field

[0002] This invention relates to electrodes for electrolysis, laminates, windings, electrolytic cells, methods for manufacturing electrolytic cells, methods for updating electrodes, methods for updating laminates, and methods for manufacturing windings. Background Technology

[0003] In the electrolysis of aqueous solutions of alkali metal chlorides such as brine and the electrolysis of water (hereinafter referred to as "electrolysis"), an electrolytic cell is used, which is equipped with a diaphragm, and more specifically, an ion exchange membrane or a microporous membrane. This electrolytic cell typically contains a large number of electrolysis units connected in series. Electrolysis is carried out by interleaving diaphragms between each electrolysis unit. In each electrolysis unit, the cathode chamber, which has a cathode, and the anode chamber, which has an anode, are separated by an isolation wall (back panel), or are arranged back-to-back by pressing using pressure, bolts, or other means.

[0004] Currently, the anodes and cathodes used in these electrolytic cells are fixed to the anode and cathode chambers of the electrolysis unit by methods such as welding and clamping, and then stored and transported to the customer. On the other hand, the diaphragm is stored and transported to the customer individually wound on a tube made of vinyl chloride (polyvinyl chloride). At the customer's location, the electrolysis units are arranged on the frame of the electrolysis cell, and the diaphragm is clamped between the electrolysis units to assemble the electrolysis cell. This is how the electrolysis units are manufactured and the electrolysis cell is assembled at the customer's location. As a structure applicable to such an electrolysis cell, Patent Documents 1 and 2 disclose a structure in which the diaphragm and electrode are integrated.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 58-048686

[0008] Patent Document 2: Japanese Patent Application Publication No. 55-148775 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] If electrolysis is started and continues, components will deteriorate due to various reasons, reducing electrolytic performance, and at some point, these components will need to be replaced. The diaphragm can be easily replaced by removing it from the electrolysis unit and inserting a new one. On the other hand, since the anode and cathode are fixed to the electrolysis unit, when replacing the electrodes, the electrolysis unit must be removed from the electrolysis cell, transported to a dedicated replacement plant to remove the old electrodes (which have been fixed by welding or other methods), install new electrodes, fix them by welding or other methods, transport them back to the electrolysis plant, and return them to the electrolysis cell. This presents a very complex operational challenge. Here, a structure that integrates the diaphragm and electrodes as described in Patent Documents 1 and 2 through hot-pressing is considered for the aforementioned replacement. However, while this structure can be relatively easily manufactured at a laboratory level, it is not easy to manufacture according to the actual commercial size of the electrolysis unit (e.g., 1.5m high and 3m wide). In addition, due to its significantly poor electrolytic performance (electrolysis voltage, current efficiency, salt concentration in caustic soda, etc.) and durability, and the generation of chlorine and hydrogen gas on the electrodes of the diaphragm and interface, it will completely peel off if used for electrolysis for a long time and cannot be used in practice.

[0011] The present invention was made in view of the problems existing in the prior art, and its object is to provide the following electrolytic electrodes, laminates, windings, electrolytic cells, methods for manufacturing electrolytic cells, methods for updating electrodes, methods for updating laminates, and methods for manufacturing windings.

[0012] (Primary Objective)

[0013] One of the objectives of this invention is to provide an electrolytic electrode, laminate, and winding that are easy to transport and handle, can greatly simplify the operation when starting a new electrolytic cell or replacing a deteriorated electrode, and can maintain or improve electrolytic performance.

[0014] (Second objective)

[0015] One of the objectives of this invention is to provide a laminate that can improve the efficiency of electrode replacement in an electrolytic cell and thus exhibit excellent electrolytic performance after replacement.

[0016] (Third objective)

[0017] One of the objectives of this invention is to provide a laminate that improves the efficiency of electrode replacement in an electrolytic cell from a different perspective than the second objective described above, and thus exhibits excellent electrolytic performance after replacement.

[0018] (4th objective)

[0019] One of the objectives of this invention is to provide an electrolytic cell that can prevent membrane damage while exhibiting excellent electrolytic performance, a method for manufacturing the electrolytic cell, and a method for updating the laminate.

[0020] (Purpose 5)

[0021] One of the objectives of this invention is to provide a method for manufacturing an electrolytic cell, a method for updating electrodes, and a method for manufacturing a wound body that can improve the efficiency of electrode replacement in an electrolytic cell.

[0022] (Sixth objective)

[0023] One of the objectives of this invention is to provide a method for manufacturing an electrolytic cell that improves the efficiency of electrode replacement in an electrolytic cell from a different perspective than the fifth objective described above.

[0024] (Seventh objective)

[0025] One of the objectives of this invention is to provide a method for manufacturing an electrolytic cell that improves the efficiency of electrode replacement in an electrolytic cell from a perspective different from the fifth and sixth objectives described above.

[0026] Methods for solving problems

[0027] To achieve the first objective, the inventors conducted repeated and in-depth research, and discovered that by manufacturing an electrolysis electrode with a small mass per unit area that can be bonded to diaphragms such as ion exchange membranes and microporous membranes or deteriorated electrodes with relatively weak force, transportation and handling become easier, significantly simplifying the operation when starting a new electrolysis cell or replacing deteriorated components. Consequently, compared with the electrolysis performance of existing technologies, performance can be significantly improved. Furthermore, it was found that the electrolysis performance can be equal to or improved compared to existing electrolysis units with complex replacement operations, thus completing this invention.

[0028] That is, the present invention includes the following solutions.

[0029] [1] An electrode for electrolysis, wherein the mass per unit area of ​​the electrode for electrolysis is 48 mg / cm². 2 The force applied per unit mass / unit area is 0.08 N / mg·cm. 2 above.

[0030] [2] The electrolysis electrode as described in [1], wherein the electrolysis electrode comprises an electrolysis electrode substrate and a catalyst layer, and the thickness of the electrolysis electrode substrate is less than 300 μm.

[0031] [3] Electrolysis electrodes as described in [1] or [2], wherein the proportion determined by the following method (3) is 75% or more.

[0032] [Method (3)]

[0033] Inorganic particles and a binder were coated on both sides of a membrane containing ion-exchange-group perfluorocarbon polymer. The resulting membrane (170 mm²) and an electrolysis electrode sample (130 mm²) were then sequentially laminated. Under conditions of 23 ± 2 °C and 30 ± 5% relative humidity, the laminate was placed on the curved surface of a polyethylene tube (145 mm outer diameter) with the electrolysis electrode sample on the outside. The laminate and the tube were thoroughly impregnated with pure water to remove excess water adhering to the surface of the laminate and the tube. After 1 minute, the percentage (%) of the area where the membrane containing ion-exchange-group perfluorocarbon polymer coated with inorganic particles and a binder on both sides was in close contact with the electrolysis electrode sample was measured.

[0034] [4] An electrolytic electrode as described in any one of [1] to [3], wherein the electrolytic electrode has a porous structure with an open porosity of 5 to 90%.

[0035] [5] An electrolytic electrode as described in any one of [1] to [4], wherein the electrolytic electrode has a porous structure with an open porosity of 10 to 80%.

[0036] [6] An electrolytic electrode as described in any one of [1] to [5], wherein the thickness of the electrolytic electrode is 315 μm or less.

[0037] [7] An electrolytic electrode as described in any one of [1] to [6], wherein the value of the electrolytic electrode measured by the following method (A) is 40 mm or less.

[0038] [Method (A)]

[0039] Under conditions of 23±2℃ and 30±5% relative humidity, the sample formed by the laminated ion exchange membrane and the above-mentioned electrolysis electrode was wound and fixed onto the curved surface of a vinyl chloride core material with an outer diameter of Φ32mm. After standing for 6 hours, the electrolysis electrode was separated and placed on a horizontal plate. The vertical heights L1 and L2 at both ends of the electrolysis electrode were measured, and their average value was taken as the measured value.

[0040] [8] An electrolytic electrode as described in any one of [1] to [7], wherein the electrolytic electrode is 50 mm × 50 mm in size, and the conditions are: temperature 24 °C, relative humidity 32%, piston speed 0.2 cm / s, and air flow rate 0.4 cc / cm. 2 The ventilation resistance is below 24 kPa·s / m at the condition of / s.

[0041] [9] An electrolytic electrode as described in any one of [1] to [8], wherein the electrode substrate comprises at least one element selected from nickel (Ni) and titanium (Ti).

[0042]

[10] A laminate comprising an electrolytic electrode as described in any one of [1] to [9].

[0043]

[11] A wound body comprising an electrolytic electrode as described in any one of [1] to [9], or a laminate as described in

[10] .

[0044] In order to achieve the second objective, the inventors conducted repeated and in-depth research and found that by using the following laminate, transportation and processing become easier, which can greatly simplify the operation when starting a new electrolytic cell or when replacing deteriorated components, and further maintain or improve electrolytic performance. The laminate has electrodes that can be bonded to the power supply such as ion exchange membranes and microporous membranes or deteriorated original electrodes with relatively weak force, thereby completing the present invention.

[0045] That is, the present invention includes the following solutions.

[0046] [2-1]

[0047] A laminated body having:

[0048] Electrolysis electrodes; and

[0049] The diaphragm or power supply body in contact with the electrodes used in electrolysis,

[0050] For the aforementioned diaphragm or power supply, the force applied per unit mass and unit area of ​​the aforementioned electrolysis electrode is less than 1.5 N / mg·cm. 2 .

[0051] [2-2]

[0052] As described in [2-1], in the laminate, the force applied per unit mass per unit area of ​​the electrolytic electrode for the aforementioned diaphragm or power supply exceeds 0.005 N / mg·cm². 2 .

[0053] [2-3]

[0054] The laminate as described in [2-1] or [2-2], wherein the power supply body is a metal wire mesh, a metal nonwoven fabric, a perforated metal, a metal plate mesh, or a foamed metal.

[0055] [2-4]

[0056] The laminate as described in any one of [2-1] to [2-3], wherein at least one surface layer of the above-mentioned diaphragm has a layer comprising a mixture of hydrophilic oxide particles and a polymer incorporating ion exchange groups.

[0057] [2-5]

[0058] The laminate as described in any one of [2-1] to [2-4], wherein a liquid is sandwiched between the electrolysis electrode and the diaphragm or power supply.

[0059] In order to achieve the third objective, the inventors conducted repeated and in-depth research and found that the above-mentioned problems could be solved by a laminate in which the diaphragm and the electrolysis electrode are partially fixed, thus completing the present invention.

[0060] That is, the present invention includes the following solutions.

[0061] [3-1]

[0062] A laminate having:

[0063] Diaphragm; and

[0064] Electrolysis electrodes fixed to at least one region of the surface of the aforementioned diaphragm.

[0065] On the surface of the aforementioned diaphragm, the proportion of the aforementioned region exceeds 0% and is less than 93%.

[0066] [3-2]

[0067] As described in [3-1], the electrolytic electrode comprises at least one catalyst component selected from the group consisting of Ru, Rh, Pd, Ir, Pt, Au, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ag, Ta, W, Re, Os, Al, In, Sn, Sb, Ga, Ge, B, C, N, O, Si, P, S, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, and Dy.

[0068] [3-3]

[0069] As described in [3-1] or [3-2], in which at least a portion of the electrolytic electrode is fixed through the diaphragm in the aforementioned region.

[0070] [3-4]

[0071] The laminate as described in any one of [3-1] to [3-3], wherein, in the aforementioned region, at least a portion of the electrolytic electrode is located inside the aforementioned diaphragm and is fixed therein.

[0072] [3-5]

[0073] The laminate as described in any one of [3-1] to [3-4] further comprises a fixing member for fixing the diaphragm and the electrolysis electrode.

[0074] [3-6]

[0075] The laminate as described in [3-5], wherein at least a portion of the fixing member holds the diaphragm and the electrolysis electrode from the outside.

[0076] [3-7]

[0077] As described in [3-5] or [3-6], in which at least a portion of the fixing member is used to fix the diaphragm and the electrolysis electrode by magnetic force.

[0078] [3-8]

[0079] The laminate as described in any one of [3-1] to [3-7], wherein the diaphragm comprises an ion exchange membrane with an organic resin surface layer.

[0080] The aforementioned organic resin is present in the aforementioned area.

[0081] [3-9]

[0082] The laminate as described in any one of [3-1] to [3-8], wherein the membrane comprises a first ion exchange resin layer and a second ion exchange resin layer having an EW different from that of the first ion exchange resin layer.

[0083] [3-10]

[0084] The laminate as described in any one of [3-1] to [3-8], wherein the membrane comprises a first ion exchange resin layer and a second ion exchange resin layer having functional groups different from those of the first ion exchange resin layer.

[0085] In order to achieve the fourth objective, the inventors conducted repeated and in-depth research and found that the above-mentioned problems could be solved by sandwiching at least a portion of the laminate of the diaphragm and the electrolytic electrode between the anode-side gasket and the cathode-side gasket, thereby completing the present invention.

[0086] That is, the present invention includes the following solutions.

[0087] [4-1]

[0088] An electrolytic cell comprising:

[0089] anode;

[0090] The anode frame supporting the aforementioned anode;

[0091] Anode side gaskets disposed on the aforementioned anode frame;

[0092] The cathode facing the aforementioned anode;

[0093] A cathode frame that supports the aforementioned cathode;

[0094] A cathode-side gasket disposed on the cathode frame and facing the anode-side gasket; and

[0095] A laminate, which is a laminate of a diaphragm and an electrode for electrolysis, is disposed between the anode-side gasket and the cathode-side gasket.

[0096] At least a portion of the aforementioned laminate is held between the aforementioned anode-side gasket and the aforementioned cathode-side gasket.

[0097] The electrodes used for electrolysis were 50mm × 50mm in size, and the conditions were set at 24°C, 32% relative humidity, a piston speed of 0.2cm / s, and a gas flow rate of 0.4cc / cm³. 2 The ventilation resistance is below 24 kPa·s / m at the condition of / s.

[0098] [4-2]

[0099] The electrolytic cell as described in [4-1], wherein the thickness of the electrolytic electrode is less than 315 μm.

[0100] [4-3]

[0101] The electrolytic cell as described in [4-1] or [4-2], wherein the value of the electrode for electrolysis measured by the following method (A) is 40 mm or less.

[0102] [4-Method (A)]

[0103] Under conditions of 23±2℃ and 30±5% relative humidity, the sample formed by the laminated ion exchange membrane and the above-mentioned electrolysis electrode was wound and fixed onto the curved surface of a vinyl chloride core material with an outer diameter of Φ32mm. After standing for 6 hours, the electrolysis electrode was separated and placed on a horizontal plate. The vertical heights L1 and L2 at both ends of the electrolysis electrode were measured, and their average value was taken as the measured value.

[0104] [4-4]

[0105] The electrolytic cell as described in any one of [4-1] to [4-3], wherein the mass per unit area of ​​the aforementioned electrolytic electrode is 48 mg / cm². 2 the following.

[0106] [4-5]

[0107] The electrolytic cell as described in any one of [4-1] to [4-4], wherein the force applied per unit mass per unit area of ​​the aforementioned electrolytic electrode exceeds 0.005 N / mg·cm. 2 .

[0108] [4-6]

[0109] The electrolytic cell as described in any one of [4-1] to [4-5], wherein the outermost peripheral edge of the aforementioned laminate is located on the outer side of the direction closer to the energized surface compared to the outermost peripheral edges of the aforementioned anode-side gasket and cathode-side gasket.

[0110] [4-7]

[0111] The electrolytic cell as described in any one of [4-1] to [4-6], wherein the electrode for electrolysis comprises at least one catalyst component selected from the group consisting of Ru, Rh, Pd, Ir, Pt, Au, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ag, Ta, W, Re, Os, Al, In, Sn, Sb, Ga, Ge, B, C, N, O, Si, P, S, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, and Dy.

[0112] [4-8]

[0113] An electrolytic cell as described in any one of [4-1] to [4-7], wherein, in the aforementioned laminate, at least a portion of the electrolytic electrode is fixed through the aforementioned diaphragm.

[0114] [4-9]

[0115] An electrolytic cell as described in any one of [4-1] to [4-7], wherein, in the aforementioned laminate, at least a portion of the electrolytic electrode is located inside the aforementioned diaphragm and is fixed therein.

[0116] [4-10]

[0117] The electrolytic cell as described in any one of [4-1] to [4-9], wherein the laminated body further comprises a fixing member for fixing the diaphragm and the electrolytic electrode.

[0118] [4-11]

[0119] In the electrolytic cell described in [4-10], at least a portion of the fixing member is fixed through the diaphragm and the electrolytic electrode in the laminate.

[0120] [4-12]

[0121] The electrolytic cell as described in [4-10] or [4-11], wherein the fixing member in the above-mentioned laminate contains a soluble material that is soluble in the electrolyte.

[0122] [4-13]

[0123] An electrolytic cell as described in any one of [4-10] to [4-12], wherein, in the aforementioned laminate, at least a portion of the fixing member holds the diaphragm and the electrolytic electrode from the outside.

[0124] [4-14]

[0125] The electrolytic cell as described in any one of [4-10] to [4-13], wherein, in the above-mentioned laminate, at least a portion of the fixing member is used to fix the diaphragm and the electrolytic electrode by magnetic force.

[0126] [4-15]

[0127] The electrolytic cell as described in any one of [4-1] to [4-14], wherein the diaphragm comprises an ion exchange membrane with an organic resin surface layer.

[0128] The aforementioned electrolysis electrode is fixed on the aforementioned organic resin.

[0129] [4-16]

[0130] The electrolytic cell as described in any one of [4-1] to [4-15], wherein the diaphragm comprises a first ion exchange resin layer and a second ion exchange resin layer having an EW different from that of the first ion exchange resin layer.

[0131] [4-17]

[0132] A method for manufacturing an electrolytic cell, which is the method for manufacturing an electrolytic cell described in any one of [4-1] to [4-16], wherein,

[0133] The manufacturing method includes a step of clamping the laminate between the anode-side gasket and the cathode-side gasket.

[0134] [4-18]

[0135] A method for updating a laminate, which is the method for updating a laminate in an electrolytic cell as described in any one of [4-1] to [4-16], wherein,

[0136] The update method has the following steps:

[0137] The process of separating the laminate from the anode-side gasket and the cathode-side gasket, thereby removing the laminate from the electrolytic cell; and

[0138] The process of clamping a new laminate between the anode-side gasket and the cathode-side gasket.

[0139] In order to achieve the fifth objective, the inventors conducted repeated and in-depth research and found that the above-mentioned problems could be solved by using an electrolysis electrode or a winding of the electrolysis electrode and a new diaphragm laminate, thereby completing the present invention.

[0140] That is, the present invention includes the following solutions.

[0141] [5-1]

[0142] A method for manufacturing an electrolytic cell, comprising manufacturing a new electrolytic cell by configuring an electrolytic electrode or a laminate of the electrolytic electrode and a new diaphragm in an existing electrolytic cell, wherein the existing electrolytic cell includes an anode, a cathode facing the anode, and a diaphragm disposed between the anode and the cathode, wherein...

[0143] The above-mentioned method for manufacturing an electrolytic cell uses the above-mentioned electrolytic electrode or the winding body of the above-mentioned laminate.

[0144] [5-2]

[0145] The method for manufacturing an electrolytic cell as described in [5-1] includes a step (A) of obtaining the wound body by holding the electrolytic electrode or the laminate in a wound state.

[0146] [5-3]

[0147] The method for manufacturing an electrolytic cell as described in [5-1] or [5-2] includes a step (B) of unwinding the winding state of the aforementioned wound body.

[0148] [5-4]

[0149] The method for manufacturing an electrolytic cell as described in [5-3] includes, after the above-described step (B), the following step (C): disposing the electrolytic electrode or the laminate on at least one surface of the anode and the cathode.

[0150] [5-5]

[0151] An electrode renewal method, which involves using an electrolysis electrode to renew an existing electrode, wherein...

[0152] The above-described update method uses the winding body of the electrolytic electrode described above.

[0153] [5-6]

[0154] The electrode renewal method described in [5-5] includes a step (A') of holding the electrolysis electrode in a wound state to obtain the wound body.

[0155] [5-7]

[0156] The electrode renewal method as described in [5-5] or [5-6] includes a step (B') of unwinding the aforementioned electrolytic electrode.

[0157] [5-8]

[0158] The electrode renewal method as described in [5-7] includes, after the above-described step (B'), the following step (C'): the above-described electrolytic electrode is disposed on the surface of the original electrode.

[0159] [5-9]

[0160] A method for manufacturing a wound body is disclosed, which is a method for manufacturing a wound body for updating an existing electrolytic cell. The existing electrolytic cell includes an anode, a cathode facing the anode, and a diaphragm disposed between the anode and the cathode.

[0161] The manufacturing method of the above-mentioned wound body includes the following steps: winding an electrolytic electrode or a laminate of the electrolytic electrode and a new diaphragm to obtain the above-mentioned wound body.

[0162] In order to achieve the sixth objective, the inventors conducted repeated and in-depth research and found that by integrating the electrolysis electrode and the new diaphragm at a temperature at which the diaphragm does not melt, the above-mentioned problems can be solved, thus completing the present invention.

[0163] That is, the present invention includes the following solutions.

[0164] [6-1]

[0165] A method for manufacturing an electrolytic cell, comprising a method for manufacturing a new electrolytic cell by arranging a laminated body in an existing electrolytic cell, wherein the existing electrolytic cell includes an anode, a cathode facing the anode, and a diaphragm disposed between the anode and the cathode, wherein...

[0166] The manufacturing method of the above-mentioned electrolytic cell includes the following steps:

[0167] In step (A), the electrolysis electrode and the new diaphragm are integrated at a temperature at which the diaphragm does not melt, thereby obtaining the above-mentioned laminate; and

[0168] Step (B) is performed after step (A) by exchanging the diaphragm and the laminate in the original electrolytic cell.

[0169] [6-2]

[0170] The method for manufacturing an electrolytic cell as described in [6-1], wherein the above-mentioned integration is carried out under normal pressure.

[0171] In order to achieve the seventh objective, the inventors conducted repeated and in-depth research and found that the above-mentioned problems could be solved by operating within the electrolytic cell frame, thus completing the present invention.

[0172] That is, the present invention includes the following solutions.

[0173] [7-1]

[0174] A method for manufacturing an electrolytic cell, comprising fabricating a new electrolytic cell by configuring a laminate containing electrolytic electrodes and a new diaphragm in an existing electrolytic cell, wherein the existing electrolytic cell includes an anode, a cathode facing the anode, a diaphragm fixed between the anode and the cathode, and an electrolytic cell frame supporting the anode, the cathode, and the diaphragm, wherein...

[0175] The manufacturing method of the above-mentioned electrolytic cell includes the following steps:

[0176] Step (A): Within the aforementioned electrolytic cell frame, the diaphragm is released from its fixation; and

[0177] Step (B) involves exchanging the diaphragm with the laminate after step (A).

[0178] [7-2]

[0179] The method for manufacturing an electrolytic cell as described in [7-1], wherein the above-mentioned step (A) is performed by sliding the above-mentioned anode and the above-mentioned cathode in their respective arrangement directions.

[0180] [7-3]

[0181] The method for manufacturing an electrolytic cell as described in [7-1] or [7-2], wherein, after the above-described step (B), the laminate is fixed within the electrolytic cell frame by extrusion from the above-described anode and the above-described cathode.

[0182] [7-4]

[0183] The method for manufacturing an electrolytic cell as described in any one of [7-1] to [7-3], wherein, in the above-described step (B), the laminate is fixed to at least one surface of the anode and the cathode at a temperature at which the laminate does not melt.

[0184] [7-5]

[0185] A method for manufacturing an electrolytic cell, comprising configuring electrolytic electrodes in an existing electrolytic cell to create a new electrolytic cell, wherein the existing electrolytic cell includes an anode, a cathode facing the anode, a diaphragm fixed between the anode and the cathode, and an electrolytic cell frame supporting the anode, the cathode, and the diaphragm, wherein...

[0186] The manufacturing method of the above-mentioned electrolytic cell includes the following steps:

[0187] Step (A): Within the aforementioned electrolytic cell frame, the diaphragm is released from its fixation; and

[0188] Step (B'): After step (A), the electrolysis electrode is placed between the diaphragm and the anode or the cathode.

[0189] The effects of the invention

[0190] (1) According to the electrolytic electrode of the present invention, the transport and handling become easy, which can greatly simplify the operation when starting a new electrolytic cell or when replacing a deteriorated electrode, and can also maintain or improve the electrolytic performance.

[0191] (2) The laminate according to the present invention can improve the working efficiency of electrode replacement in the electrolytic cell and thus exhibit excellent electrolytic performance after replacement.

[0192] (3) According to the laminate of the present invention, the efficiency of electrode replacement in the electrolytic cell can be improved from a different aspect than (2) above, and thus the electrolytic performance can be maintained even after replacement.

[0193] (4) The electrolytic cell according to the present invention has excellent electrolytic performance and can prevent damage to the diaphragm.

[0194] (5) The method for manufacturing an electrolytic cell according to the present invention can improve the efficiency of electrode replacement in an electrolytic cell.

[0195] (6) According to the method of manufacturing an electrolytic cell of the present invention, the efficiency of electrode replacement in an electrolytic cell can be improved from a different aspect than (5) above.

[0196] (7) According to the method of manufacturing an electrolytic cell of the present invention, the efficiency of electrode replacement in an electrolytic cell can be improved from a different perspective than (5) and (6) above. Attached Figure Description

[0197] Figure 1 This is a schematic cross-sectional view of an electrolytic electrode according to one embodiment of the present invention.

[0198] Figure 2 This is a cross-sectional schematic diagram illustrating one embodiment of an ion exchange membrane.

[0199] Figure 3 This is a schematic diagram illustrating the aperture ratio of the reinforcing core material that constitutes an ion exchange membrane.

[0200] Figure 4This is a schematic diagram illustrating a method for forming interconnecting pores in an ion exchange membrane.

[0201] Figure 5 This is a schematic cross-sectional view of an electrolysis unit.

[0202] Figure 6 This is a schematic cross-sectional view showing the state of two electrolysis units connected in series.

[0203] Figure 7 This is a schematic diagram of an electrolytic cell.

[0204] Figure 8 This is a schematic perspective view showing the process of assembling an electrolytic cell.

[0205] Figure 9 This is a schematic cross-sectional view of the reverse current absorber in the electrolysis unit.

[0206] Figure 10 This is a schematic diagram of the evaluation method for the force (1) applied per unit mass and unit area as described in the embodiment.

[0207] Figure 11 This is a schematic diagram of the evaluation method (1) for winding a 280mm diameter cylinder as described in the embodiment.

[0208] Figure 12 This is a schematic diagram of the evaluation method (2) for winding a 280mm diameter cylinder as described in the embodiment.

[0209] Figure 13 This is a schematic diagram of the evaluation method (3) for winding a 145mm diameter cylinder as described in the embodiment.

[0210] Figure 14 This is a schematic diagram of the elastic deformation test of the electrode described in the embodiment.

[0211] Figure 15 This is a schematic diagram of a method for evaluating the softness after plastic deformation.

[0212] Figure 16 This is a schematic diagram of the electrode fabricated in Comparative Example 13.

[0213] Figure 17 This is a schematic diagram of the structure used to place the electrode made in Comparative Example 13 onto the nickel mesh power supply.

[0214] Figure 18 This is a schematic diagram of the electrode fabricated in Comparative Example 14.

[0215] Figure 19 This is a schematic diagram of the structure used to place the electrode made in Comparative Example 14 onto the nickel mesh power supply.

[0216] Figure 20 This is a schematic diagram of the electrode fabricated in Comparative Example 15.

[0217] Figure 21 This is a schematic diagram of the structure used to place the electrode made in Comparative Example 15 onto the nickel mesh power supply.

[0218] Figure 22 This is a schematic cross-sectional view of an electrolysis electrode according to one embodiment of the present invention.

[0219] Figure 23 This is a cross-sectional schematic diagram illustrating one embodiment of an ion exchange membrane.

[0220] Figure 24 This is a schematic diagram illustrating the aperture ratio of the reinforcing core material that constitutes an ion exchange membrane.

[0221] Figure 25 This is a schematic diagram illustrating a method for forming interconnecting pores in an ion exchange membrane.

[0222] Figure 26 This is a schematic cross-sectional view of an electrolysis unit.

[0223] Figure 27 This is a schematic cross-sectional view showing the state of two electrolysis units connected in series.

[0224] Figure 28 This is a schematic diagram of an electrolytic cell.

[0225] Figure 29 This is a schematic perspective view showing the process of assembling an electrolytic cell.

[0226] Figure 30 This is a schematic cross-sectional view of the reverse current absorber in the electrolysis unit.

[0227] Figure 31 This is a schematic diagram of the evaluation method for the force (1) applied per unit mass and unit area as described in the embodiment.

[0228] Figure 32 This is a schematic diagram of the evaluation method (1) for winding a 280mm diameter cylinder as described in the embodiment.

[0229] Figure 33 This is a schematic diagram of the evaluation method (2) for winding a 280mm diameter cylinder as described in the embodiment.

[0230] Figure 34 This is a schematic diagram of the evaluation method (3) for winding a 145mm diameter cylinder as described in the embodiment.

[0231] Figure 35 This is a schematic diagram of the elastic deformation test of the electrode described in the embodiment.

[0232] Figure 36 This is a schematic diagram of a method for evaluating the softness after plastic deformation.

[0233] Figure 37 This is a schematic diagram of the electrode fabricated in Example 34.

[0234] Figure 38 This is a schematic diagram of the structure used to place the electrode made in Example 34 onto the nickel mesh power supply.

[0235] Figure 39 This is a schematic diagram of the electrode fabricated in Example 35.

[0236] Figure 40 This is a schematic diagram of the structure used to place the electrode made in Example 35 onto the nickel mesh power supply.

[0237] Figure 41 This is a schematic diagram of the electrode fabricated in Example 36.

[0238] Figure 42 This is a schematic diagram of the structure used to place the electrode made in Example 36 onto the nickel mesh power supply.

[0239] Figure 43 This is a schematic cross-sectional view of an electrolysis electrode according to one embodiment of the present invention.

[0240] Figure 44 This is a cross-sectional schematic diagram illustrating one embodiment of an ion exchange membrane.

[0241] Figure 45 This is a schematic diagram illustrating the aperture ratio of the reinforcing core material that constitutes an ion exchange membrane.

[0242] Figure 46 This is a schematic diagram illustrating a method for forming interconnecting pores in an ion exchange membrane.

[0243] Figure 47 middle, Figure 47 A is a schematic cross-sectional view of a laminate illustrating how at least a portion of an electrode for electrolysis is fixed through a diaphragm. Figure 47 B is shown as the method used to obtain Figure 47 A diagram illustrating the process steps of structure A.

[0244] Figure 48 middle, Figure 48 A is a schematic cross-sectional view of a laminate in which at least a portion of the electrode for electrolysis is located inside the diaphragm and fixed in that manner. Figure 48 B is shown as the method used to obtain Figure 48 A diagram illustrating the process steps of structure A.

[0245] Figure 49 middle, Figure 49 A to C are schematic cross-sectional views illustrating a laminated body used as a fixing member for fixing a diaphragm and an electrolytic electrode, in which filamentary fixing members are used for fixing.

[0246] Figure 50 This is a schematic cross-sectional view illustrating a laminated body used as a fixing component for fixing a diaphragm and an electrolytic electrode, where organic resin is used for fixing.

[0247] Figure 51 middle, Figure 51 A is a schematic cross-sectional view of a laminate illustrating how at least a portion of the fixing member holds the diaphragm and the electrolytic electrode from the outside for fixing. Figure 51 B is a schematic cross-sectional view of a laminate in which at least a portion of the fixing component is magnetically fixed to the diaphragm and the electrolytic electrode.

[0248] Figure 52 This is a schematic cross-sectional view of an electrolysis unit.

[0249] Figure 53 This is a schematic cross-sectional view showing the state of two electrolysis units connected in series.

[0250] Figure 54 This is a schematic diagram of an electrolytic cell.

[0251] Figure 55 This is a schematic perspective view showing the process of assembling an electrolytic cell.

[0252] Figure 56 This is a schematic cross-sectional view of a reverse current absorber that an electrolysis unit may possess.

[0253] Figure 57 This is an explanatory diagram showing the laminate in Example 1.

[0254] Figure 58 This is an explanatory diagram showing the laminate in Example 2.

[0255] Figure 59 This is an explanatory diagram showing the laminate in Example 3.

[0256] Figure 60 This is an explanatory diagram showing the laminate in Example 4.

[0257] Figure 61 This is an explanatory diagram showing the laminate in Example 5.

[0258] Figure 62 This is an explanatory diagram showing the laminate in Example 6.

[0259] Figure 63This is a schematic cross-sectional view of an electrolysis unit.

[0260] Figure 64 middle, Figure 64 A is a schematic cross-sectional view showing the state of two electrolysis units connected in series in an existing electrolytic cell. Figure 64 B is a schematic cross-sectional view showing the state in which two electrolysis units in the electrolytic cell of this embodiment are connected in series.

[0261] Figure 65 This is a schematic diagram of an electrolytic cell.

[0262] Figure 66 This is a schematic perspective view showing the process of assembling an electrolytic cell.

[0263] Figure 67 This is a schematic cross-sectional view of a reverse current absorber that an electrolysis unit may possess.

[0264] Figure 68 This is a schematic cross-sectional view of an electrolysis electrode according to one embodiment of the present invention.

[0265] Figure 69 This is a cross-sectional schematic diagram illustrating one embodiment of an ion exchange membrane.

[0266] Figure 70 This is a schematic diagram illustrating the aperture ratio of the reinforcing core material that constitutes an ion exchange membrane.

[0267] Figure 71 This is a schematic diagram illustrating a method for forming interconnecting pores in an ion exchange membrane.

[0268] Figure 72 It is an explanatory diagram used to illustrate the positional relationship between the laminate and the gasket.

[0269] Figure 73 It is an explanatory diagram used to illustrate the positional relationship between the laminate and the gasket.

[0270] Figure 74 middle, Figure 74 A is a schematic cross-sectional view of a laminate illustrating how at least a portion of an electrode for electrolysis is fixed through a diaphragm. Figure 74 B is shown as the method used to obtain Figure 74 A diagram illustrating the process steps of structure A.

[0271] Figure 75 middle, Figure 75 A is a schematic cross-sectional view of a laminate in which at least a portion of the electrode for electrolysis is located inside the diaphragm and fixed in that manner. Figure 75 B is shown as the method used to obtain Figure 75 A diagram illustrating the process steps of structure A.

[0272] Figure 76 middle, Figure 76 A to C are schematic cross-sectional views illustrating a laminated body used as a fixing member for fixing a diaphragm and an electrolytic electrode, in which filamentary fixing members are used for fixing.

[0273] Figure 77 This is a schematic cross-sectional view illustrating a laminated body used as a fixing component for fixing a diaphragm and an electrolytic electrode, where organic resin is used for fixing.

[0274] Figure 78 middle, Figure 78 A is a schematic cross-sectional view of a laminate illustrating how at least a portion of the fixing member holds the diaphragm and the electrolytic electrode from the outside for fixing. Figure 78 B is a schematic cross-sectional view of a laminate in which at least a portion of the fixing component is magnetically fixed to the diaphragm and the electrolytic electrode.

[0275] Figure 79 This is a schematic diagram of the evaluation method for the force (1) applied per unit mass and unit area as described in the embodiment.

[0276] Figure 80 This is a schematic diagram of the evaluation method (1) for winding a 280mm diameter cylinder as described in the embodiment.

[0277] Figure 81 This is a schematic diagram of the evaluation method (2) for winding a 280mm diameter cylinder as described in the embodiment.

[0278] Figure 82 This is a schematic diagram of the evaluation method (3) for winding a 145mm diameter cylinder as described in the embodiment.

[0279] Figure 83 This is a schematic diagram illustrating the evaluation of the flexibility of the electrode as described in the embodiments.

[0280] Figure 84 This is a schematic diagram of a method for evaluating the softness after plastic deformation.

[0281] Figure 85 This is a schematic diagram of the electrode fabricated in Example 35.

[0282] Figure 86 This is a schematic diagram of the structure used to place the electrode made in Example 35 onto the nickel mesh power supply.

[0283] Figure 87 This is a schematic diagram of the electrode fabricated in Example 36.

[0284] Figure 88 This is a schematic diagram of the structure used to place the electrode made in Example 36 onto the nickel mesh power supply.

[0285] Figure 89 This is a schematic diagram of the electrode fabricated in Example 37.

[0286] Figure 90 This is a schematic diagram of the structure used to place the electrode made in Example 37 onto the nickel mesh power supply.

[0287] Figure 91 This is a schematic cross-sectional view of an electrolysis unit.

[0288] Figure 92 This is a schematic cross-sectional view showing the state of two electrolysis units connected in series.

[0289] Figure 93 This is a schematic diagram of an electrolytic cell.

[0290] Figure 94 This is a schematic perspective view showing the process of assembling an electrolytic cell.

[0291] Figure 95 This is a schematic cross-sectional view of a reverse current absorber that an electrolysis unit may possess.

[0292] Figure 96 This is a schematic cross-sectional view of an electrolysis electrode according to one embodiment of the present invention.

[0293] Figure 97 This is a cross-sectional schematic diagram illustrating one embodiment of an ion exchange membrane.

[0294] Figure 98 This is a schematic diagram illustrating the aperture ratio of the reinforcing core material that constitutes an ion exchange membrane.

[0295] Figure 99 This is a schematic diagram illustrating a method for forming interconnecting pores in an ion exchange membrane.

[0296] Figure 100 This is a schematic diagram of the laminate fabricated in Example 1.

[0297] Figure 101 This is a schematic diagram of the process of winding the laminate prepared in Example 1 to form a wound body.

[0298] Figure 102 This is a schematic diagram of the laminate fabricated in Example 4.

[0299] Figure 103 This is a schematic cross-sectional view of an electrolysis unit.

[0300] Figure 104 This is a schematic cross-sectional view showing the state of two electrolysis units connected in series.

[0301] Figure 105This is a schematic diagram of an electrolytic cell.

[0302] Figure 106 This is a schematic perspective view showing the process of assembling an electrolytic cell.

[0303] Figure 107 This is a schematic cross-sectional view of a reverse current absorber that an electrolysis unit may possess.

[0304] Figure 108 This is a schematic cross-sectional view of an electrolysis electrode according to one embodiment of the present invention.

[0305] Figure 109 This is a cross-sectional schematic diagram illustrating one embodiment of an ion exchange membrane.

[0306] Figure 110 This is a schematic diagram illustrating the aperture ratio of the reinforcing core material that constitutes an ion exchange membrane.

[0307] Figure 111 This is a schematic diagram illustrating a method for forming interconnecting pores in an ion exchange membrane.

[0308] Figure 112 This is a schematic cross-sectional view of an electrolysis unit.

[0309] Figure 113 This is a schematic cross-sectional view showing the state of two electrolysis units connected in series.

[0310] Figure 114 This is a schematic diagram of an electrolytic cell.

[0311] Figure 115 This is a schematic perspective view showing the process of assembling an electrolytic cell.

[0312] Figure 116 This is a schematic cross-sectional view of a reverse current absorber that an electrolysis unit may possess.

[0313] Figure 117 middle, Figure 117 (A) is a schematic diagram of an electrolytic cell used to illustrate an example of each step of the first method of this embodiment. Figure 117 (B) is related to Figure 117 (A) Corresponding schematic 3D diagram.

[0314] Figure 118 middle, Figure 118 (A) is a schematic diagram of an electrolytic cell used to illustrate an example of each step of the second method of this embodiment. Figure 118 (B) is related to Figure 118 (A) Corresponding schematic 3D diagram.

[0315] Figure 119 This is a schematic cross-sectional view of an electrolysis electrode according to one embodiment of the present invention.

[0316] Figure 120 This is a cross-sectional schematic diagram illustrating one embodiment of an ion exchange membrane.

[0317] Figure 121 This is a schematic diagram illustrating the aperture ratio of the reinforcing core material that constitutes an ion exchange membrane.

[0318] Figure 122 This is a schematic diagram illustrating a method for forming interconnecting pores in an ion exchange membrane. Detailed Implementation

[0319] Hereinafter, embodiments of the present invention (hereinafter also referred to as "this embodiment") will be described in detail with reference to the accompanying drawings, according to <Embodiment 1> to <Embodiment 7>. The following embodiments are examples for illustrating the present invention, and the present invention is not limited to the following content. Furthermore, the accompanying drawings show one example of an embodiment, but the embodiment is not interpreted as limited thereto. The present invention can be implemented with appropriate modifications within its essential points. It should be noted that the positional relationships such as up, down, left, and right in the accompanying drawings are based on the positional relationships shown in the drawings unless otherwise specified. The dimensions and scale of the accompanying drawings are not limited to the dimensions and scales shown in the drawings.

[0320] <First Implementation>

[0321] Here, refer to Figures 1-21 The first embodiment of the present invention will be described in detail below.

[0322] Electrolysis electrodes

[0323] Regarding the electrolysis electrode of the first embodiment (hereinafter, in the section on "first embodiment", it is simply referred to as "this embodiment"), from the aspects of obtaining good processability, good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and power supplies without catalyst coating, and economy, the mass per unit area is 48 mg / cm². 2 Below. Furthermore, based on the above aspects, 30 mg / cm³ is preferred. 2 The following, and more preferably, is 20 mg / cm³. 2 Furthermore, considering the comprehensive aspects of processability, adhesion, and economy, 15 mg / cm³ is preferred. 2 The following is a lower limit value, which is not specifically defined, for example, 1 mg / cm³. 2 about.

[0324] The mass per unit area mentioned above can be adjusted, for example, by appropriately adjusting the aperture ratio, electrode thickness, etc. (described later). More specifically, for the same thickness, increasing the aperture ratio tends to decrease the mass per unit area, while decreasing the aperture ratio tends to increase the mass per unit area.

[0325] Regarding the electrolysis electrode of this embodiment, considering its good processability and good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power sources, the force applied per unit mass per unit area is 0.08 N / (mg·cm²). 2 ) or above. Furthermore, considering the above aspects, 0.1 N / (mg·cm³) is preferred. 2 0.14 N / (mg·cm³) or more, preferably 0.14 N / (mg·cm³) 2 From the perspective of easier handling of large-sized objects (e.g., 1.5m × 2.5m), 0.2 N / (mg·cm³) is further preferred. 2 The upper limit is not specifically limited, but is preferably 1.6 N / (mg·cm). 2 ) or less, more preferably less than 1.6 N / (mg·cm 2 Further preferred is less than 1.5 N / (mg·cm). 2 ), and more preferably 1.2 N / mg·cm 2 The following, and more preferably, is 1.20 N / mg·cm 2 The following is a further preferred value: 1.1 N / mg·cm³. 2 The following, and more preferably, is 1.10 N / mg·cm⁻¹ 2 The following, particularly preferred, value is 1.0 N / mg·cm⁻¹ 2 The following, particularly preferred, value is 1.00 N / mg·cm⁻¹ 2 the following.

[0326] When the electrolysis electrode of this embodiment is an electrode with a wide elastic deformation region, from the perspective of obtaining better processability and better adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and power supplies without catalyst coating, the thickness of the electrolysis electrode is preferably 315 μm or less, more preferably 220 μm or less, further preferably 170 μm or less, even more preferably 150 μm or less, particularly preferably 145 μm or less, even more preferably 140 μm or less, even more preferably 138 μm or less, and even more preferably 135 μm or less. Good processability can be obtained if it is 135 μm or less. Furthermore, from the same perspective as above, it is preferably 130 μm or less, more preferably less than 130 μm, even more preferably 115 μm or less, and even more preferably 65 μm or less. The lower limit value is not particularly limited, but it is preferably 1 μm or more, and from a practical point of view, it is more preferably 5 μm or more, and even more preferably 20 μm or more. It should be noted that in this embodiment, "wide elastic deformation region" means that when the electrolysis electrode is wound into a coil, it is difficult for warping due to winding to occur after the coil is unwound. Furthermore, regarding the thickness of the electrolysis electrode, in the case of the catalyst layer described later, it refers to the thickness of the electrolysis electrode substrate and the catalyst layer combined together.

[0327] The electrolysis electrode according to this embodiment, as described above, exhibits excellent adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and power supply units without catalyst coating, enabling its integration with membranes such as ion exchange membranes or microporous membranes. Therefore, when replacing the electrode, the same simple operation as membrane replacement can be used, without the cumbersome replacement operation of peeling off the electrode fixed to the electrolysis unit, thus significantly improving work efficiency. Furthermore, even in the case where a new electrolysis unit only has a power supply unit (i.e., an electrode without a catalyst layer), it can function as an electrode simply by attaching the electrolysis electrode of this embodiment to the power supply unit, thus significantly reducing or completely eliminating catalyst coating.

[0328] Furthermore, the electrolysis electrode according to this embodiment can make the electrolysis performance the same as or even better than that of a new product.

[0329] The electrolysis electrode of this embodiment can be stored and transported to the customer in a state of being wound on, for example, a tube made of polyvinyl chloride (in a roll or the like), making it very easy to handle.

[0330] The applied force can be measured using either method (i) or (ii), as detailed in the examples. Regarding the applied force, the value obtained by method (i) (also referred to as "the applied force (1)") and the value obtained by method (ii) (also referred to as "the applied force (2)") may be the same or different, but both values ​​are 0.08 N / (mg·cm²). 2 )above.

[0331] The applied force described above can be adjusted to the range described below, for example, by appropriately adjusting the porosity, electrode thickness, arithmetic mean surface roughness, etc. More specifically, for example, increasing the porosity tends to decrease the applied force, while decreasing the porosity tends to increase the applied force.

[0332] [Method(i)]

[0333] A nickel plate (1.2 mm thick, 200 mm square) obtained by sandblasting alumina particle number 320, an ion exchange membrane (170 mm square, details of which are as described in the examples) with inorganic particles and binders coated on both sides of a membrane containing ion exchange groups of perfluorocarbon polymer, and an electrolysis electrode sample (130 mm square) were sequentially laminated. The laminate was thoroughly impregnated with pure water, and excess water adhering to the surface of the laminate was removed to obtain the sample for measurement. It should be noted that the arithmetic mean surface roughness (Ra) of the sandblasted nickel plate is 0.7 μm. The specific calculation method for the arithmetic mean surface roughness (Ra) is as described in the examples.

[0334] Under conditions of 23±2℃ and 30±5% relative humidity, a tensile compression testing machine was used to raise only the electrolytic electrode sample in the test sample at a vertical speed of 10 mm / min, and the load on the electrolytic electrode sample when it rose 10 mm vertically was measured. This measurement was performed three times, and the average value was calculated.

[0335] Divide this average value by the area of ​​the overlap between the electrolysis electrode sample and the ion exchange membrane, and the mass of the electrolysis electrode sample in the overlap area with the ion exchange membrane, to calculate the force applied per unit mass per unit area (1) (N / mg·cm). 2 ).

[0336] Regarding the force (1) applied per unit mass per unit area obtained by method (i), considering the good processability and good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power sources, the applied force (1) is 0.08 N / (mg·cm²). 2) or higher, preferably 0.1 N / (mg·cm 2 From the perspective of easier handling of large-sized objects (e.g., 1.5m × 2.5m), a value of 0.2 N / (mg·cm³) is more preferable. 2 The upper limit is not specifically limited, but is preferably 1.6 N / (mg·cm). 2 ) or less, more preferably less than 1.6 N / (mg·cm 2 Further preferred is less than 1.5 N / (mg·cm). 2 ), and more preferably 1.2 N / mg·cm 2 The following, and more preferably, is 1.20 N / mg·cm 2 The following is a further preferred value: 1.1 N / mg·cm³. 2 The following, and more preferably, is 1.10 N / mg·cm⁻¹ 2 The following, particularly preferred, value is 1.0 N / mg·cm⁻¹ 2 The following, and especially preferred, value is 1.00 N / mg·cm⁻¹. 2 the following.

[0337] If the electrolysis electrode of this embodiment satisfies the applied force (1), it can be integrated with a membrane such as an ion exchange membrane or a microporous membrane. Therefore, when updating the electrode, it is not necessary to replace the cathode and anode that are fixed to the electrolysis unit by welding or other methods, thus greatly improving work efficiency. In addition, by using the electrolysis electrode of this embodiment as an integrated electrode with the ion exchange membrane, the electrolysis performance can be the same as or even improved from that of a new product.

[0338] In the prior art, when shipping new electrolysis units, the electrodes fixed to the electrolysis unit are coated with a catalyst. However, the electrolysis electrodes of this embodiment can be used as electrodes simply by combining electrodes that have not been coated with a catalyst. Therefore, the manufacturing process for catalyst coating or the amount of catalyst can be significantly reduced or completely eliminated. The prior art electrodes, whose catalyst coating has been significantly reduced or completely eliminated, can be electrically connected to the electrolysis electrodes of this embodiment and function as a power source for flowing current.

[0339] [Method (ii)]

[0340] A nickel plate (1.2 mm thick, 200 mm square, the same nickel plate as in method (i) above) obtained by sandblasting alumina particle number 320, and an electrolytic electrode sample (130 mm square) were sequentially laminated. The laminate was thoroughly impregnated with pure water, and excess water adhering to the surface of the laminate was removed, thus obtaining the test sample. Under conditions of 23 ± 2 °C and 30 ± 5% relative humidity, a tensile compression testing machine was used to raise only the electrolytic electrode sample in the test sample vertically at a rate of 10 mm / min, and the load on the electrolytic electrode sample when raised 10 mm vertically was measured. This measurement was performed three times, and the average value was calculated.

[0341] Divide this average value by the area of ​​the overlapping portion between the electrolytic electrode sample and the nickel plate, and the mass of the electrolytic electrode sample in the overlapping portion, to calculate the adhesive force per unit mass per unit area (2) (N / mg·cm). 2 ).

[0342] Regarding the force (2) applied per unit mass per unit area obtained by method (ii), considering the good processability and good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power sources, the applied force (2) is 0.08 N / (mg·cm²). 2 ) or higher, preferably 0.1 N / (mg·cm 2 From the perspective of easier processing of large-sized objects (e.g., 1.5m × 2.5m), a value of 0.14 N / (mg·cm³) is more preferable. 2 The upper limit is not specifically limited, but is preferably 1.6 N / (mg·cm). 2 ) or less, more preferably less than 1.6 N / (mg·cm 2 Further preferred is less than 1.5 N / (mg·cm). 2 ), and more preferably 1.2 N / mg·cm 2 The following, and more preferably, is 1.20 N / mg·cm 2 The following is a further preferred value: 1.1 N / mg·cm³. 2 The following, and more preferably, is 1.10 N / mg·cm⁻¹ 2 The following, particularly preferred, value is 1.0 N / mg·cm⁻¹ 2 The following, and especially preferred, value is 1.00 N / mg·cm⁻¹. 2 the following.

[0343] If the electrolysis electrode of this embodiment satisfies the applied force (2), it can be stored and transported to the customer in a state of being wound on, for example, a PVC tube (in rolls, etc.), making processing very easy. In addition, by attaching the electrolysis electrode of this embodiment to a deteriorated electrode, the electrolysis performance can be made the same as or even improved compared to that of a new product.

[0344] In this embodiment, any liquid can be used as long as it is a substance that generates surface tension, such as water or an organic solvent, between the ion exchange membrane or microporous membrane and the electrolysis electrode, or between the power supply (a degraded electrode or an electrode without catalyst coating) and the electrolysis electrode. The greater the surface tension of the liquid, the greater the force applied between the diaphragm and the electrolysis electrode, or between the metal plate and the electrolysis electrode; therefore, a liquid with high surface tension is preferred. Examples of liquids include the following substances (the values ​​in parentheses represent the surface tension of the liquid).

[0345] Hexane (20.44 mN / m), acetone (23.30 mN / m), methanol (24.00 mN / m), ethanol (24.05 mN / m), ethylene glycol (50.21 mN / m), water (72.76 mN / m)

[0346] If the liquid has high surface tension, the diaphragm and the electrolysis electrode, or the porous metal plate or metal plate (power supply) and the electrolysis electrode, become integrated (forming a laminate), making electrode replacement easier. The amount of liquid between the diaphragm and the electrolysis electrode, or the porous metal plate or metal plate (power supply) and the electrolysis electrode, only needs to be such that they adhere to each other due to surface tension. As a result, the liquid volume is small, so even if it mixes into the electrolyte after being placed in the electrolysis unit of this laminate, it will not affect the electrolysis itself.

[0347] From a practical standpoint, liquids with a surface tension of 20 mN / m to 80 mN / m, such as ethanol, ethylene glycol, and water, are preferred. Water, or aqueous solutions containing caustic soda, potassium hydroxide, lithium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium carbonate, or potassium carbonate to form an alkaline solution, are particularly preferred. Alternatively, these liquids can be formulated with surfactants to adjust the surface tension. By including surfactants, the adhesion between the diaphragm and the electrolysis electrode, or between the metal plate and the electrolysis electrode, changes, allowing for adjustments to the processability. There are no particular limitations on the surfactant used; either ionic or nonionic surfactants can be used.

[0348] The electrolysis electrode of this embodiment preferably comprises an electrolysis electrode substrate and a catalyst layer. The thickness (gauge thickness) of the electrolysis electrode substrate is not particularly limited, but from the perspective of achieving good processability, good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power supplies, suitability for rolling, good bending, and ease of processing at large sizes (e.g., 1.5m × 2.5m), it is preferably 300 μm or less, more preferably 205 μm or less, further preferably 155 μm or less, even more preferably 135 μm or less, even more preferably 125 μm or less, even more preferably 120 μm or less, and even more preferably 100 μm or less. From the perspective of processability and economy, it is even more preferably 50 μm or less. The lower limit value is not particularly limited, for example, it is 1 μm, preferably 5 μm, and more preferably 15 μm.

[0349] The electrode used for electrolysis in this embodiment is not particularly limited. From the perspective of obtaining good processability and good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power supplies, the proportion measured by the following method (2) is preferably 90% or more, more preferably 92% or more. Furthermore, from the perspective of facilitating processing at large sizes (e.g., 1.5m × 2.5m), it is even more preferably 95% or more. The upper limit is 100%.

[0350] [Method (2)]

[0351] An ion exchange membrane (170 mm²) and an electrolysis electrode sample (130 mm²) were sequentially laminated. Under conditions of 23 ± 2 °C and 30 ± 5% relative humidity, the laminate was placed on the curved surface of a polyethylene tube (280 mm outer diameter) with the electrolysis electrode sample on the outside. The laminate and tube were thoroughly immersed in pure water to remove excess water adhering to their surfaces. After one minute, the percentage (%) of the area where the ion exchange membrane (170 mm²) and the electrolysis electrode sample were in close contact was measured.

[0352] The electrode used for electrolysis in this embodiment is not particularly limited. However, from the perspective of obtaining good processability, good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power supplies, and the ability to be rolled up and bent easily, the proportion measured by the following method (3) is preferably 75% or more, more preferably 80% or more. Furthermore, from the perspective of facilitating processing at large sizes (e.g., 1.5m × 2.5m), it is even more preferably 90% or more. The upper limit is 100%.

[0353] [Method (3)]

[0354] An ion exchange membrane (170 mm²) and an electrolysis electrode sample (130 mm²) were sequentially laminated. Under conditions of 23 ± 2 °C and 30 ± 5% relative humidity, the laminate was placed on the curved surface of a polyethylene tube (145 mm outer diameter) with the electrolysis electrode sample on the outside. The laminate and tube were thoroughly immersed in pure water to remove excess water adhering to their surfaces. After one minute, the percentage (%) of the area where the ion exchange membrane (170 mm²) and the electrolysis electrode sample were in close contact was measured.

[0355] The electrode used for electrolysis in this embodiment is not particularly limited. However, from the perspectives of obtaining good processability, good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power supplies, and preventing the retention of gases generated during electrolysis, a porous structure is preferred, and its porosity is 5 to 90% or less. More preferably, the porosity is 10 to 80% or less, and even more preferably 20 to 75%.

[0356] It should be noted that the porosity refers to the proportion of open portions per unit volume. The calculation method varies depending on whether the open portion is considered to be down to the sub-micron level or only to openings visible to the naked eye. In this embodiment, the volume V is calculated from the values ​​of the electrode gauge thickness, width, and length, and then the actual weight W is measured. The porosity A is then calculated using the following formula.

[0357] A = (1 - (W / (V×ρ))×100)

[0358] ρ is the density of the electrode material (g / cm³). 3 For example, in the case of nickel, it is 8.908 g / cm³. 3 In the case of titanium, it is 4.506 g / cm³. 3 The porosity can be adjusted appropriately using the following methods: for perforated metal, change the area of ​​the stamped metal per unit area; for sheet metal, change the values ​​of SW (short diameter), LW (long diameter), and feed; for mesh, change the wire diameter and mesh count of the metal fibers; for electroforming, change the pattern of the photoresist used; for nonwoven fabric, change the metal fiber diameter and fiber density; for foamed metal, change the mold used to form the voids; and so on.

[0359] Regarding the electrolysis electrode in this embodiment, from a processability perspective, the value measured by the following method (A) is preferably 40 mm or less, more preferably 29 mm or less, further preferably 10 mm or less, and even more preferably 6.5 mm or less. It should be noted that the specific measurement method is as described in the examples.

[0360] [Method (A)]

[0361] Under conditions of 23±2℃ and 30±5% relative humidity, the sample formed by the laminated ion exchange membrane and the above-mentioned electrolysis electrode was wound and fixed onto the curved surface of a vinyl chloride core material with an outer diameter of Φ32mm. After standing for 6 hours, the electrolysis electrode was separated and placed on a horizontal plate. The vertical heights L1 and L2 at both ends of the electrolysis electrode were measured, and their average value was taken as the measured value.

[0362] Regarding the electrolysis electrode in this embodiment, the electrode is 50mm × 50mm in size, and the conditions are: temperature 24°C, relative humidity 32%, piston speed 0.2cm / s, and air flow rate 0.4cc / cm. 2 The aeration resistance (hereinafter referred to as "aeration resistance 1") under the condition of / s (hereinafter also referred to as "measurement condition 1") is preferably 24 kPa·s / m or less. High aeration resistance means that air is difficult to flow, indicating a high density state. Under this state, the products generated by electrolysis remain in the electrode, and the reaction matrix has difficulty diffusing into the electrode interior, thus tending to deteriorate electrolysis performance (voltage, etc.). Furthermore, there is a tendency for the concentration at the membrane surface to increase. Specifically, there is a tendency for the caustic concentration to increase at the cathode surface and the supply of brine to decrease at the anode surface. As a result, the products remain at a high concentration at the interface between the diaphragm and the electrode, thus tending to cause diaphragm damage, as well as voltage increase and membrane damage at the cathode surface and membrane damage at the anode surface. In this embodiment, to prevent these adverse conditions, it is preferable that the aeration resistance is 24 kPa·s / m or less. From the same perspective as above, it is more preferable to be less than 0.19 kPa·s / m, further preferably less than 0.15 kPa·s / m, and even more preferably less than 0.07 kPa·s / m.

[0363] It should be noted that in this embodiment, if the ventilation resistance is high enough, in the case of the cathode, the NaOH generated at the electrode will remain at the interface between the electrode and the diaphragm, tending to become highly concentrated; in the case of the anode, the brine supply will decrease, tending to become less concentrated. From the perspective of preventing potential damage to the diaphragm due to such retention, it is preferable to be less than 0.19 kPa·s / m, more preferably less than 0.15 kPa·s / m, and even more preferably less than 0.07 kPa·s / m.

[0364] On the other hand, when the ventilation resistance is low, the electrode area decreases, thus tending to decrease the electrolysis area and deteriorate the electrolysis performance (voltage, etc.). When the ventilation resistance is zero, since no electrode for electrolysis is provided, the power supply body functions as the electrode, tending to significantly deteriorate the electrolysis performance (voltage, etc.). From this perspective, there is no particular limitation on the preferred lower limit value of the ventilation resistance 1, but it is preferably greater than 0 kPa·s / m, more preferably 0.0001 kPa·s / m or more, and even more preferably 0.001 kPa·s / m or more.

[0365] It should be noted that, regarding the ventilation resistance 1, from the perspective of its measurement method, sufficient measurement accuracy is sometimes not obtainable when it is below 0.07 kPa·s / m. Therefore, for electrolytic electrodes with a ventilation resistance 1 of 0.07 kPa·s / m or less, the ventilation resistance (hereinafter referred to as "ventilation resistance 2") can also be evaluated using the following measurement method (hereinafter also referred to as "measurement condition 2"). That is, ventilation resistance 2 is defined as follows: the electrolytic electrode is 50 mm × 50 mm in size, at a temperature of 24 °C, a relative humidity of 32%, a piston speed of 2 cm / s, and a ventilation rate of 4 cc / cm³. 2 Ventilation resistance at a rate of / s.

[0366] The specific methods for measuring ventilation resistances 1 and 2 are as described in the examples.

[0367] The aforementioned ventilation resistances 1 and 2 can be adjusted to the range described below, for example, by appropriately adjusting the aperture ratio, electrode thickness, etc. More specifically, for example, if the thickness is the same, increasing the aperture ratio tends to decrease ventilation resistances 1 and 2, while decreasing the aperture ratio tends to increase ventilation resistances 1 and 2.

[0368] The following describes one embodiment of the electrode for electrolysis.

[0369] The electrolysis electrode of this embodiment preferably comprises an electrolysis electrode substrate and a catalyst layer. The catalyst layer, as described below, can consist of multiple layers or a single-layer structure.

[0370] like Figure 1 As shown, the electrolysis electrode 100 of this embodiment includes an electrolysis electrode substrate 10 and a pair of first layers 20 covering both surfaces of the electrolysis electrode substrate 10. The first layer 20 preferably covers the entire electrolysis electrode substrate 10. This easily improves the catalytic activity and durability of the electrode. It should be noted that the first layer 20 may also be deposited only on one surface of the electrolysis electrode substrate 10.

[0371] In addition, such as Figure 1As shown, the surface of the first layer 20 can be covered by the second layer 30. Preferably, the second layer 30 covers the entire first layer 20. Alternatively, the second layer 30 may be deposited on only one surface of the first layer 20.

[0372] (Electrode substrate for electrolysis)

[0373] The electrode substrate 10 for electrolysis is not particularly limited, and can be made of materials such as nickel, nickel alloys, stainless steel, and valve metals such as titanium. Preferably, it contains at least one element selected from nickel (Ni) and titanium (Ti). That is, the electrode substrate for electrolysis preferably contains at least one element selected from nickel (Ni) and titanium (Ti).

[0374] When stainless steel is used in high-concentration alkaline aqueous solutions, considering the leaching of iron and chromium, and the fact that the conductivity of stainless steel is about 1 / 10 that of nickel, a substrate containing nickel (Ni) is preferred as the electrode substrate for electrolysis.

[0375] In addition, when the electrode substrate 10 for electrolysis is used in a near-saturated high-concentration brine solution or in a chlorine-generating atmosphere, the material is preferably titanium, which has high corrosion resistance.

[0376] The shape of the electrode substrate 10 for electrolysis is not particularly limited, and an appropriate shape can be selected according to the purpose. As a shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or a so-called woven mesh made by braiding metal wires. Among these, perforated metal or metal mesh is preferred. It should be noted that electroforming refers to a technique for producing metal thin films with precise patterns by combining photolithography and electroplating. It is a method of obtaining a metal thin film by forming a pattern on a substrate using a photoresist and then electroplating the areas not protected by the photoresist.

[0377] Regarding the shape of the electrode substrate for electrolysis, appropriate specifications are available depending on the distance between the anode and cathode in the electrolytic cell. Although there are no particular limitations, when the anode and cathode have a limited distance, metal mesh or perforated metal shapes can be used. In the case of a so-called zero-gap electrolytic cell where the ion exchange membrane and the electrode are in contact, woven mesh made of fine threads, foamed metal, metal nonwoven fabric, metal mesh, perforated metal, and porous metal foil can be used.

[0378] Examples of electrode substrates 10 for electrolysis include metal foil, metal wire mesh, metal nonwoven fabric, perforated metal, metal mesh, or foamed metal.

[0379] As a sheet material to be processed into perforated metal or metal mesh, rolled sheet material or electrolytic foil is preferred. As a post-processing step, the electrolytic foil is preferably further plated with the same elements as the base material to create an uneven surface.

[0380] Furthermore, regarding the thickness of the electrode substrate 10 for electrolysis, as described above, it is preferably 300 μm or less, more preferably 205 μm or less, even more preferably 155 μm or less, further preferably 135 μm or less, even more preferably 125 μm or less, even more preferably 120 μm or less, and even more preferably 100 μm or less. From the perspective of processability and economy, it is even more preferably 50 μm or less. The lower limit is not particularly limited, for example, it is 1 μm, preferably 5 μm, and more preferably 15 μm.

[0381] In the electrode substrate for electrolysis, it is preferable to anneal the electrode substrate in an oxidizing atmosphere, thereby mitigating residual stress from processing. Furthermore, to improve adhesion to the catalyst layer coated on the surface of the electrode substrate, it is preferable to create an uneven surface using steel grating, alumina grating, or the like, followed by acid treatment to increase the surface area. It is also preferable to use the same elements as the substrate for plating treatment to increase the surface area.

[0382] For the electrode substrate 10 for electrolysis, in order to ensure close adhesion between the first layer 20 and the surface of the electrode substrate 10, it is preferable to perform a treatment that increases the surface area. Examples of treatments that increase the surface area include: sandblasting using chopped wire, steel grating, alumina grating, etc.; acid treatment using sulfuric acid or hydrochloric acid; plating using the same elements as the substrate; and so on. The arithmetic mean surface roughness (Ra) of the substrate surface is not particularly limited, but is preferably 0.05 μm to 50 μm, more preferably 0.1 to 10 μm, and even more preferably 0.1 to 5 μm.

[0383] Next, the case of using the electrolysis electrode of this embodiment as the anode for salt electrolysis will be described.

[0384] (First layer)

[0385] Figure 1 In this catalyst layer, the first layer 20 comprises at least one oxide selected from ruthenium oxide, iridium oxide, and titanium oxide. Examples of ruthenium oxides include RuO2. Examples of iridium oxides include IrO2. Examples of titanium oxides include TiO2. The first layer 20 preferably comprises both ruthenium oxide and titanium oxide, or both ruthenium oxide, iridium oxide, and titanium oxide. This makes the first layer 20 a more stable layer, further improving its adhesion to the second layer 30.

[0386] When the first layer 20 contains both ruthenium oxide and titanium oxide, the amount of titanium oxide in the first layer 20 is preferably 1 to 9 moles, more preferably 1 to 4 moles, relative to 1 mole of ruthenium oxide. By maintaining the composition ratio of the two oxides within this range, the electrolytic electrode 100 exhibits excellent durability.

[0387] When the first layer 20 contains ruthenium oxide, iridium oxide, and titanium oxide, the amount of iridium oxide in the first layer 20 is preferably 0.2 to 3 moles, more preferably 0.3 to 2.5 moles, relative to 1 mole of ruthenium oxide. Similarly, the amount of titanium oxide in the first layer 20 is preferably 0.3 to 8 moles, more preferably 1 to 7 moles, relative to 1 mole of ruthenium oxide. By maintaining the composition ratio of the three oxides within this range, the electrolytic electrode 100 exhibits excellent durability.

[0388] When the first layer 20 contains at least two oxides selected from ruthenium oxide, iridium oxide, and titanium oxide, these oxides preferably form a solid solution. By forming an oxide solid solution, the electrolytic electrode 100 exhibits excellent durability.

[0389] In addition to the above-mentioned components, substances with various compositions can be used as long as they contain at least one oxide selected from ruthenium oxide, iridium oxide, and titanium oxide. For example, an oxide coating containing ruthenium, iridium, tantalum, niobium, titanium, tin, cobalt, manganese, platinum, etc., known as DSA (registered trademark) can also be used as the first layer 20.

[0390] The first layer 20 does not need to be a single layer, and may contain multiple layers. For example, the first layer 20 may contain a layer containing three oxides and a layer containing two oxides. The thickness of the first layer 20 is preferably 0.05 to 10 μm, more preferably 0.1 to 8 μm.

[0391] (Second layer)

[0392] The second layer 30 preferably contains ruthenium and titanium. This further reduces the chlorine overvoltage immediately after electrolysis.

[0393] The second layer 30 preferably comprises palladium oxide, a solid solution of palladium oxide and platinum, or an alloy of palladium and platinum. This further reduces the chlorine overvoltage immediately after electrolysis.

[0394] When the second layer is 30 μm thick, the period during which electrolytic performance can be maintained will be longer, but from an economic point of view, a thickness of 0.05 to 3 μm is preferred.

[0395] Next, the case of using the electrolysis electrode of this embodiment as the cathode for salt electrolysis will be described.

[0396] (First layer)

[0397] The composition of the first layer 20, which serves as the catalyst layer, can include metals such as C, Si, P, S, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, as well as their oxides or hydroxides.

[0398] In cases where at least one of platinum group metals, platinum group metal oxides, platinum group metal hydroxides, or alloys containing platinum group metals is included, the platinum group metals, platinum group metal oxides, platinum group metal hydroxides, or alloys containing platinum group metals preferably include at least one platinum group metal selected from platinum, palladium, rhodium, ruthenium, and iridium.

[0399] As a platinum group metal, it preferably contains platinum.

[0400] As a platinum group metal oxide, it preferably contains ruthenium oxide.

[0401] As a platinum group metal hydroxide, it is preferred to include ruthenium hydroxide.

[0402] As a platinum group metal alloy, an alloy containing platinum, nickel, iron, and cobalt is preferred.

[0403] Furthermore, if necessary, oxides or hydroxides containing lanthanides are preferably used as the second component. As a result, the electrolytic electrode 100 exhibits excellent durability.

[0404] As an oxide or hydroxide of a lanthanide element, it preferably contains at least one selected from lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, and dysprosium.

[0405] Furthermore, if necessary, oxides or hydroxides containing transition metals are preferably used as the third component.

[0406] By adding a third component, the electrolytic electrode 100 exhibits superior durability and can reduce the electrolysis voltage.

[0407] Examples of preferred combinations include those consisting solely of ruthenium, ruthenium + nickel, ruthenium + cerium, ruthenium + lanthanum, ruthenium + lanthanum + platinum, ruthenium + lanthanum + palladium, ruthenium + praseodymium, ruthenium + praseodymium + platinum, ruthenium + praseodymium + platinum + palladium, ruthenium + neodymium, ruthenium + neodymium + platinum, ruthenium + neodymium + manganese, ruthenium + neodymium + iron, ruthenium + neodymium + cobalt, ruthenium + neodymium + zinc, ruthenium + neodymium + gallium, ruthenium + neodymium + sulfur, ruthenium + neodymium + lead, ruthenium + neodymium + nickel, and ruthenium + Neodymium + Copper, Ruthenium + Samarium, Ruthenium + Samarium + Manganese, Ruthenium + Samarium + Iron, Ruthenium + Samarium + Cobalt, Ruthenium + Samarium + Zinc, Ruthenium + Samarium + Gallium, Ruthenium + Samarium + Sulfur, Ruthenium + Samarium + Lead, Ruthenium + Samarium + Nickel, Platinum + Cerium, Platinum + Palladium + Cerium, Platinum + Palladium + Lanthanum + Cerium, Platinum + Iridium, Platinum + Palladium, Platinum + Iridium + Palladium, Platinum + Nickel + Palladium, Platinum + Nickel + Ruthenium, Platinum and Nickel alloys, Platinum and Cobalt alloys, Platinum and Iron alloys, etc.

[0408] In the absence of platinum group metals, platinum group metal oxides, platinum group metal hydroxides, or alloys containing platinum group metals, the main component of the catalyst is preferably nickel.

[0409] Preferably, it contains at least one of nickel metal, oxide, and hydroxide.

[0410] Transition metals may also be added as a second component. Preferably, the added second component includes at least one element selected from titanium, tin, molybdenum, cobalt, manganese, iron, sulfur, zinc, copper, and carbon.

[0411] Preferred combinations include nickel + tin, nickel + titanium, nickel + molybdenum, and nickel + cobalt.

[0412] If necessary, an intermediate layer can be provided between the first layer 20 and the electrode substrate 10 for electrolysis. By providing an intermediate layer, the durability of the electrode 100 for electrolysis can be improved.

[0413] As an intermediate layer, it is preferable to have an affinity for both the first layer 20 and the electrolytic electrode substrate 10. Nickel oxide, platinum group metals, platinum group metal oxides, and platinum group metal hydroxides are preferred as the intermediate layer. The intermediate layer can be formed by coating a solution containing the components forming the intermediate layer and then firing it, or by heat-treating the substrate in an air atmosphere at a temperature of 300–600°C to form a surface oxide layer. Alternatively, it can be formed using known methods such as thermal spraying or ion plating.

[0414] (Second layer)

[0415] The composition of the first layer 30, which serves as the catalyst layer, can include metals such as C, Si, P, S, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, as well as oxides or hydroxides of these metals. It may contain at least one of platinum group metals, platinum group metal oxides, platinum group metal hydroxides, or alloys containing platinum group metals, or it may not contain any. Examples of preferred combinations of elements included in the second layer include combinations mentioned in the first layer. The combination of the first and second layers can be a combination with the same composition but different composition ratios, or a combination with different compositions.

[0416] The thickness of the catalyst layer, including the intermediate layer, is preferably 0.01 μm to 20 μm. If it is 0.01 μm or more, it can fully function as a catalyst. If it is 20 μm or less, there is less detachment from the substrate, resulting in a robust catalyst layer. More preferably, it is 0.05 μm to 15 μm. More preferably, it is 0.1 μm to 10 μm. Even more preferably, it is 0.2 μm to 8 μm.

[0417] The thickness of the electrode, i.e., the total thickness of the electrode substrate and the catalyst layer for electrolysis, is preferably 315 μm or less, more preferably 220 μm or less, even more preferably 170 μm or less, even more preferably 150 μm or less, particularly preferably 145 μm or less, even more preferably 140 μm or less, even more preferably 138 μm or less, and even more preferably 135 μm or less, from the perspective of electrode processability. Good processability can be obtained when the thickness is 135 μm or less. Furthermore, from the same perspective as above, it is preferably 130 μm or less, more preferably less than 130 μm, even more preferably 115 μm or less, and even more preferably 65 μm or less. The lower limit is not particularly limited, but it is preferably 1 μm or more, and from a practical perspective, it is more preferably 5 μm or more, and even more preferably 20 μm or more. It should be noted that the electrode thickness can be determined by measuring it with a digital thickness gauge (Mitutoyo Co., Ltd., minimum display 0.001 mm). The thickness of the electrode substrate for electrolysis is measured in the same manner as the electrode thickness. The thickness of the catalyst layer can be determined by subtracting the thickness of the electrode substrate for electrolysis from the electrode thickness.

[0418] (Manufacturing method of electrodes for electrolysis)

[0419] Next, one embodiment of the method for manufacturing the electrolysis electrode 100 will be described in detail.

[0420] In this embodiment, an electrolytic electrode 100 is manufactured by forming a first layer 20, preferably a second layer 30, on an electrolytic electrode substrate through methods such as firing (thermal decomposition) of a coating film under an oxygen atmosphere, or ion plating, plating, or thermal spraying. Thermal decomposition, plating, and ion plating are preferred because they can form a catalyst layer while suppressing deformation of the electrolytic electrode substrate. Furthermore, from the perspective of productivity, plating and thermal decomposition are even more preferred. This manufacturing method of this embodiment achieves high productivity for the electrolytic electrode 100. Specifically, in the case of thermal decomposition, a catalyst layer is formed on the electrolytic electrode substrate through a coating process of applying a coating liquid containing a catalyst, a drying process of drying the coating liquid, and a thermal decomposition process of thermal decomposition. Here, thermal decomposition refers to heating a metal salt as a precursor to decompose it into a metal or metal oxide and a gaseous substance. The decomposition products vary depending on the type of metal used, the type of salt, and the atmosphere in which thermal decomposition is performed; however, many metals tend to easily form oxides under an oxidizing atmosphere. In the industrial manufacturing process of electrodes for electrolysis, thermal decomposition usually takes place in air, and in most cases forms metal oxides or metal hydroxides.

[0421] (Formation of the first layer of the anode)

[0422] (Coating process)

[0423] The first layer 20 is obtained by coating an electrode substrate containing a solution of at least one metal salt selected from ruthenium, iridium, and titanium (a first coating solution) onto the substrate, followed by thermal decomposition (firing) in the presence of oxygen. The content of ruthenium, iridium, and titanium in the first coating solution is approximately equal to that in the first layer 20.

[0424] The metal salt can be any of the following: chloride salt, nitrate salt, sulfate salt, metal alkoxide, or other salt. The solvent for the first coating solution can be selected according to the type of metal salt, and can be water or alcohols such as butanol. Water or a mixture of water and alcohol is preferred as the solvent. The total metal concentration in the first coating solution containing the dissolved metal salt is not particularly limited, but a range of 10–150 g / L is preferred, taking into account the thickness of the coating film formed in a single coating application.

[0425] Methods for applying the first coating liquid to the electrolytic electrode substrate 10 include immersion methods (immersing the electrolytic electrode substrate 10 in the first coating liquid), brush coating methods (coating the first coating liquid with brush bristles), roller coating methods (using a sponge-like roller impregnated with the first coating liquid), and electrostatic coating methods (spraying the electrolytic electrode substrate 10 and the first coating liquid with opposite charges). Among these, roller coating or electrostatic coating methods, which have excellent industrial productivity, are preferred.

[0426] (Drying process, thermal decomposition process)

[0427] After applying a first coating solution to the electrode substrate 100 for electrolysis, it is dried at a temperature of 10–90°C and then thermally decomposed in a firing furnace heated to 350–650°C. During drying and thermal decomposition, pre-firing can be performed at 100–350°C as needed. The drying, pre-firing, and thermal decomposition temperatures can be appropriately selected based on the composition or solvent type of the first coating solution. A longer duration for each thermal decomposition is preferred; from the perspective of electrode productivity, 3–60 minutes is preferred, and 5–20 minutes is more preferred.

[0428] By repeating the above-described cycle of coating, drying, and thermal decomposition, the coating (first layer 20) is formed to a specified thickness. After forming the first layer 20, further heating followed by prolonged firing as needed can further improve the stability of the first layer 20.

[0429] (Formation of the second layer of the anode)

[0430] The second layer 30 is formed as needed, for example, by coating a solution containing palladium and platinum compounds or a solution containing ruthenium and titanium compounds (the second coating solution) onto the first layer 20 and then thermally decomposing it in the presence of oxygen.

[0431] (Formation of the first layer of the cathode using thermal decomposition)

[0432] (Coating process)

[0433] The first layer 20 is obtained by coating a solution containing various combinations of metal salts (first coating solution) onto an electrolytic electrode substrate, followed by thermal decomposition (firing) in the presence of oxygen. The metal content in the first coating solution is approximately equal to that in the first layer 20.

[0434] The metal salt can be any of the following: chloride salt, nitrate salt, sulfate salt, metal alkoxide, or other salt. The solvent for the first coating solution can be selected based on the type of metal salt, and can be water or alcohols such as ethanol and butanol. Water or a mixture of water and alcohols is preferred as the solvent. The total metal concentration in the first coating solution containing the dissolved metal salt is not particularly limited, but a range of 10–150 g / L is preferred, taking into account the thickness of the coating film formed in a single coating application.

[0435] Methods for applying the first coating liquid to the electrolytic electrode substrate 10 include immersion methods (immersing the electrolytic electrode substrate 10 in the first coating liquid), brush coating methods (coating the first coating liquid with brush bristles), roller coating methods (using a sponge-like roller impregnated with the first coating liquid), and electrostatic coating methods (spraying the electrolytic electrode substrate 10 and the first coating liquid with opposite charges). Among these, roller coating or electrostatic coating methods, which have excellent industrial productivity, are preferred.

[0436] (Drying process, thermal decomposition process)

[0437] After the first coating solution is applied to the electrode substrate 10 for electrolysis, it is dried at a temperature of 10–90°C and then thermally decomposed in a firing furnace heated to 350–650°C. During drying and thermal decomposition, pre-firing can be performed at 100–350°C as needed. The drying, pre-firing, and thermal decomposition temperatures can be appropriately selected according to the composition or solvent type of the first coating solution. A longer thermal decomposition time is preferred; from the perspective of electrode productivity, 3–60 minutes is preferred, and 5–20 minutes is more preferred.

[0438] Repeating the above-described cycle of coating, drying, and thermal decomposition will form the coating (first layer 20) to a specified thickness. After forming the first layer 20, further prolonged firing as needed, such as heating at 350°C to 650°C for 1 to 90 minutes, can further improve the stability of the first layer 20.

[0439] (Formation of the intermediate layer)

[0440] The intermediate layer is formed as needed, for example, by applying a solution containing a palladium compound or platinum compound (second coating solution) to the substrate and then thermally decomposing it in the presence of oxygen. Alternatively, the solution may not be applied, but the substrate may be heated at a temperature of 300°C to 580°C for 1 to 60 minutes to form a nickel oxide intermediate layer on the substrate surface.

[0441] (The formation of the first layer of the cathode using ion plating)

[0442] The first layer 20 can also be formed using ion plating.

[0443] As an example, a method can be described where a substrate is fixed within a chamber and an electron beam is irradiated onto a ruthenium target. Evaporated ruthenium particles become positively charged in the plasma within the chamber and accumulate on a negatively charged substrate. The plasma atmosphere is argon and oxygen, and ruthenium is deposited on the substrate in the form of ruthenium oxide.

[0444] (Utilizing the formation of the first layer of the plated cathode)

[0445] The first layer 20 can also be formed using a plating method.

[0446] As an example, if a substrate is used as the cathode and electroplating is performed in an electrolyte containing nickel and tin, an alloy coating of nickel and tin can be formed.

[0447] (Formation of the first layer of the cathode using thermal spraying)

[0448] The first layer 20 can also be formed using thermal spraying.

[0449] As an example, nickel oxide particles are plasma-sprayed onto a substrate, thereby forming a catalyst layer composed of a mixture of metallic nickel and nickel oxide.

[0450] The electrolysis electrode of this embodiment can be integrated with membranes such as ion exchange membranes or microporous membranes. Therefore, it can be used as a membrane-integrated electrode, eliminating the need for cathode and anode replacement operations when updating electrodes, thus significantly improving operational efficiency.

[0451] In this embodiment, the electrolysis electrode is laminated with a membrane such as an ion exchange membrane or a microporous membrane, becoming an integral part of the membrane and electrode. This allows the electrolysis performance to be the same as or even improved compared to that of a new product. There are no particular limitations on the membrane as long as it can form a laminate with the electrode; a detailed explanation follows.

[0452] Ion exchange membrane

[0453] The ion exchange membrane comprises: a membrane substrate containing a hydrocarbon polymer or a fluorinated polymer having ion exchange groups; and a coating layer disposed on at least one surface of the membrane substrate. Furthermore, the coating layer comprises inorganic particles and a binder, and the specific surface area of ​​the coating layer is 0.1–10 m². 2 / g. For ion exchange membranes with this structure, the gas generated during electrolysis has little impact on electrolysis performance, and can exhibit stable electrolysis performance.

[0454] The above-mentioned ion exchange membrane has ion exchange groups (-SO3) derived from sulfonyl groups. - The group represented (hereinafter also referred to as "sulfonic acid group") is a sulfonic acid layer, and has an ion exchange group (-CO2) from a carboxyl group. - The group represented (hereinafter also referred to as "carboxylic acid group") is any one of the carboxylic acid layers. From the perspective of strength and dimensional stability, it is preferable to further have a reinforcing core material.

[0455] Inorganic particles and adhesives are described in detail below in the section on coating.

[0456] Figure 2 This is a cross-sectional schematic diagram illustrating one embodiment of an ion exchange membrane. The ion exchange membrane 1 has: a membrane body 10 comprising a hydrocarbon polymer or a fluorinated polymer having ion exchange groups; and coating layers 11a and 11b formed on both sides of the membrane body 10.

[0457] In ion exchange membrane 1, the membrane body 10 comprises a sulfonic acid layer 3 and a carboxylic acid layer 2, and its strength and dimensional stability are enhanced by a reinforcing core material 4. Ion exchange membrane 1, comprising the sulfonic acid layer 3 and the carboxylic acid layer 2, is therefore suitable for use as an ion exchange membrane.

[0458] It should be noted that ion exchange membranes can also contain only either a sulfonic acid layer or a carboxylic acid layer. Furthermore, ion exchange membranes do not necessarily require reinforcement with a core material, and the configuration of the core material is not limited to a specific configuration. Figure 2 Examples.

[0459] (Membrane body)

[0460] First, the membrane body 10 constituting the ion exchange membrane 1 will be described.

[0461] The membrane body 10 has the function of selectively permeating cations. It can contain hydrocarbon polymers or fluorinated polymers with ion exchange groups. There are no special limitations on its composition or materials. Suitable composition or materials can be selected appropriately.

[0462] The hydrocarbon polymer or fluorinated polymer with ion exchange groups in the membrane body 10 can be obtained, for example, from a hydrocarbon polymer or fluorinated polymer having an ion exchange group precursor that can be converted into an ion exchange group through hydrolysis or the like. Specifically, for example, a polymer whose main chain is composed of fluorinated hydrocarbons, has groups (ion exchange group precursors) that can be converted into ion exchange groups through hydrolysis or the like as side chains, and is capable of melt processing (hereinafter referred to as "fluorinated polymer (a)" as appropriate) can be used to prepare the precursor of the membrane body 10, and then the ion exchange group precursor can be converted into ion exchange groups to obtain the membrane body 10.

[0463] Fluorinated polymers (a) can be manufactured, for example, by copolymerizing at least one monomer selected from Group 1 below with at least one monomer selected from Group 2 and / or Group 3 below. Alternatively, they can be manufactured by homopolymerization of a monomer selected from any one of Group 1, Group 2 and Group 3 below.

[0464] Examples of monomers in Group 1 include fluorinated vinyl compounds. Examples of fluorinated vinyl compounds include ethylene fluoride, tetrafluoroethylene, hexafluoropropylene, vinylidene fluoride, trifluoroethylene, trifluorochloroethylene, and perfluoroalkyl vinyl ethers. In particular, when using an ion exchange membrane as a membrane for alkaline electrolysis, the fluorinated vinyl compound is preferably a perfluorinated monomer, and more preferably a perfluorinated monomer selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, and perfluoroalkyl vinyl ethers.

[0465] As monomers in Group 2, examples include vinyl compounds having functional groups capable of being converted into carboxylic acid ion exchange groups (carboxylic acid groups). For example, CF2=CF(OCF2CYF) is a vinyl compound having functional groups capable of being converted into carboxylic acid groups. s -O(CZF) t-COOR indicates monomers, etc. (here, s represents an integer from 0 to 2, t represents an integer from 1 to 12, Y and Z each independently represent F or CF3, and R represents a lower alkyl group. Lower alkyl groups are, for example, alkyl groups with 1 to 3 carbon atoms.)

[0466] Of these, CF2 = CF(OCF2CYF) is preferred. n -O(CF2) m -COOR represents the compound. Here, n represents an integer from 0 to 2, m represents an integer from 1 to 4, Y represents F or CF3, and R represents CH3, C2H5, or C3H7.

[0467] It should be noted that when using an ion exchange membrane as a cation exchange membrane for alkaline electrolysis, it is preferable to use at least a perfluorinated compound as a monomer. However, since the alkyl group of the ester group (refer to R above) is removed from the polymer during hydrolysis, the alkyl group (R) may not be a perfluorinated alkyl group in which all hydrogen atoms are replaced by fluorine atoms.

[0468] As for the monomers in the second group, among the above, the monomers indicated below are more preferred.

[0469] CF2=CFOCF2-CF(CF3)OCF2COOCH3,

[0470] CF2=CFOCF2CF(CF3)O(CF2)2COOCH3,

[0471] CF2=CF[OCF2-CF(CF3)]2O(CF2)2COOCH3,

[0472] CF2=CFOCF2CF(CF3)O(CF2)3COOCH3,

[0473] CF2=CFO(CF2)2COOCH3、

[0474] CF2=CFO(CF2)3COOCH3.

[0475] As monomers in Group 3, examples include vinyl compounds having functional groups capable of being converted to sulfonate ion-exchange groups (sulfonic acid groups). As vinyl compounds having functional groups capable of being converted to sulfonic acid groups, monomers represented by CF2=CFO-X-CF2-SO2F (where X represents a perfluoroalkylene group) are preferred. Specific examples include monomers represented below.

[0476] CF2 = CFOCF2CF2SO2F,

[0477] CF2=CFOCF2CF(CF3)OCF2CF2SO2F,

[0478] CF2=CFOCF2CF(CF3)OCF2CF2CF2SO2F,

[0479] CF2=CF(CF2)2SO2F、

[0480] CF2=CFO[CF2CF(CF3)O]2CF2CF2SO2F,

[0481] CF2=CFOCF2CF(CF2OCF3)OCF2CF2SO2F.

[0482] Among these, CF2=CFOCF2CF(CF3)OCF2CF2CF2SO2F and CF2=CFOCF2CF(CF3)OCF2CF2SO2F are preferred.

[0483] The copolymers obtained from these monomers can be manufactured using polymerization methods developed for homopolymerization and copolymerization of fluorinated ethylene, and especially the general polymerization methods used for tetrafluoroethylene. For example, in a non-aqueous method, inert solvents such as perfluorocarbons and chlorofluorocarbons can be used, and polymerization can be carried out in the presence of free radical polymerization initiators such as perfluorocarbon peroxides or azo compounds, at temperatures of 0–200°C and pressures of 0.1–20 MPa.

[0484] In the above copolymerization, the types and proportions of the monomers are not particularly limited, and are selected based on the type and amount of functional groups desired to be imparted to the resulting fluorinated polymer. For example, in the case of forming a fluorinated polymer containing only carboxylic acid groups, at least one monomer from each of the above groups 1 and 2 can be copolymerized. Similarly, in the case of forming a fluorinated polymer containing only sulfonic acid groups, at least one monomer from each of the above groups 1 and 3 can be copolymerized. Furthermore, in the case of forming a fluorinated polymer having both carboxylic acid and sulfonic acid groups, at least one monomer from each of the above groups 1, 2, and 3 can be copolymerized. In this case, copolymers composed of groups 1 and 2 and copolymers composed of groups 1 and 3 are polymerized separately, and then mixed to obtain the target fluorinated polymer. Furthermore, the mixing ratio of each monomer is not particularly limited; to increase the amount of functional groups per unit polymer, simply increase the proportion of monomers selected from groups 2 and 3.

[0485] The total ion exchange capacity of the fluorinated copolymer is not particularly limited, but is preferably 0.5 to 2.0 mg equivalents / g, more preferably 0.6 to 1.5 mg equivalents / g. Here, the total ion exchange capacity refers to the equivalent of exchange groups per unit weight of the dried resin, which can be determined by neutralization titration or the like.

[0486] In the membrane body 10 of the ion exchange membrane 1, a sulfonic acid layer 3 comprising a fluorinated polymer having sulfonic acid groups and a carboxylic acid layer 2 comprising a fluorinated polymer having carboxylic acid groups are laminated. By forming the membrane body 10 with this layered structure, the selective permeability of cations such as sodium ions can be further improved.

[0487] When the ion exchange membrane 1 is placed in an electrolyzer, it is usually arranged such that the sulfonic acid layer 3 is located on the anode side of the electrolyzer and the carboxylic acid layer 2 is located on the cathode side of the electrolyzer.

[0488] The sulfonic acid layer 3 is preferably made of a material with low electrical resistance, and from the perspective of film strength, it is preferable that the film thickness is thicker than that of the carboxylic acid layer 2. The film thickness of the sulfonic acid layer 3 is preferably 2 to 25 times that of the carboxylic acid layer 2, and more preferably 3 to 15 times.

[0489] The carboxylic acid layer 2 preferably exhibits high anion rejection capacity even when the membrane is thin. Anion rejection capacity, as referred to here, means the property of preventing anions from penetrating or permeating into the ion exchange membrane 1. To improve anion rejection capacity, it is effective to configure a carboxylic acid layer or similar layer with a smaller ion exchange capacity compared to the sulfonic acid layer.

[0490] As a fluorinated polymer for sulfonic acid layer 3, for example, a polymer obtained by using CF2=CFOCF2CF(CF3)OCF2CF2SO2F as a monomer of group 3 is suitable.

[0491] As a fluorinated polymer for carboxylic acid layer 2, for example, a polymer obtained by using CF2=CFOCF2CF(CF2)O(CF2)2COOCH3 as a monomer of group 2 is suitable.

[0492] (Coating layer)

[0493] The ion exchange membrane has a coating layer on at least one surface of the membrane substrate. Additionally, as... Figure 2 As shown, in the ion exchange membrane 1, coating layers 11a and 11b are formed on both sides of the membrane body 10, respectively.

[0494] The coating layer contains inorganic particles and adhesives.

[0495] The average particle size of the inorganic particles is more preferably 0.90 μm or more. When the average particle size of the inorganic particles is 0.90 μm or more, not only is the adhesion to gas improved, but the durability against impurities is also greatly enhanced. That is, by increasing the average particle size of the inorganic particles while simultaneously satisfying the above-mentioned specific surface area value, a particularly significant effect can be obtained. Due to satisfying this average particle size and specific surface area, irregularly shaped inorganic particles are preferred. Inorganic particles obtained by melting or by pulverizing raw ore can be used. Preferably, inorganic particles obtained by pulverizing raw ore can be used appropriately.

[0496] Furthermore, the average particle size of the inorganic particles can be 2 μm or less. If the average particle size of the inorganic particles is 2 μm or less, damage to the membrane due to the inorganic particles can be prevented. More preferably, the average particle size of the inorganic particles is 0.90 to 1.2 μm.

[0497] Here, the average particle size can be measured using a particle size analyzer ("SALD2200" Shimadzu Corporation).

[0498] The inorganic particles are preferably irregularly shaped. This further improves their tolerance to impurities. Furthermore, the particle size distribution of the inorganic particles is preferably broad.

[0499] The inorganic particles preferably comprise at least one inorganic material selected from the group consisting of oxides of elements in Group IV of the periodic table, nitrides of elements in Group IV of the periodic table, and carbides of elements in Group IV of the periodic table. From a durability perspective, zirconium oxide particles are more preferred.

[0500] The inorganic particles are preferably inorganic particles manufactured by crushing the raw ore of inorganic particles, or by melting and refining the raw ore of inorganic particles, and using the resulting spherical particles with uniform particle size as inorganic particles.

[0501] There are no particular limitations on the method for crushing raw ore, and examples include ball mills, bead mills, colloid mills, conical mills, disc mills, edge mills, pulverizing mills, hammer mills, particle mills, VSI mills, Wiley mills, roller mills, and jet mills. Furthermore, it is preferable to perform washing after crushing, and acid treatment is preferred as the washing method. This reduces impurities such as iron adhering to the surface of inorganic particles.

[0502] The coating layer preferably includes an adhesive. The adhesive is a component that holds inorganic particles on the surface of the ion exchange membrane to form the coating layer. From the perspective of resistance to electrolyte or electrolysis products, the adhesive preferably includes a fluorinated polymer.

[0503] As an adhesive, fluorinated polymers having carboxylic acid groups or sulfonic acid groups are more preferred from the perspectives of resistance to electrolytes or electrolysis products and adhesion to the surface of ion exchange membranes. When a coating layer is provided on a layer containing a fluorinated polymer with sulfonic acid groups (sulfonic acid layer), a fluorinated polymer with sulfonic acid groups is even more preferred as the adhesive for this coating layer. Furthermore, when a coating layer is provided on a layer containing a fluorinated polymer with carboxylic acid groups (carboxylic acid layer), a fluorinated polymer with carboxylic acid groups is even more preferred as the adhesive for this coating layer.

[0504] In the coating layer, the content of inorganic particles is preferably 40-90% by mass, more preferably 50-90% by mass. Additionally, the content of the binder is preferably 10-60% by mass, more preferably 10-50% by mass.

[0505] The preferred distribution density of the coating layer in the ion exchange membrane is per 1 cm. 2 The concentration is 0.05–2 mg. Furthermore, when the ion exchange membrane has an uneven surface, the preferred coating density is per 1 cm³. 2 The dosage is 0.5–2 mg.

[0506] There are no particular limitations on the method for forming the coating layer, and known methods can be used. For example, the following method can be used: dispersing inorganic particles in a solution containing an adhesive, and applying the resulting coating liquid by spraying or the like.

[0507] (Reinforced core material)

[0508] The ion exchange membrane preferably has a reinforcing core material disposed inside the membrane body.

[0509] The reinforcing core material is a component that enhances the strength and dimensional stability of the ion exchange membrane. By placing the reinforcing core material inside the membrane body, the expansion and contraction of the ion exchange membrane can be controlled within a desired range. This ensures that the ion exchange membrane does not expand or contract beyond the necessary extent during electrolysis, thus maintaining excellent dimensional stability over a long period.

[0510] The composition of the reinforcing core material is not particularly limited; for example, it can be formed by spinning a filament called a reinforcing fiber. The reinforcing fiber, as referred to here, is a component constituting the reinforcing core material, meaning a filament capable of imparting the desired dimensional stability and mechanical strength to the ion exchange membrane and being able to exist stably within the ion exchange membrane. By using a reinforcing core material spun from this reinforcing fiber, the ion exchange membrane can be endowed with superior dimensional stability and mechanical strength.

[0511] The materials for the reinforcing core and the reinforcing filaments used in the reinforcing core are not particularly limited, but materials resistant to acids and alkalis are preferred. Since heat resistance and chemical resistance are required for a long time, fibers made of fluorinated polymers are preferred.

[0512] Examples of fluorinated polymers used as reinforcing core materials include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-ethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene copolymer, trifluorochloroethylene-ethylene copolymer, and vinylidene fluoride polymer (PVDF). Among these, fibers made of polytetrafluoroethylene are particularly preferred from the perspective of heat resistance and chemical resistance.

[0513] The diameter of the reinforcing filaments used to reinforce the core material is not particularly limited, but is preferably 20–300 denier, more preferably 50–250 denier. The weaving density (number of weft threads per unit length) is preferably 5–50 threads / inch. The method of using the reinforcing core material is not particularly limited; for example, woven fabric, nonwoven fabric, or braided fabric can be used, but woven fabric is preferred. Furthermore, regarding the thickness of the woven fabric, a thickness of 30–250 μm is preferred, more preferably 30–150 μm.

[0514] Fabric can be woven or braided using monofilament, multifilament or their yarns, cut film yarns, etc., and various weaving methods can be used, such as plain weave, leno weave, knit, rib weave, crepe stripe weave, etc.

[0515] There are no particular limitations on the weaving method and configuration of the reinforcing core material in the membrane body. The size or shape of the ion exchange membrane, the desired physical properties of the ion exchange membrane, and the usage environment can be taken into account to set a suitable configuration.

[0516] For example, the reinforcing core material can be arranged along a predetermined direction of the membrane body, but from the perspective of dimensional stability, it is preferable to arrange the reinforcing core material along a predetermined first direction and arrange other reinforcing core materials along a second direction that is substantially perpendicular to the first direction. Within the longitudinal interior of the membrane body, by arranging a plurality of reinforcing core materials in a substantially straight manner, superior dimensional stability and mechanical strength can be imparted in multiple directions. For example, it is preferable to weave longitudinally arranged reinforcing core materials (warp) and transversely arranged reinforcing core materials (weft) onto the surface of the membrane body. From the perspectives of dimensional stability, mechanical strength, and ease of manufacture, more preferred are: plain weave, in which warp and weft alternately float and sink; leno weave, in which two warp threads are twisted while being woven with the weft; square plain weave, in which two or more warp threads are aligned and weave the same number of weft threads; and so on.

[0517] It is particularly preferable to arrange the reinforcing core material along both the MD (Machine Direction, longitudinal direction) and TD (Transverse Direction, transverse direction) directions of the ion exchange membrane. That is, it is preferable to weave it flat in both the MD and TD directions. Here, the MD direction refers to the direction (flow direction) in which the membrane body and various core materials (e.g., reinforcing core material, reinforcing wire, sacrificial wire, etc., described later) are conveyed during the manufacturing process of the ion exchange membrane, and the TD direction refers to the direction approximately perpendicular to the MD direction. Furthermore, the filament woven along the MD direction is called an MD filament, and the filament woven along the TD direction is called a TD filament. Typically, ion exchange membranes used for electrolysis are mostly rectangular, with the length direction being the MD direction and the width direction being the TD direction. By weaving in reinforcing core material as MD filament and reinforcing core material as TD filament, superior dimensional stability and mechanical strength can be imparted in multiple directions.

[0518] There are no particular limitations on the spacing of the reinforced core material; the appropriate spacing can be determined by considering the desired physical properties of the ion exchange membrane and the operating environment.

[0519] The opening ratio of the reinforcing core material is not particularly limited, but is preferably 30% or more, more preferably 50% or more and 90% or less. Regarding the opening ratio, from the perspective of the electrochemical properties of the ion exchange membrane, it is preferably 30% or more, and from the perspective of the mechanical strength of the ion exchange membrane, it is preferably 90% or less.

[0520] The aperture ratio of the reinforcing core material refers to the proportion (B / A) of the total surface area (A) through which substances such as ions (electrolyte and cations contained therein, e.g., sodium ions) can pass. The total surface area (B) through which substances such as ions can pass refers to the total area of ​​the ion exchange membrane where cations, electrolytes, etc., are not blocked by the reinforcing core material or similar components contained in the ion exchange membrane.

[0521] Figure 3 This is a schematic diagram illustrating the aperture ratio of the reinforcing core material that constitutes an ion exchange membrane. Figure 3 A portion of the ion exchange membrane is magnified, showing only the configuration of the reinforcing core materials 21 and 22 within that region; other components are omitted from the illustration.

[0522] By subtracting the total area (C) of the reinforcing core material from the area (A) of the region (the region being the area surrounded by the longitudinally arranged reinforcing core material 21 and the transversely arranged reinforcing core material 22, and the area (A) including the area of ​​the reinforcing core material), the total area (B) of the region (A) through which ions and other substances can pass can be calculated. That is, the aperture ratio can be calculated by the following formula (I).

[0523] Opening ratio=(B) / (A)=((A)-(C)) / (A)…(I)

[0524] In terms of chemical resistance and heat resistance, the reinforced core material is particularly preferred to be a flat filament or a highly oriented monofilament containing PTFE. Specifically, more preferred methods include: cutting a high-strength porous sheet made of PTFE into strip-shaped flat filaments; or a reinforced core material made of highly oriented monofilaments of PTFE with a denier of 50 to 300 denier and a weaving density of 10 to 50 threads / inch, with a thickness ranging from 50 to 100 μm. The aperture ratio of the ion exchange membrane containing this reinforced core material is further preferably 60% or more.

[0525] Examples of reinforcing filament shapes include round filaments and ribbon filaments.

[0526] (Connecting hole)

[0527] The ion exchange membrane preferably has interconnecting pores inside the membrane body.

[0528] A connecting pore is a pore that serves as a flow channel for ions and electrolyte generated during electrolysis. Alternatively, a connecting pore can also refer to a tubular pore formed within the membrane matrix, created by the dissolution of the sacrificial core material (or sacrificial wire), described later. The shape and diameter of the connecting pore can be controlled by selecting the shape and diameter of the sacrificial core material (sacrificial wire).

[0529] By forming interconnecting pores in the ion exchange membrane, the mobility of the electrolyte can be ensured during electrolysis. The shape of the interconnecting pores is not particularly limited and can be the shape of the sacrificial core material used to form the interconnecting pores, according to the manufacturing method described later.

[0530] The connecting pores are preferably formed in a manner that alternates between the anode side (sulfonic acid layer side) and the cathode side (carboxylic acid layer side) of the reinforcing core material. With this structure, the portion of the reinforcing core material with connecting pores formed on the cathode side allows ions (e.g., sodium ions) transported through the electrolyte filling the connecting pores to also flow to the cathode side of the reinforcing core material. As a result, the flow of cations is not impeded, thus further reducing the resistance of the ion exchange membrane.

[0531] The connecting pores may be formed only in one specified direction of the membrane body constituting the ion exchange membrane, but from the perspective of achieving more stable electrolysis performance, it is preferable to form them in both the longitudinal and transverse directions of the membrane body.

[0532] [Manufacturing Method]

[0533] As a preferred manufacturing method for ion exchange membranes, a method having the following steps (1) to (6) can be cited.

[0534] (1) Process: The process of manufacturing fluorinated polymers that have ion exchange groups or ion exchange group precursors that can become ion exchange groups by hydrolysis.

[0535] (2) Process: As needed, at least a plurality of reinforcing core materials and sacrificial yarns that are soluble in acid or alkali and form interconnected pores are woven in to obtain a reinforcing material in which sacrificial yarns are arranged between adjacent reinforcing core materials.

[0536] (3) Process: The process of membraneizing the above-mentioned fluorinated polymer having ion exchange groups or ion exchange group precursors that can become ion exchange groups through hydrolysis.

[0537] (4) Process: The process of embedding the above-mentioned reinforcing material into the above-mentioned membrane as needed to obtain a membrane body with the above-mentioned reinforcing material disposed inside.

[0538] (5) Process: The process of hydrolyzing the membrane substrate obtained in (4) (hydrolysis process).

[0539] (6) Process: The process of applying a coating layer to the membrane body obtained in process (5) (coating process).

[0540] The following is a detailed description of each process.

[0541] (1) Process: The process of manufacturing fluorinated polymers

[0542] In step (1), the monomers of the raw materials described in groups 1 to 3 above are used to manufacture a fluorinated polymer. In order to control the ion exchange capacity of the fluorinated polymer, the mixing ratio of the monomers of the raw materials can be adjusted during the manufacturing of the fluorinated polymer that forms each layer.

[0543] (2) Process: Manufacturing process of reinforced materials

[0544] Reinforcing materials refer to fabrics or similar materials woven from reinforcing fibers. By embedding the reinforcing material within the membrane, a reinforcing core material is formed. When manufacturing an ion exchange membrane with interconnected pores, sacrificial fibers are also woven into the reinforcing material. The preferred percentage of sacrificial fibers in this process is 10–80% by mass of the total reinforcing material, more preferably 30–70% by mass. Weaving in sacrificial fibers also helps prevent misalignment of the reinforcing core material.

[0545] The sacrificial fibers are soluble in the membrane manufacturing process or electrolytic environment, and materials such as rayon, polyethylene terephthalate (PET), cellulose, and polyamide are used. Additionally, polyvinyl alcohol with a thickness of 20–50 denier and composed of monofilaments or multifilaments is preferred.

[0546] It should be noted that in process (2), by adjusting the configuration of the reinforcing core material and the sacrificial wire, the opening ratio and the configuration of the connecting holes can be controlled.

[0547] (3) Process: Membrane formation process

[0548] In step (3), the fluorinated polymer obtained in step (1) is film-formed using an extruder. The film can be a single-layer structure, or a two-layer structure consisting of a sulfonic acid layer and a carboxylic acid layer as described above, or a multi-layer structure with three or more layers.

[0549] As a method for performing membrane formation, the following methods can be cited, for example.

[0550] A method for separately membraneizing fluoropolymers with carboxylic acid groups and fluoropolymers with sulfonic acid groups.

[0551] A method for preparing a composite film by co-extrusion of a fluoropolymer with carboxylic acid groups and a fluoropolymer with sulfonic acid groups.

[0552] It should be noted that the membrane can consist of two or more sheets. Furthermore, co-extruding different types of membranes helps improve the interfacial adhesion strength, and is therefore preferred.

[0553] (4) Process: The process of obtaining the membrane substrate

[0554] In step (4), the reinforcing material obtained in step (2) is embedded inside the membrane obtained in step (3), thereby obtaining a membrane body containing the reinforcing material inside.

[0555] Preferred methods for forming the membrane body include: (i) co-extruding a fluorinated polymer having a carboxylic acid precursor (e.g., a carboxylic acid ester functional group) located on the cathode side (hereinafter referred to as the first layer) and a fluorinated polymer having a sulfonic acid precursor (e.g., a sulfonyl fluoride functional group) (hereinafter referred to as the second layer) by means of a co-extrusion process, using a heating source and a vacuum source as needed, and laminating the membrane onto a flat plate or cylinder with numerous fine pores on the surface, separated by a breathable, heat-resistant release paper, in the order of reinforcing material, second layer / first layer composite membrane, and so on. (ii) A method of removing air between layers by depressurization at the melting temperature of the polymer and simultaneously integrating them; (ii) A separate operation with the second / first layer composite film, wherein a fluorinated polymer (third layer) having a sulfonic acid precursor is pre-filmed separately, and a heat source and vacuum source are used as needed, and the third layer film, the reinforcing core material, and the composite film consisting of the second / first layer are laminated in the order of the third layer film, the reinforcing core material, and the composite film consisting of the second / first layer, with the air between layers removed by depressurization at the melting temperature of each polymer and simultaneously integrating them.

[0556] Here, co-extruding the first and second layers helps to improve the bonding strength of the interface.

[0557] Furthermore, compared to the pressure pressing method, the depressurized integration method features an increased thickness of the third layer on the reinforcing material. In addition, since the reinforcing material is fixed to the inner surface of the membrane body, it possesses the ability to adequately maintain the mechanical strength of the ion exchange membrane.

[0558] It should be noted that the lamination transformation pattern described here is an example. Alternatively, one can consider the desired layer composition or physical properties of the membrane body, and choose a suitable lamination pattern (e.g., the combination of layers) before co-extrusion.

[0559] It should be noted that, in order to further improve the electrical performance of the ion exchange membrane, a fourth layer composed of a fluorinated polymer having both carboxylic acid group precursors and sulfonic acid group precursors can be sandwiched between the first layer and the second layer, or, in place of the second layer, a fourth layer composed of a fluorinated polymer having both carboxylic acid group precursors and sulfonic acid group precursors can be used.

[0560] The fourth layer can be formed by mixing a fluorinated polymer having a carboxylic acid precursor and a fluorinated polymer having a sulfonic acid precursor, or by using a substance copolymerized from a monomer having a carboxylic acid precursor and a monomer having a sulfonic acid precursor.

[0561] When the fourth layer is composed of an ion exchange membrane, the first and fourth layers can be co-extruded to form a membrane, while the third and second layers are separately membraneized and laminated using the method described above; alternatively, the first, fourth, and second layers can be membraneized in one step through co-extrusion.

[0562] In this case, the direction of the extruded membrane flow is the MD direction. Thus, a membrane matrix comprising a fluorinated polymer with ion exchange groups can be formed on the reinforcing material.

[0563] Furthermore, the ion exchange membrane preferably has a protruding portion, or convex portion, made of a fluoropolymer with sulfonic acid groups on the surface side composed of a sulfonic acid layer. There is no particular limitation on the method for forming such a convex portion, and known methods for forming convex portions on the resin surface can be used. Specifically, for example, a method of embossing the surface of the membrane body can be employed. For example, when integrating the aforementioned composite membrane and reinforcing material, the aforementioned convex portion can be formed by using a pre-embossed release paper. When the convex portion is formed by embossing, the height and density of the convex portion can be controlled by controlling the embossing shape (the shape of the release paper) used for transfer.

[0564] (5) Hydrolysis process

[0565] In step (5), the following steps are performed: the membrane substrate obtained in step (4) is hydrolyzed to convert the ion exchanger precursor into an ion exchanger (hydrolysis step).

[0566] Additionally, in step (5), the sacrificial fibers contained in the membrane body can be dissolved and removed using acid or alkali, thereby forming dissolution pores in the membrane body. It should be noted that the sacrificial fibers may remain in the interconnecting pores and are not completely dissolved and removed. Furthermore, the sacrificial fibers remaining in the interconnecting pores can be dissolved and removed by the electrolyte when the ion exchange membrane is supplied with electrolyte.

[0567] Sacrificial wires are soluble in acids or bases during the manufacturing process and electrolysis environment of ion exchange membranes. The sacrificial wires dissolve and form interconnecting pores in the corresponding areas.

[0568] (5) The process can be carried out by immersing the membrane body obtained in step (4) in a hydrolysis solution containing an acid or an alkali. For example, a mixed solution containing KOH and DMSO (dimethyl sulfoxide) can be used as the hydrolysis solution.

[0569] The mixed solution preferably contains 2.5–4.0 N KOH and 25–35% by mass DMSO.

[0570] The hydrolysis temperature is preferably 70–100°C. Higher temperatures result in greater apparent thickness. 75–100°C is more preferred.

[0571] The hydrolysis time is preferably 10 to 120 minutes. The longer the time, the greater the increase in apparent thickness. More preferably, it is 20 to 120 minutes.

[0572] Here, the process of dissolving the sacrificial wire to form a connecting hole is explained in more detail. Figure 4 (a) and (b) are schematic diagrams illustrating the method of forming the connecting pores of an ion exchange membrane.

[0573] exist Figure 4 In (a) and (b), only the connecting hole 504 formed by the reinforcing wire 52, the sacrificial wire 504a and the sacrificial wire 504a is shown, and other components such as the membrane body are omitted from the illustration.

[0574] First, a reinforcing material is made by weaving in reinforcing wires 52, which constitute the reinforcing core material in the ion exchange membrane, and sacrificial wires 504a, which are used to form connecting pores 504 in the ion exchange membrane. Then, the connecting pores 504 are formed by dissolving the sacrificial wires 504a in step (5).

[0575] According to the above method, the weaving method of reinforcing wire 52 and sacrificial wire 504a can be adjusted according to the configuration of the reinforcing core material and the connecting holes in the membrane body of the ion exchange membrane, which is very simple.

[0576] exist Figure 4 (a) illustrates a plain-woven reinforcing material formed by weaving reinforcing yarns 52 and sacrificial yarns 504a into the paper surface in both longitudinal and transverse directions, but the configuration of reinforcing yarns 52 and sacrificial yarns 504a in the reinforcing material can be changed as needed.

[0577] (6) Coating process

[0578] In step (6), a coating liquid containing inorganic particles obtained by crushing or melting raw ore and a binder is prepared. The coating liquid is applied to the surface of the ion exchange membrane obtained in step (5) and dried, thereby forming a coating layer.

[0579] As an adhesive, an adhesive obtained as follows is preferred: a fluorinated polymer having an ion-exchange group precursor is hydrolyzed with an aqueous solution containing dimethyl sulfoxide (DMSO) and potassium hydroxide (KOH), and then impregnated in hydrochloric acid to replace the counter ion of the ion-exchange group with H+. + (For example, fluorinated polymers having carboxyl or sulfonyl groups). Therefore, they are readily soluble in water or ethanol, as described later, and are thus preferred.

[0580] The adhesive is dissolved in a solution containing water and ethanol. It should be noted that the preferred volume ratio of water to ethanol is 10:1 to 1:10, more preferably 5:1 to 1:5, and even more preferably 2:1 to 1:2. The inorganic particles are dispersed in the resulting solution using a ball mill to obtain a coating solution. The average particle size can be adjusted by changing the dispersion time and rotation speed. It should be noted that the preferred mixing ratio of the inorganic particles and the adhesive is as described above.

[0581] There are no particular limitations on the concentration of inorganic particles and binders in the coating solution, but a dilute coating solution is preferred. This allows for uniform coating onto the surface of the ion exchange membrane.

[0582] In addition, when dispersing inorganic particles, a surfactant can be added to the dispersion. Nonionic surfactants are preferred, such as HS-210, NS-210, P-210, and E-212 manufactured by Nippon Oil Co., Ltd.

[0583] The obtained coating solution is applied to the surface of the ion exchange membrane by spray coating or roller coating, thereby obtaining the ion exchange membrane.

[0584] [Microporous membrane]

[0585] As described above, there are no particular limitations on the microporous membrane used in this embodiment, as long as it can form a laminate with the electrolysis electrode, and various microporous membranes can be used.

[0586] The porosity of the microporous membrane in this embodiment is not particularly limited, but can be, for example, 20 to 90, preferably 30 to 85. The above porosity can be calculated, for example, using the following formula.

[0587] Porosity = (1 - (Weight of the membrane in dry state) / (Weight calculated based on the volume of the membrane from its thickness, width, and length, and the density of the membrane feedstock)) × 100

[0588] The average pore size of the microporous membrane in this embodiment is not particularly limited, and can be, for example, 0.01 μm to 10 μm, preferably 0.05 μm to 5 μm. Regarding the above average pore size, for example, the membrane is cut perpendicular to the thickness direction, and the cross-section is observed using FE-SEM. The average pore size is calculated by measuring approximately 100 points of the observed pore diameter.

[0589] The thickness of the microporous membrane in this embodiment is not particularly limited, and can be, for example, 10 μm to 1000 μm, preferably 50 μm to 600 μm. The thickness can be measured, for example, using a micrometer (manufactured by Mitutoyo Co., Ltd.).

[0590] Specific examples of the aforementioned microporous membranes include the Zirfon Perl UTP 500 manufactured by Agfa Corporation (also referred to as the Zirfon membrane in this embodiment), International Publication No. 2013-183584, and International Publication No. 2016-203701.

[0591] [laminated body]

[0592] The laminate of this embodiment includes the electrolysis electrode of this embodiment and a diaphragm or power supply in contact with the electrolysis electrode. Due to this configuration, the laminate of this embodiment can improve the efficiency of electrode replacement in the electrolytic cell, and thus exhibit excellent electrolytic performance even after replacement.

[0593] That is, according to the laminate of this embodiment, when updating the electrode, the electrode can be updated using the same simple operation as the diaphragm update without complicated operations such as peeling off the electrode fixed to the electrolysis unit, thus greatly improving the work efficiency.

[0594] Furthermore, the laminate according to the present invention can maintain the performance of a new product or improve the electrolysis performance. In addition, when a new electrolysis unit is provided with only a power supply (i.e., an electrode without a catalyst layer is provided), it can function as an electrode simply by attaching the electrolysis electrode of this embodiment to the power supply, thus significantly reducing or completely eliminating the need for catalyst coating.

[0595] The laminate of this embodiment can be stored and transported to customers in a state of being wound around, for example, a PVC tube (in rolls), making it very easy to handle.

[0596] It should be noted that, as the power supply in this embodiment, various substrates, such as degraded electrodes (i.e., original electrodes) or electrodes without catalyst coating, can be used.

[0597] In the laminate of this embodiment, the force applied per unit mass and unit area of ​​the electrolysis electrode to the diaphragm or power supply is preferably 0.08 N / (mg·cm²). 2 0.1 N / (mg·cm³) or more, preferably 0.1 N / (mg·cm³) 2 ) or higher, and more preferably 0.14 N / (mg·cm 2 From the perspective of easier processing of large-sized objects (e.g., 1.5m × 2.5m), a value of 0.2 N / (mg·cm³) is more preferable. 2 The upper limit is not specifically limited, but is preferably 1.6 N / (mg·cm). 2 ) or less, more preferably less than 1.6 N / (mg·cm 2 Further preferred is less than 1.5 N / (mg·cm). 2 ), and more preferably 1.2 N / mg·cm 2 The following, and more preferably, is 1.20 N / mg·cm 2 The following is a further preferred value: 1.1 N / mg·cm³. 2 The following, and more preferably, is 1.10 N / mg·cm⁻¹ 2 The following, particularly preferred, value is 1.0 N / mg·cm⁻¹ 2 The following, and especially preferred, value is 1.00 N / mg·cm⁻¹. 2 the following.

[0598] [Wound Body]

[0599] The wound body of this embodiment includes the electrolysis electrode of this embodiment or the laminate of this embodiment. That is, the wound body of this embodiment is formed by winding the electrolysis electrode of this embodiment or the laminate of this embodiment. As with the wound body of this embodiment, by winding the electrolysis electrode of this embodiment or the laminate of this embodiment, the size is reduced, thereby further improving processability.

[0600] Electrolytic cell

[0601] The electrolytic cell of this embodiment includes the electrolysis electrodes of this embodiment. Hereinafter, an embodiment of the electrolytic cell will be described in detail, taking the use of an ion exchange membrane as a diaphragm for salt electrolysis as an example.

[0602] [Electrolysis Unit]

[0603] Figure 5 This is a cross-sectional view of electrolysis unit 1.

[0604] Electrolysis unit 1 includes an anode chamber 10, a cathode chamber 20, a partition wall 30 disposed between the anode chamber 10 and the cathode chamber 20, an anode 11 disposed in the anode chamber 10, and a cathode 21 disposed in the cathode chamber 20. If necessary, a reverse current absorber 18 disposed in the cathode chamber may also be included. The reverse current absorber 18 has a substrate 18a and a reverse current absorbing layer 18b formed on the substrate 18a. The anode 11 and cathode 21 belonging to one electrolysis unit 1 are electrically connected to each other. In other words, electrolysis unit 1 includes the following cathode structure: Cathode structure 40 includes a cathode chamber 20, a cathode 21 disposed in the cathode chamber 20, and a reverse current absorber 18 disposed within the cathode chamber 20. The reverse current absorber 18 is as follows: Figure 9The cathode 21 has a substrate 18a and a reverse current absorption layer 18b formed on the substrate 18a, and the reverse current absorption layer 18b is electrically connected to the cathode 21. The cathode chamber 20 further includes a current collector 23, a support 24 supporting the current collector, and a metal elastomer 22. The metal elastomer 22 is disposed between the current collector 23 and the cathode 21. The support 24 is disposed between the current collector 23 and the isolation wall 30. The current collector 23 is electrically connected to the cathode 21 via the metal elastomer 22. The isolation wall 30 is electrically connected to the current collector 23 via the support 24. Therefore, the isolation wall 30, the support 24, the current collector 23, the metal elastomer 22, and the cathode 21 are electrically connected. The cathode 21 is electrically connected to the reverse current absorption layer 18b. The cathode 21 and the reverse current absorption layer can be directly connected or indirectly connected via the current collector, the support, the metal elastomer, or the isolation wall. The entire surface of the cathode 21 is preferably covered with a catalyst layer for the reduction reaction. Alternatively, the electrical connection can be achieved by directly mounting the isolation wall 30 and the support 24, directly mounting the support 24 and the current collector 23, or directly mounting the current collector 23 and the metallic elastomer 22, with the cathode 21 laminated on the metallic elastomer 22. Welding is an example of a method for directly mounting these components together. Alternatively, the reverse current absorber 18, the cathode 21, and the current collector 23 can be collectively referred to as the cathode structure 40.

[0605] Figure 6 This is a cross-sectional view of two adjacent electrolysis units 1 within electrolysis cell 4. Figure 7 Electrolytic cell 4 is shown. Figure 8 The process of assembling electrolytic cell 4 is shown. For example... Figure 6 As shown, the electrolysis unit 1, cation exchange membrane 2, and electrolysis unit 1 are arranged in series. An ion exchange membrane 2 is disposed between the anode chamber of one electrolysis unit 1 and the cathode chamber of the other electrolysis unit 1 within two adjacent electrolysis units in the electrolytic cell. That is, the anode chamber 10 of electrolysis unit 1 and the cathode chamber 20 of the adjacent electrolysis unit 1 are separated by the cation exchange membrane 2. Figure 7 As shown, the electrolytic cell 4 is composed of a plurality of electrolytic units 1 connected in series with ion exchange membranes 2 in between. That is, the electrolytic cell 4 is a bipolar electrolytic cell having a plurality of electrolytic units 1 arranged in series and ion exchange membranes 2 disposed between adjacent electrolytic units 1. Figure 8 As shown, the electrolytic cell 4 is assembled by arranging a plurality of electrolysis units 1 in series with ion exchange membranes 2 in between and connecting them with a pressure device 5.

[0606] The electrolytic cell 4 has an anode terminal 7 and a cathode terminal 6 connected to a power source. The anode 11 of the electrolytic unit 1 located at the far end of the plurality of electrolytic units 1 connected in series within the electrolytic cell 4 is electrically connected to the anode terminal 7. The cathode 21 of the electrolytic unit located at the end opposite to the anode terminal 7 of the plurality of electrolytic units 2 connected in series within the electrolytic cell 4 is electrically connected to the cathode terminal 6. During electrolysis, the current flows from the anode terminal 7 side through the anode and cathode of each electrolytic unit 1 to the cathode terminal 6. It should be noted that electrolytic units with only an anode chamber (anode terminal unit) and electrolytic units with only a cathode chamber (cathode terminal unit) can also be configured at both ends of the connected electrolytic unit 1. In this case, the anode terminal 7 is connected to the anode terminal unit located at one end, and the cathode terminal 6 is connected to the cathode terminal unit located at the other end.

[0607] In the case of brine electrolysis, brine is supplied to each anode chamber 10, and pure water or a low-concentration sodium hydroxide aqueous solution is supplied to the cathode chamber 20. Each liquid is supplied to each electrolysis unit 1 from an electrolyte supply pipe (omitted in the figure) via an electrolyte supply hose (omitted in the figure). Furthermore, the electrolyte and electrolysis products are recovered by an electrolyte recovery pipe (omitted in the figure). During electrolysis, sodium ions in the brine move from the anode chamber 10 of one electrolysis unit 1 to the cathode chamber 20 of the adjacent electrolysis unit 1 via the ion exchange membrane 2. Thus, the current in the electrolysis flows along the series connection direction of the electrolysis units 1. That is, the current flows from the anode chamber 10 to the cathode chamber 20 via the cation exchange membrane 2. Accompanying the brine electrolysis, chlorine gas is generated on the anode 11 side, and sodium hydroxide (solute) and hydrogen gas are generated on the cathode 21 side.

[0608] (Anode chamber)

[0609] The anode chamber 10 has an anode 11 or an anode power supply 11. When the electrolysis electrode of this embodiment is inserted into the anode side, 11 functions as an anode power supply. When the electrolysis electrode of this embodiment is not inserted into the anode side, 11 functions as an anode. In addition, the anode chamber 10 preferably has: an anode-side electrolyte supply section for supplying electrolyte to the anode chamber 10; a baffle plate disposed above the anode-side electrolyte supply section and disposed substantially parallel to or inclined to the isolation wall 30; and an anode-side gas-liquid separation section disposed above the baffle plate for separating gas from the electrolyte mixed with gas.

[0610] (anode)

[0611] Without inserting the electrolysis electrode of this embodiment into the anode side, an anode 11 is provided within the frame of the anode chamber 10. The anode 11 can be a metal electrode such as a so-called DSA (registered trademark). DSA refers to an electrode made of a titanium substrate whose surface is coated with an oxide composed of ruthenium, iridium, and titanium.

[0612] As for the shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or so-called woven mesh made by braiding metal wires.

[0613] (Anode power supply)

[0614] When the electrolysis electrode of this embodiment is inserted into the anode side, an anode power supply 11 is provided within the frame of the anode chamber 10. The anode power supply 11 can be a metal electrode such as a so-called DSA (registered trademark), or it can be titanium without catalyst coating. Alternatively, a DSA with a reduced catalyst coating thickness can also be used. Furthermore, a previously used anode can also be used.

[0615] As for the shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or so-called woven mesh made by braiding metal wires.

[0616] (Anode-side electrolyte supply section)

[0617] An anode-side electrolyte supply unit supplies electrolyte to the anode chamber 10 and is connected to an electrolyte supply pipe. The anode-side electrolyte supply unit is preferably located below the anode chamber 10. For example, a pipe (dispersion pipe) with an opening formed on its surface can be used as the anode-side electrolyte supply unit. More preferably, this pipe is arranged parallel to the bottom 19 of the electrolysis unit along the surface of the anode 11. This pipe is connected to an electrolyte supply pipe (liquid supply nozzle) that supplies electrolyte to the electrolysis unit 1. The electrolyte supplied by the liquid supply nozzle is conveyed into the electrolysis unit 1 through the pipe and supplied into the interior of the anode chamber 10 from the opening provided on the surface of the pipe. Arranging the pipe parallel to the bottom 19 of the electrolysis unit along the surface of the anode 11 allows for uniform supply of electrolyte into the interior of the anode chamber 10, which is therefore preferable.

[0618] (Anode-side gas-liquid separation section)

[0619] The anode-side gas-liquid separator is preferably positioned above the baffle plate. In electrolysis, the anode-side gas-liquid separator functions to separate generated gases such as chlorine from the electrolyte. It should be noted that, unless otherwise specified, "above" refers to... Figure 5 In electrolysis unit 1, the upward direction and the downward direction refer to... Figure 5 The downward direction in electrolysis unit 1.

[0620] During electrolysis, if the generated gas and electrolyte produced in electrolysis unit 1 become a mixed phase (gas-liquid mixture) and are discharged outside the system, vibration will occur due to pressure fluctuations inside electrolysis unit 1, sometimes causing physical damage to the ion exchange membrane. To suppress this phenomenon, it is preferable that the electrolysis unit 1 of this embodiment is provided with an anode-side gas-liquid separation section for separating the gas and liquid. A defoaming plate for eliminating bubbles is preferably provided in the anode-side gas-liquid separation section. When the gas-liquid mixture flows through the defoaming plate, the bubbles break, thereby separating into electrolyte and gas. As a result, vibration during electrolysis can be prevented.

[0621] (Baffle plate)

[0622] The baffle is preferably positioned above the electrolyte supply section on the anode side and is arranged substantially parallel or inclined to the isolation wall 30. The baffle acts as a partition to control the flow of electrolyte in the anode chamber 10. By providing the baffle, the electrolyte (such as brine) can circulate internally within the anode chamber 10, resulting in a uniform concentration. To generate this internal circulation, the baffle is preferably arranged to separate the space near the anode 11 from the space near the isolation wall 30. In this respect, the baffle is preferably positioned facing each surface of the anode 11 and the isolation wall 30. In the space near the anode separated by the baffle, as electrolysis proceeds, the electrolyte concentration (brine concentration) decreases, and gases such as chlorine are generated. This creates a gas-liquid density difference between the space near the anode 11 and the space near the isolation wall 30. This density difference promotes internal circulation of the electrolyte in the anode chamber 10, resulting in a more uniform electrolyte concentration distribution within the anode chamber 10.

[0623] It should be noted that, although not shown in Figure 5 However, a current collector can be separately installed inside the anode chamber 10. This current collector can also be made of the same material or structure as the current collector in the cathode chamber, which will be described later. Alternatively, the anode 11 itself can function as a current collector in the anode chamber 10.

[0624] (Isolation wall)

[0625] An isolation wall 30 is disposed between the anode chamber 10 and the cathode chamber 20. The isolation wall 30 is sometimes referred to as a separation plate, which divides the anode chamber 10 and the cathode chamber 20. As the isolation wall 30, materials known as separation plates for electrolysis can be used, for example, an isolation wall with a nickel plate welded to the cathode side or a titanium plate welded to the anode side can be cited.

[0626] (Cathode chamber)

[0627] Regarding the cathode chamber 20, when the electrolysis electrode of this embodiment is inserted into the cathode side, 21 functions as a cathode power supply; when the electrolysis electrode of this embodiment is not inserted into the cathode side, 21 functions as a cathode. In the case of a reverse current absorber, the cathode or cathode power supply 21 is electrically connected to the reverse current absorber. Furthermore, the cathode chamber 20, like the anode chamber 10, preferably has a cathode-side electrolyte supply section and a cathode-side gas-liquid separation section. It should be noted that descriptions of the parts constituting the cathode chamber 20 that are the same as those constituting the anode chamber 10 are omitted.

[0628] (cathode)

[0629] Without inserting the electrolysis electrode of this embodiment into the cathode side, a cathode 21 is provided within the frame of the cathode chamber 20. The cathode 21 preferably has a nickel substrate and a catalyst layer coated with the nickel substrate. Examples of components for the catalyst layer on the nickel substrate include metals such as Ru, C, Si, P, S, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Rh, Pd, Ag, Cd, In, Sn, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, as well as oxides or hydroxides of these metals. Examples of methods for forming the catalyst layer include plating, alloy plating, dispersion / composite plating, CVD, PVD, thermal decomposition, and spraying. These methods can also be combined. The catalyst layer can have multiple layers and multiple elements as needed. Additionally, the cathode 21 can be subjected to a reduction treatment as required. It should be noted that nickel, nickel alloys, or nickel-plated iron or stainless steel substrates can also be used as the substrate for the cathode 21.

[0630] As for the shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or so-called woven mesh made by braiding metal wires.

[0631] (Cathode power supply)

[0632] When the electrolysis electrode of this embodiment is inserted into the cathode side, a cathode power supply 21 is provided within the frame of the cathode chamber 20. The cathode power supply 21 may be coated with a catalyst component. This catalyst component may be a substance that was originally used as a cathode and remains there. Examples of catalyst layer components include metals such as Ru, C, Si, P, S, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Rh, Pd, Ag, Cd, In, Sn, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, as well as oxides or hydroxides of these metals. Methods for forming the catalyst layer include plating, alloy plating, dispersion / composite plating, CVD, PVD, thermal decomposition, and spraying. These methods may also be combined. The catalyst layer can have multiple layers and multiple elements as needed. It should be noted that the substrate for the cathode power supply body 21 can also be nickel, nickel alloy, or nickel-plated iron or stainless steel.

[0633] Alternatively, the power supply unit 21 may also use uncoated nickel, nickel alloys, or nickel-plated materials on iron or stainless steel.

[0634] As for the shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or so-called woven mesh made by braiding metal wires.

[0635] (Reverse current absorption layer)

[0636] A material with a lower redox potential than the element used in the catalyst layer of the cathode can be selected as the material for the reverse current absorption layer. For example, nickel and iron can be cited.

[0637] (Current collector)

[0638] The cathode chamber 20 preferably includes a current collector 23. This improves the current collection effect. In this embodiment, the current collector 23 is preferably a perforated plate and is arranged substantially parallel to the surface of the cathode 21.

[0639] The current collector 23 is preferably made of conductive metals such as nickel, iron, copper, silver, and titanium. The current collector 23 can also be a mixture, alloy, or composite oxide of these metals. It should be noted that the shape of the current collector 23 can be any shape, as long as it functions as a current collector; it can be plate-like or mesh-like.

[0640] (Metallic elastomer)

[0641] By providing a metallic elastomer 22 between the current collector 23 and the cathode 21, each cathode 21 of the series-connected plurality of electrolysis units 1 is pressed against the ion exchange membrane 2, shortening the distance between each anode 11 and each cathode 21, thereby reducing the voltage applied to the entire series-connected plurality of electrolysis units 1. By reducing the voltage, power consumption can be reduced. Furthermore, by providing the metallic elastomer 22, when a laminate containing the electrolysis electrode of the present invention is disposed in the electrolysis unit, the pressing pressure generated by the metallic elastomer 22 can stably maintain the electrolysis electrode in a fixed position.

[0642] As the metallic elastomer 22, spring components such as helical springs and coils, and cushioning pads can be used. A suitable metallic elastomer can be selected to account for factors such as the stress on the ion exchange membrane. The metallic elastomer 22 can be disposed on the surface of the current collector 23 on the cathode chamber 20 side, or on the surface of the isolation wall on the anode chamber 10 side. Typically, the cathode chamber 20 is divided into two chambers, with the anode chamber 10 being smaller than the cathode chamber 10. Therefore, considering the strength of the frame, it is preferable to place the metallic elastomer 22 between the current collector 23 and the cathode 21 in the cathode chamber 20. Furthermore, the metallic elastomer 23 is preferably made of a conductive metal such as nickel, iron, copper, silver, or titanium.

[0643] (Support structure)

[0644] The cathode chamber 20 preferably includes a support 24 that electrically connects the current collector 23 and the isolation wall 30. This allows for efficient current flow.

[0645] The support 24 is preferably made of a conductive metal such as nickel, iron, copper, silver, or titanium. Furthermore, the shape of the support 24 can be any shape, as long as it can support the current collector 23; it can be rod-shaped, plate-shaped, or mesh-shaped. For example, the support 24 is plate-shaped. A plurality of supports 24 are disposed between the isolation wall 30 and the current collector 23. The plurality of supports 24 are arranged such that their respective faces are parallel to each other. The supports 24 are arranged substantially perpendicular to the isolation wall 30 and the current collector 23.

[0646] (Anode side gasket, cathode side gasket)

[0647] The anode-side gasket is preferably disposed on the surface of the frame constituting the anode chamber 10. The cathode-side gasket is preferably disposed on the surface of the frame constituting the cathode chamber 20. The electrolysis units are connected to each other in such a way that the ion exchange membrane 2 is sandwiched between the anode-side gasket of one electrolysis unit and the cathode-side gasket of the adjacent electrolysis unit (see reference). Figure 5 , 6 These gaskets enable airtightness at the connection points when multiple electrolysis units 1 are connected in series via ion exchange membrane 2.

[0648] A gasket is a component used to seal the connection between the ion exchange membrane and the electrolysis unit. Specific examples of gaskets include frame-shaped rubber sheets with a central opening. Gaskets must be resistant to corrosive electrolytes or generated gases and be usable for extended periods. Therefore, considering chemical resistance and hardness, vulcanized or peroxide-crosslinked products of ethylene propylene diene monomer (EPDM) rubber or diethylene propylene diene monomer (EPM) rubber are commonly used as gaskets. Alternatively, gaskets whose liquid-contact areas (liquid contact portions) are coated with fluorinated resins such as polytetrafluoroethylene (PTFE) or tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) can be used as needed. These gaskets are not particularly limited in shape as long as they have openings that do not obstruct electrolyte flow. For example, frame-shaped gaskets can be adhered with adhesives or similar materials around the periphery of each opening in the anode chamber frame constituting the anode chamber 10 or the cathode chamber frame constituting the cathode chamber 20. Additionally, for example, in the case where two electrolysis units 1 are connected through an ion exchange membrane 2 (see reference). Figure 6 Each electrolysis unit 1, with its gasket attached, is then secured through the ion exchange membrane 2. This prevents the electrolyte, alkali metal hydroxides generated during electrolysis, chlorine gas, hydrogen gas, etc., from leaking to the outside of the electrolysis unit 1.

[0649] (Ion exchange membrane 2)

[0650] As ion exchange membrane 2, it is as described in the section on ion exchange membranes above.

[0651] (Water electrolysis)

[0652] The electrolytic cell of this embodiment is an electrolytic cell for water electrolysis, and it has the following configuration: the ion exchange membrane in the electrolytic cell for salt electrolysis described above is replaced with a microporous membrane. Furthermore, it differs from the electrolytic cell for salt electrolysis in that the supplied raw material is water. Regarding other configurations, the electrolytic cell for water electrolysis can also adopt the same configuration as the electrolytic cell for salt electrolysis. In the case of salt electrolysis, chlorine gas is generated in the anode chamber, so titanium is used as the material for the anode chamber. However, in the case of water electrolysis, only oxygen is generated in the anode chamber, so the same material as the cathode chamber can be used. For example, nickel can be used. In addition, the anode coating is suitable as a catalyst coating for oxygen generation. Examples of catalyst coatings include platinum group metals and transition metals, oxides, hydroxides, etc. For example, elements such as platinum, iridium, palladium, ruthenium, nickel, cobalt, and iron can be used.

[0653] <Second Implementation Method>

[0654] Here, refer to Figures 22-42 The second embodiment of the present invention will be described in detail.

[0655] [laminated body]

[0656] The laminate of the second embodiment (hereinafter, in the section on the second embodiment, it is simply referred to as "this embodiment") includes an electrolytic electrode and a diaphragm or power supply in contact with the electrolytic electrode. The force applied per unit mass per unit area of ​​the electrolytic electrode to the diaphragm or power supply is less than 1.5 N / mg·cm². 2 Because of this configuration, the laminate of this embodiment can improve the efficiency of electrode replacement in the electrolytic cell, and thus exhibit excellent electrolytic performance even after replacement.

[0657] That is, according to the laminate of this embodiment, when updating the electrodes, the electrodes can be updated using the same simple operation as the diaphragm update without complicated operations such as peeling off the original electrodes fixed to the electrolysis unit, thus greatly improving work efficiency.

[0658] Furthermore, the laminate according to the present invention can maintain the performance of a new product or improve the electrolysis performance. Therefore, the electrodes that are fixed to existing new electrolysis units and function as anodes and cathodes can simply function as power sources, which can significantly reduce or completely eliminate catalyst coating.

[0659] The laminate of this embodiment can be stored and transported to customers in a state of being wound around, for example, a PVC tube (in rolls), making it very easy to handle.

[0660] It should be noted that, as the power supply in this embodiment, various substrates, such as degraded electrodes (i.e., original electrodes) and electrodes without catalyst coating, can be used.

[0661] Furthermore, the laminate of this embodiment, as long as it has the above-described configuration, may also partially include a fixing portion. That is, when the laminate of this embodiment has a fixing portion, the portion without the fixing portion is tested, and the force applied per unit mass / unit area of ​​the resulting electrolytic electrode is less than 1.5 N / mg·cm. 2 That's all.

[0662] Electrolysis electrodes

[0663] Regarding the electrolysis electrode of this embodiment, from the aspects of obtaining good processability and good adhesion to membranes such as ion exchange membranes or microporous membranes, and power supply bodies (degraded electrodes and electrodes without catalyst coating), the force applied per unit mass / unit area is less than 1.5 N / mg·cm. 2 The preferred value is 1.2 N / mg·cm³. 2 The following, and more preferably, is 1.20 N / mg·cm2 The following is a further preferred value: 1.1 N / mg·cm³. 2 The following, and more preferably, is 1.10 N / mg·cm⁻¹ 2 The following, and more preferably, is 1.0 N / mg·cm 2 The following, and even more preferably, is 1.00 N / mg·cm⁻¹ 2 the following.

[0664] From the perspective of further improving electrolysis performance, a value exceeding 0.005 N / (mg·cm⁻¹) is preferred. 2 ), more preferably 0.08 N / (mg·cm 2 ) or higher, and more preferably 0.1 N / mg·cm 2 The above, and more preferably, is 0.14 N / (mg·cm³). 2 The above is preferred because it makes processing larger sizes (e.g., 1.5m × 2.5m) easier. 2 )above.

[0665] The applied force described above can be adjusted to the range described below, for example, by appropriately adjusting the porosity, electrode thickness, arithmetic mean surface roughness, etc. More specifically, for example, increasing the porosity tends to decrease the applied force, while decreasing the porosity tends to increase the applied force.

[0666] Furthermore, considering good processability, good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power sources, as well as economic efficiency, the preferred mass per unit area is 48 mg / cm². 2 The following, or more preferably, is 30 mg / cm³ 2 The following, and more preferably, is 20 mg / cm³. 2 Furthermore, considering the comprehensive aspects of processability, adhesion, and economy, 15 mg / cm³ is preferred. 2 The following is a lower limit value, which is not specifically defined, for example, 1 mg / cm³. 2 about.

[0667] The mass per unit area mentioned above can be adjusted, for example, by appropriately adjusting the aperture ratio, electrode thickness, etc. (described later). More specifically, for the same thickness, increasing the aperture ratio tends to decrease the mass per unit area, while decreasing the aperture ratio tends to increase the mass per unit area.

[0668] The applied force can be measured using either method (i) or (ii), as detailed in the examples. The value obtained by method (i) (also referred to as “applied force (1)”) and the value obtained by method (ii) (also referred to as “applied force (2)”) may be the same or different, but both values ​​must be less than 1.5 N / mg·cm⁻¹. 2 .

[0669] [Method(i)]

[0670] A nickel plate (1.2 mm thick, 200 mm square) obtained by sandblasting alumina particle number 320, an ion exchange membrane (170 mm square, details of which are as described in the examples) with inorganic particles and binders coated on both sides of a membrane containing ion exchange groups of perfluorocarbon polymer, and an electrode sample (130 mm square) were sequentially laminated. The laminate was thoroughly impregnated with pure water, and excess water adhering to the surface of the laminate was removed to obtain the sample for measurement. It should be noted that the arithmetic mean surface roughness (Ra) of the sandblasted nickel plate is 0.5–0.8 μm. The specific calculation method for the arithmetic mean surface roughness (Ra) is as described in the examples.

[0671] Under conditions of 23±2℃ and 30±5% relative humidity, a tensile compression testing machine was used to raise only the electrode sample in the test sample at a vertical speed of 10 mm / min, and the load when the electrode sample rose 10 mm vertically was measured. This measurement was performed three times, and the average value was calculated.

[0672] Divide this average value by the area of ​​the overlap between the electrode sample and the ion exchange membrane, and the mass of the electrode sample in the overlap portion, to calculate the force applied per unit mass per unit area (1) (N / mg·cm). 2 ).

[0673] Regarding the force (1) applied per unit mass per unit area obtained by method (i), from the perspective of obtaining good processability and good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power sources, the applied force (1) is less than 1.5 N / mg·cm. 2 The preferred value is 1.2 N / mg·cm³. 2 The following, and more preferably, is 1.20 N / mg·cm 2 The following, and more preferably, is 1.1 N / mg·cm⁻¹ 2 The following, and more preferably, is 1.10 N / mg·cm⁻¹ 2 The following, and more preferably, is 1.0 N / mg·cm2 The following, and even more preferably, is 1.00 N / mg·cm⁻¹ 2 Below. Furthermore, from the perspective of further improving electrolysis performance, the applied force (1) is preferably greater than 0.005 N / (mg·cm). 2 ), more preferably 0.08 N / (mg·cm 2 ) or higher, and more preferably 0.1 N / (mg·cm 2 Furthermore, considering the ease of handling large sizes (e.g., 1.5m × 2.5m), 0.14 N / (mg·cm³) is even more preferable. 2 ) or higher, and even more preferably 0.2 N / (mg·cm 2 )above.

[0674] If the electrolysis electrode of this embodiment satisfies the applied force (1), it can be integrated with a membrane such as an ion exchange membrane or a microporous membrane, or a power supply (i.e., used as a laminate). Therefore, when updating the electrode, it is not necessary to replace the cathode and anode fixed to the electrolysis unit by welding or other methods, thus greatly improving work efficiency. In addition, by using the electrolysis electrode of this embodiment as a laminate integrated with an ion exchange membrane, a microporous membrane, or a power supply, the electrolysis performance can be the same as or even improved from that of a new product.

[0675] In the prior art, when shipping new electrolysis units, the electrodes fixed to the electrolysis unit are coated with a catalyst. However, the electrolysis electrodes of this embodiment can be used as electrodes simply by combining electrodes that have not been coated with a catalyst. Therefore, the manufacturing process for catalyst coating or the amount of catalyst can be significantly reduced or completely eliminated. The prior art electrodes, whose catalyst coating has been significantly reduced or completely eliminated, can be electrically connected to the electrolysis electrodes of this embodiment and function as a power source for flowing current.

[0676] [Method (ii)]

[0677] A nickel plate (1.2 mm thick, 200 mm square, the same nickel plate as in method (i) above) obtained by sandblasting alumina with particle number 320, and an electrode sample (130 mm square) were sequentially laminated. The laminate was thoroughly impregnated with pure water, and excess water adhering to the surface of the laminate was removed, thus obtaining the sample for testing. Under conditions of 23 ± 2 °C and 30 ± 5% relative humidity, a tensile compression testing machine was used to raise only the electrode sample in the vertical direction at a rate of 10 mm / min, and the load on the electrode sample when it rose 10 mm vertically was measured. This measurement was performed three times, and the average value was calculated.

[0678] Divide this average value by the area of ​​the overlap between the electrode sample and the nickel plate, and the mass of the electrode sample in the overlap area, to calculate the adhesive force per unit mass per unit area (2) (N / mg·cm). 2 ).

[0679] Regarding the force (2) applied per unit mass per unit area obtained by method (ii), considering the good processability and good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power sources, the applied force (2) is less than 1.5 N / mg·cm. 2 The preferred value is 1.2 N / mg·cm³. 2 The following, and more preferably, is 1.20 N / mg·cm 2 The following, and more preferably, is 1.1 N / mg·cm⁻¹ 2 The following, and more preferably, is 1.10 N / mg·cm⁻¹ 2 The following, and more preferably, is 1.0 N / mg·cm 2 The following, and even more preferably, is 1.00 N / mg·cm⁻¹ 2 Below. From the perspective of further improving electrolysis performance, the applied force (2) is preferably greater than 0.005 N / (mg·cm). 2 ), more preferably 0.08 N / (mg·cm 2 ) or higher, and more preferably 0.1 N / (mg·cm 2 Furthermore, considering the ease of handling large sizes (e.g., 1.5m × 2.5m), 0.14 N / (mg·cm³) is even more preferable. 2 )above.

[0680] If the electrolysis electrode of this embodiment satisfies the applied force (2), it can be stored and transported to the customer in a state of being wound on, for example, a tube made of polyvinyl chloride (in a roll or the like), making processing very easy. In addition, by attaching the electrolysis electrode of this embodiment to a deteriorated original electrode to form a laminate, the electrolysis performance can be made the same as or even better than that of a new product.

[0681] When the electrolysis electrode of this embodiment is an electrode with a wide elastic deformation region, from the perspective of obtaining better processability and better adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and power supplies without catalyst coating, the thickness of the electrolysis electrode is preferably 315 μm or less, more preferably 220 μm or less, further preferably 170 μm or less, even more preferably 150 μm or less, particularly preferably 145 μm or less, even more preferably 140 μm or less, even more preferably 138 μm or less, and even more preferably 135 μm or less. Good processability can be obtained if it is 135 μm or less. Furthermore, from the same perspective as above, it is preferably 130 μm or less, more preferably less than 130 μm, even more preferably 115 μm or less, and even more preferably 65 μm or less. The lower limit value is not particularly limited, but it is preferably 1 μm or more, and from a practical point of view, it is more preferably 5 μm or more, and even more preferably 20 μm or more. It should be noted that in this embodiment, "wide elastic deformation region" means that when the electrolysis electrode is wound into a coil, it is difficult for warping due to winding to occur after the coil is unwound. Furthermore, regarding the thickness of the electrolysis electrode, in the case of the catalyst layer described later, it refers to the thickness of the electrolysis electrode substrate and the catalyst layer combined together.

[0682] The electrolysis electrode of this embodiment preferably comprises an electrolysis electrode substrate and a catalyst layer. The thickness (gauge thickness) of the electrolysis electrode substrate is not particularly limited, but from the perspective of achieving good processability, good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes (power sources), and electrodes (power sources) without catalyst coating, the ability to be suitably rolled into rolls, good bending, and easy processing at large sizes (e.g., 1.5m × 2.5m), it is preferably 300 μm or less, more preferably 205 μm or less, further preferably 155 μm or less, even more preferably 135 μm or less, even more preferably 125 μm or less, even more preferably 120 μm or less, and even more preferably 100 μm or less. From the perspective of processability and economy, it is even more preferably 50 μm or less. The lower limit value is not particularly limited, for example, it is 1 μm, preferably 5 μm, and more preferably 15 μm.

[0683] In this embodiment, a liquid is preferably sandwiched between the ion exchange membrane or microporous membrane and the electrode, or between the deteriorated original electrode or the electrode without catalyst coating, or between the metal porous plate or metal plate (i.e., the power supply) and the electrolysis electrode. This liquid can be any substance that generates surface tension, such as water or an organic solvent. The greater the surface tension of the liquid, the greater the force exerted between the diaphragm and the electrolysis electrode, or between the metal porous plate or metal plate and the electrolysis electrode; therefore, a liquid with high surface tension is preferred. Examples of liquids include the following substances (the values ​​in parentheses are the surface tension of the liquid at 20°C).

[0684] Hexane (20.44 mN / m), acetone (23.30 mN / m), methanol (24.00 mN / m), ethanol (24.05 mN / m), ethylene glycol (50.21 mN / m), water (72.76 mN / m)

[0685] If the liquid has high surface tension, the diaphragm and the electrolysis electrode, or the porous metal plate or metal plate (power supply) and the electrolysis electrode, become integrated (forming a laminate), making electrode replacement easier. The amount of liquid between the diaphragm and the electrolysis electrode, or the porous metal plate or metal plate (power supply) and the electrolysis electrode, only needs to be such that they adhere to each other due to surface tension. As a result, the liquid volume is small, so even if it mixes into the electrolyte after being placed in the electrolysis unit of this laminate, it will not affect the electrolysis itself.

[0686] From a practical standpoint, liquids with a surface tension of 24 mN / m to 80 mN / m, such as ethanol, ethylene glycol, and water, are preferred. Water, or aqueous solutions containing caustic soda, potassium hydroxide, lithium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium carbonate, or potassium carbonate to form an alkaline solution, are particularly preferred. Alternatively, these liquids can be formulated with surfactants to adjust the surface tension. By including surfactants, the adhesion between the diaphragm and the electrolysis electrode, or between the porous metal plate or the metal plate (power supply) and the electrolysis electrode, changes, allowing for adjustments to the processability. There are no particular limitations on the surfactant used; either ionic or nonionic surfactants can be used.

[0687] The electrode used for electrolysis in this embodiment is not particularly limited. From the perspective of obtaining good processability and good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes (power supply bodies), and electrodes (power supply bodies) without catalyst coating, the proportion measured by the following method (2) is preferably 90% or more, more preferably 92% or more. Furthermore, from the perspective of facilitating processing at large sizes (e.g., 1.5m × 2.5m), it is even more preferably 95% or more. The upper limit is 100%.

[0688] [Method (2)]

[0689] The ion exchange membrane (170 mm²) and the electrode sample (130 mm²) were sequentially laminated. Under conditions of 23 ± 2 °C and 30 ± 5% relative humidity, the laminate was placed on the curved surface of a polyethylene tube (280 mm outer diameter) with the electrode sample on the outside. The laminate and the tube were thoroughly immersed in pure water to remove excess water adhering to the surface of the laminate and the tube. After 1 minute, the percentage of the area of ​​the ion exchange membrane (170 mm²) in close contact with the electrode sample was measured.

[0690] The electrode used for electrolysis in this embodiment is not particularly limited. From the perspective of obtaining good processability, good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes (power supply bodies), and electrodes (power supply bodies) without catalyst coating, and the ability to be suitably rolled into rolls and easily bent, the proportion measured by the following method (3) is preferably 75% or more, more preferably 80% or more. Furthermore, from the perspective of facilitating processing at large sizes (e.g., 1.5m × 2.5m), it is even more preferably 90% or more. The upper limit is 100%.

[0691] [Method (3)]

[0692] The ion exchange membrane (170 mm²) and the electrode sample (130 mm²) were sequentially laminated. Under conditions of 23 ± 2 °C and 30 ± 5% relative humidity, the laminate was placed on the curved surface of a polyethylene tube (145 mm outer diameter) with the electrode sample on the outside. The laminate and tube were thoroughly immersed in pure water to remove excess water adhering to their surfaces. After 1 minute, the percentage (%) of the area where the ion exchange membrane (170 mm²) and the electrode sample were in close contact was measured.

[0693] The electrode used for electrolysis in this embodiment is not particularly limited. From the perspectives of obtaining good processability, good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes (power supply bodies), and electrodes (power supply bodies) without catalyst coating, and preventing the retention of gases generated during electrolysis, a porous structure is preferred, and its porosity is 5 to 90% or less. More preferably, the porosity is 10 to 80% or less, and even more preferably 20 to 75%.

[0694] It should be noted that the porosity refers to the proportion of open portions per unit volume. The calculation method varies depending on whether the open portion is considered to be down to the sub-micron level or only to openings visible to the naked eye. In this embodiment, the volume V is calculated from the values ​​of the electrode gauge thickness, width, and length, and then the actual weight W is measured. The porosity A is then calculated using the following formula.

[0695] A = (1 - (W / (V×ρ))×100)

[0696] ρ is the density of the electrode material (g / cm³). 3 For example, in the case of nickel, it is 8.908 g / cm³. 3 In the case of titanium, it is 4.506 g / cm³. 3 The porosity can be adjusted appropriately using the following methods: for perforated metal, change the area of ​​the stamped metal per unit area; for sheet metal, change the values ​​of SW (short diameter), LW (long diameter), and feed; for mesh, change the wire diameter and mesh count of the metal fibers; for electroforming, change the pattern of the photoresist used; for nonwoven fabric, change the metal fiber diameter and fiber density; for foamed metal, change the mold used to form the voids; and so on.

[0697] Regarding the electrolysis electrode in this embodiment, from a processability perspective, the value measured by the following method (A) is preferably 40 mm or less, more preferably 29 mm or less, further preferably 10 mm or less, and even more preferably 6.5 mm or less. It should be noted that the specific measurement method is as described in the examples.

[0698] [Method (A)]

[0699] Under conditions of 23±2℃ and 30±5% relative humidity, the sample formed by the laminated ion exchange membrane and the above-mentioned electrolysis electrode was wound and fixed onto the curved surface of a vinyl chloride core material with an outer diameter of Φ32mm. After standing for 6 hours, the electrolysis electrode was separated and placed on a horizontal plate. The vertical heights L1 and L2 at both ends of the electrolysis electrode were measured, and their average value was taken as the measured value.

[0700] Regarding the electrolysis electrode in this embodiment, the electrode is 50mm × 50mm in size, and the conditions are: temperature 24°C, relative humidity 32%, piston speed 0.2cm / s, and air flow rate 0.4cc / cm. 2The aeration resistance (hereinafter referred to as "aeration resistance 1") under the condition of / s (hereinafter also referred to as "measurement condition 1") is preferably 24 kPa·s / m or less. High aeration resistance means that air is difficult to flow, indicating a high density state. Under this state, the products generated by electrolysis remain in the electrode, and the reaction matrix has difficulty diffusing into the electrode interior, thus tending to deteriorate electrolysis performance (voltage, etc.). Furthermore, there is a tendency for the concentration at the membrane surface to increase. Specifically, there is a tendency for the caustic concentration to increase at the cathode surface and the supply of brine to decrease at the anode surface. As a result, the products remain at a high concentration at the interface between the diaphragm and the electrode, thus tending to cause diaphragm damage, as well as voltage increase and membrane damage at the cathode surface and membrane damage at the anode surface. In this embodiment, to prevent these adverse conditions, it is preferable that the aeration resistance is 24 kPa·s / m or less. From the same perspective as above, it is more preferable to be less than 0.19 kPa·s / m, further preferably less than 0.15 kPa·s / m, and even more preferably less than 0.07 kPa·s / m.

[0701] It should be noted that in this embodiment, if the ventilation resistance is high enough, in the case of the cathode, the NaOH generated at the electrode will remain at the interface between the electrode and the diaphragm, tending to become highly concentrated; in the case of the anode, the brine supply will decrease, tending to become less concentrated. From the perspective of preventing potential damage to the diaphragm due to such retention, it is preferable to be less than 0.19 kPa·s / m, more preferably less than 0.15 kPa·s / m, and even more preferably less than 0.07 kPa·s / m.

[0702] On the other hand, when the ventilation resistance is low, the electrode area decreases, thus tending to decrease the electrolysis area and deteriorate the electrolysis performance (voltage, etc.). When the ventilation resistance is zero, since no electrode for electrolysis is provided, the power supply body functions as the electrode, tending to significantly deteriorate the electrolysis performance (voltage, etc.). From this perspective, there is no particular limitation on the preferred lower limit value of the ventilation resistance 1, but it is preferably greater than 0 kPa·s / m, more preferably 0.0001 kPa·s / m or more, and even more preferably 0.001 kPa·s / m or more.

[0703] It should be noted that, regarding the ventilation resistance 1, from the perspective of its measurement method, sufficient measurement accuracy is sometimes not obtainable when it is below 0.07 kPa·s / m. Therefore, for electrolytic electrodes with a ventilation resistance 1 of 0.07 kPa·s / m or less, the ventilation resistance (hereinafter referred to as "ventilation resistance 2") can also be evaluated using the following measurement method (hereinafter also referred to as "measurement condition 2"). That is, ventilation resistance 2 is defined as follows: the electrolytic electrode is 50 mm × 50 mm in size, at a temperature of 24 °C, a relative humidity of 32%, a piston speed of 2 cm / s, and a ventilation rate of 4 cc / cm³. 2 Ventilation resistance at a rate of / s.

[0704] The specific methods for measuring ventilation resistances 1 and 2 are as described in the examples.

[0705] The aforementioned ventilation resistances 1 and 2 can be adjusted to the range described below, for example, by appropriately adjusting the aperture ratio, electrode thickness, etc. More specifically, for example, if the thickness is the same, increasing the aperture ratio tends to decrease ventilation resistances 1 and 2, while decreasing the aperture ratio tends to increase ventilation resistances 1 and 2.

[0706] Regarding the electrolysis electrode of this embodiment, as described above, for the diaphragm or the power supply, the force applied per unit mass / unit area of ​​the electrolysis electrode is less than 1.5 N / mg·cm. 2 In this way, the electrolysis electrode of this embodiment contacts the diaphragm or power supply (e.g., the original anode or cathode in the electrolytic cell) with a moderate adhesive force, thereby forming a laminate with the diaphragm or power supply. That is, there is no need to firmly bond the diaphragm or power supply to the electrolysis electrode using complicated methods such as hot pressing. For example, even relatively weak forces such as the surface tension of water that may be contained in the diaphragm, such as ion exchange membranes or microporous membranes, can be used to bond and form a laminate. Therefore, laminates of any scale can be easily formed. Furthermore, such laminates exhibit excellent electrolytic performance. Therefore, the laminate of this embodiment is suitable for electrolysis applications, and is particularly preferred for applications involving components of electrolytic cells or the replacement of such components.

[0707] The following describes one embodiment of the electrode for electrolysis.

[0708] The electrolysis electrode of this embodiment preferably comprises an electrolysis electrode substrate and a catalyst layer. The catalyst layer, as described below, can consist of multiple layers or a single-layer structure.

[0709] like Figure 22As shown, the electrolysis electrode 100 of this embodiment includes an electrolysis electrode substrate 10 and a pair of first layers 20 covering both surfaces of the electrolysis electrode substrate 10. The first layer 20 preferably covers the entire electrolysis electrode substrate 10. This easily improves the catalytic activity and durability of the electrolysis electrode. It should be noted that the first layer 20 may also be deposited only on one surface of the electrolysis electrode substrate 10.

[0710] In addition, such as Figure 22 As shown, the surface of the first layer 20 can be covered by the second layer 30. Preferably, the second layer 30 covers the entire first layer 20. Alternatively, the second layer 30 may be deposited on only one surface of the first layer 20.

[0711] (Electrode substrate for electrolysis)

[0712] The electrode substrate 10 for electrolysis is not particularly limited, and can be made of materials such as nickel, nickel alloy, stainless steel, or valve metals such as titanium. It preferably contains at least one element selected from nickel (Ni) and titanium (Ti).

[0713] When stainless steel is used in high-concentration alkaline aqueous solutions, considering the leaching of iron and chromium, and the fact that the conductivity of stainless steel is about 1 / 10 that of nickel, a substrate containing nickel (Ni) is preferred as the electrode substrate for electrolysis.

[0714] In addition, when the electrode substrate 10 for electrolysis is used in a near-saturated high-concentration brine solution or in a chlorine-generating atmosphere, the material is preferably titanium, which has high corrosion resistance.

[0715] The shape of the electrode substrate 10 for electrolysis is not particularly limited, and an appropriate shape can be selected according to the purpose. As a shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or a so-called woven mesh made by braiding metal wires. Among these, perforated metal or metal mesh is preferred. It should be noted that electroforming refers to a technique for producing metal thin films with precise patterns by combining photolithography and electroplating. It is a method of obtaining a metal thin film by forming a pattern on a substrate using a photoresist and then electroplating the areas not protected by the photoresist.

[0716] Regarding the shape of the electrode substrate for electrolysis, appropriate specifications are available depending on the distance between the anode and cathode in the electrolytic cell. Although there are no particular limitations, when the anode and cathode have a limited distance, metal mesh or perforated metal shapes can be used. In the case of a so-called zero-gap electrolytic cell where the ion exchange membrane and the electrode are in contact, woven mesh made of fine threads, metal wire mesh, foamed metal, metal nonwoven fabric, metal mesh, perforated metal, and porous metal foil can be used.

[0717] Examples of electrode substrates 10 for electrolysis include porous metal foil, metal wire mesh, nonwoven metal fabric, perforated metal, metal mesh, or foamed metal.

[0718] As a sheet material to be processed into perforated metal or metal mesh, rolled sheet material or electrolytic foil is preferred. As a post-processing step, the electrolytic foil is preferably further plated with the same elements as the base material to form an uneven surface on one or both sides.

[0719] Furthermore, regarding the thickness of the electrode substrate 10 for electrolysis, as described above, it is preferably 300 μm or less, more preferably 205 μm or less, even more preferably 155 μm or less, further preferably 135 μm or less, even more preferably 125 μm or less, even more preferably 120 μm or less, and even more preferably 100 μm or less. From the perspective of processability and economy, it is even more preferably 50 μm or less. The lower limit is not particularly limited, for example, it is 1 μm, preferably 5 μm, and more preferably 15 μm.

[0720] In the electrode substrate for electrolysis, it is preferable to anneal the electrode substrate in an oxidizing atmosphere, thereby mitigating residual stress from processing. Furthermore, to improve adhesion to the catalyst layer coated on the surface of the electrode substrate, it is preferable to create an uneven surface using materials such as steel grating or alumina powder, followed by acid treatment to increase the surface area. Alternatively, it is preferable to increase the surface area by plating with the same elements as the substrate.

[0721] For the electrode substrate 10 for electrolysis, in order to ensure close adhesion between the first layer 20 and the surface of the electrode substrate 10, it is preferable to perform a treatment that increases the surface area. Examples of treatments that increase the surface area include: sandblasting using chopped wire, steel grating, alumina grating, etc.; acid treatment using sulfuric acid or hydrochloric acid; plating using the same elements as the substrate; and so on. The arithmetic mean surface roughness (Ra) of the substrate surface is not particularly limited, but is preferably 0.05 μm to 50 μm, more preferably 0.1 to 10 μm, and even more preferably 0.1 to 8 μm.

[0722] Next, the case of using the electrolysis electrode of this embodiment as the anode for salt electrolysis will be described.

[0723] (First layer)

[0724] Figure 22In this catalyst layer, the first layer 20 comprises at least one oxide selected from ruthenium oxide, iridium oxide, and titanium oxide. Examples of ruthenium oxides include RuO2. Examples of iridium oxides include IrO2. Examples of titanium oxides include TiO2. The first layer 20 preferably comprises both ruthenium oxide and titanium oxide, or both ruthenium oxide, iridium oxide, and titanium oxide. This makes the first layer 20 a more stable layer, further improving its adhesion to the second layer 30.

[0725] When the first layer 20 contains both ruthenium oxide and titanium oxide, the amount of titanium oxide in the first layer 20 is preferably 1 to 9 moles, more preferably 1 to 4 moles, relative to 1 mole of ruthenium oxide. By maintaining the composition ratio of the two oxides within this range, the electrolytic electrode 100 exhibits excellent durability.

[0726] When the first layer 20 contains ruthenium oxide, iridium oxide, and titanium oxide, the amount of iridium oxide in the first layer 20 is preferably 0.2 to 3 moles, more preferably 0.3 to 2.5 moles, relative to 1 mole of ruthenium oxide. Similarly, the amount of titanium oxide in the first layer 20 is preferably 0.3 to 8 moles, more preferably 1 to 7 moles, relative to 1 mole of ruthenium oxide. By maintaining the composition ratio of the three oxides within this range, the electrolytic electrode 100 exhibits excellent durability.

[0727] When the first layer 20 contains at least two oxides selected from ruthenium oxide, iridium oxide, and titanium oxide, these oxides preferably form a solid solution. By forming an oxide solid solution, the electrolytic electrode 100 exhibits excellent durability.

[0728] In addition to the above-mentioned components, substances with various compositions can be used as long as they contain at least one oxide selected from ruthenium oxide, iridium oxide, and titanium oxide. For example, an oxide coating containing ruthenium, iridium, tantalum, niobium, titanium, tin, cobalt, manganese, platinum, etc., known as DSA (registered trademark) can also be used as the first layer 20.

[0729] The first layer 20 does not need to be a single layer, and may contain multiple layers. For example, the first layer 20 may contain a layer containing three oxides and a layer containing two oxides. The thickness of the first layer 20 is preferably 0.05 to 10 μm, more preferably 0.1 to 8 μm.

[0730] (Second layer)

[0731] The second layer 30 preferably contains ruthenium and titanium. This further reduces the chlorine overvoltage immediately after electrolysis.

[0732] The second layer 30 preferably comprises palladium oxide, a solid solution of palladium oxide and platinum, or an alloy of palladium and platinum. This further reduces the chlorine overvoltage immediately after electrolysis.

[0733] When the second layer is 30 μm thick, the period during which electrolytic performance can be maintained will be longer, but from an economic point of view, a thickness of 0.05 to 3 μm is preferred.

[0734] Next, the case of using the electrolysis electrode of this embodiment as the cathode for salt electrolysis will be described.

[0735] (First layer)

[0736] The composition of the first layer 20, which serves as the catalyst layer, can include metals such as C, Si, P, S, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, as well as their oxides or hydroxides.

[0737] It may contain at least one of platinum group metals, platinum group metal oxides, platinum group metal hydroxides, or alloys containing platinum group metals, or it may not contain any of them.

[0738] In cases where at least one of platinum group metals, platinum group metal oxides, platinum group metal hydroxides, or alloys containing platinum group metals is included, the platinum group metals, platinum group metal oxides, platinum group metal hydroxides, or alloys containing platinum group metals preferably include at least one platinum group metal selected from platinum, palladium, rhodium, ruthenium, and iridium.

[0739] As a platinum group metal, it preferably contains platinum.

[0740] As a platinum group metal oxide, it preferably contains ruthenium oxide.

[0741] As a platinum group metal hydroxide, it is preferred to include ruthenium hydroxide.

[0742] As a platinum group metal alloy, an alloy containing platinum, nickel, iron, and cobalt is preferred.

[0743] Furthermore, if necessary, oxides or hydroxides containing lanthanides are preferably used as the second component. As a result, the electrolytic electrode 100 exhibits excellent durability.

[0744] As an oxide or hydroxide of a lanthanide element, it preferably contains at least one selected from lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, and dysprosium.

[0745] Furthermore, if necessary, oxides or hydroxides containing transition metals are preferably used as the third component.

[0746] By adding a third component, the electrolytic electrode 100 exhibits superior durability and can reduce the electrolysis voltage.

[0747] Examples of preferred combinations include those consisting solely of ruthenium, ruthenium + nickel, ruthenium + cerium, ruthenium + lanthanum, ruthenium + lanthanum + platinum, ruthenium + lanthanum + palladium, ruthenium + praseodymium, ruthenium + praseodymium + platinum, ruthenium + praseodymium + platinum + palladium, ruthenium + neodymium, ruthenium + neodymium + platinum, ruthenium + neodymium + manganese, ruthenium + neodymium + iron, ruthenium + neodymium + cobalt, ruthenium + neodymium + zinc, ruthenium + neodymium + gallium, ruthenium + neodymium + sulfur, ruthenium + neodymium + lead, ruthenium + neodymium + nickel, and ruthenium + Neodymium + Copper, Ruthenium + Samarium, Ruthenium + Samarium + Manganese, Ruthenium + Samarium + Iron, Ruthenium + Samarium + Cobalt, Ruthenium + Samarium + Zinc, Ruthenium + Samarium + Gallium, Ruthenium + Samarium + Sulfur, Ruthenium + Samarium + Lead, Ruthenium + Samarium + Nickel, Platinum + Cerium, Platinum + Palladium + Cerium, Platinum + Palladium + Lanthanum + Cerium, Platinum + Iridium, Platinum + Palladium, Platinum + Iridium + Palladium, Platinum + Nickel + Palladium, Platinum + Nickel + Ruthenium, Platinum and Nickel alloys, Platinum and Cobalt alloys, Platinum and Iron alloys, etc.

[0748] In the absence of platinum group metals, platinum group metal oxides, platinum group metal hydroxides, or alloys containing platinum group metals, the main component of the catalyst is preferably nickel.

[0749] Preferably, it contains at least one of nickel metal, oxide, and hydroxide.

[0750] Transition metals may also be added as a second component. Preferably, the added second component includes at least one element selected from titanium, tin, molybdenum, cobalt, manganese, iron, sulfur, zinc, copper, and carbon.

[0751] Preferred combinations include nickel + tin, nickel + titanium, nickel + molybdenum, and nickel + cobalt.

[0752] If necessary, an intermediate layer can be provided between the first layer 20 and the electrode substrate 10 for electrolysis. By providing an intermediate layer, the durability of the electrode 100 for electrolysis can be improved.

[0753] As an intermediate layer, it is preferable to have an affinity for both the first layer 20 and the electrolytic electrode substrate 10. Nickel oxide, platinum group metals, platinum group metal oxides, and platinum group metal hydroxides are preferred as the intermediate layer. The intermediate layer can be formed by coating a solution containing the components forming the intermediate layer and then firing it, or by heat-treating the substrate in an air atmosphere at a temperature of 300–600°C to form a surface oxide layer. Alternatively, it can be formed using known methods such as thermal spraying or ion plating.

[0754] (Second layer)

[0755] The composition of the first layer 30, which serves as the catalyst layer, can include metals such as C, Si, P, S, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, as well as their oxides or hydroxides.

[0756] It may contain at least one of platinum group metals, platinum group metal oxides, platinum group metal hydroxides, or alloys containing platinum group metals, or it may not contain any. Examples of preferred combinations of elements included in the second layer include combinations mentioned in the first layer. The combination of the first and second layers may be a combination with the same composition but different composition ratios, or it may be a combination with different compositions.

[0757] The thickness of the catalyst layer, including the intermediate layer, is preferably 0.01 μm to 20 μm. If it is 0.01 μm or more, it can fully function as a catalyst. If it is 20 μm or less, there is less detachment from the substrate, resulting in a robust catalyst layer. More preferably, it is 0.05 μm to 15 μm. More preferably, it is 0.1 μm to 10 μm. Even more preferably, it is 0.2 μm to 8 μm.

[0758] The thickness of the electrode for electrolysis, i.e., the total thickness of the electrode substrate and the catalyst layer, is preferably 315 μm or less, more preferably 220 μm or less, further preferably 170 μm or less, even more preferably 150 μm or less, particularly preferably 145 μm or less, even more preferably 140 μm or less, even more preferably 138 μm or less, and even more preferably 135 μm or less, from the perspective of processability. Good processability can be obtained when the thickness is 135 μm or less. Furthermore, from the same perspective as above, it is preferably 130 μm or less, more preferably less than 130 μm, even more preferably 115 μm or less, and even more preferably 65 μm or less. The lower limit is not particularly limited, but it is preferably 1 μm or more, and from a practical perspective, it is more preferably 5 μm or more, and even more preferably 20 μm or more. It should be noted that the electrode thickness can be determined by measuring it with a digital thickness gauge (Mitutoyo Co., Ltd., minimum display 0.001 mm). The thickness of the electrode substrate for electrolysis can be measured in the same manner as the thickness of the electrode for electrolysis. The thickness of the catalyst layer can be determined by subtracting the thickness of the electrode substrate for electrolysis from the thickness of the electrode for electrolysis.

[0759] (Manufacturing method of electrodes for electrolysis)

[0760] Next, one embodiment of the method for manufacturing the electrolysis electrode 100 will be described in detail.

[0761] In this embodiment, an electrolytic electrode 100 is manufactured by forming a first layer 20, preferably a second layer 30, on an electrolytic electrode substrate through methods such as firing (thermal decomposition) of a coating film under an oxygen atmosphere, or ion plating, plating, or thermal spraying. This manufacturing method of this embodiment achieves high productivity of the electrolytic electrode 100. Specifically, a catalyst layer is formed on the electrolytic electrode substrate through a coating process of applying a coating liquid containing a catalyst, a drying process of drying the coating liquid, and a thermal decomposition process of thermal decomposition. Here, thermal decomposition refers to heating a metal salt as a precursor and decomposing it into a metal or metal oxide and a gaseous substance. The decomposition products vary depending on the type of metal used, the type of salt, and the atmosphere in which thermal decomposition is carried out, but many metals tend to easily form oxides under an oxidizing atmosphere. In the industrial manufacturing process of electrodes, thermal decomposition is usually carried out in air, and in most cases, metal oxides or metal hydroxides are formed.

[0762] (Formation of the first layer of the anode)

[0763] (Coating process)

[0764] The first layer 20 is obtained by coating an electrode substrate containing a solution of at least one metal salt selected from ruthenium, iridium, and titanium (a first coating solution) onto the substrate, followed by thermal decomposition (firing) in the presence of oxygen. The content of ruthenium, iridium, and titanium in the first coating solution is approximately equal to that in the first layer 20.

[0765] The metal salt can be any of the following: chloride salt, nitrate salt, sulfate salt, metal alkoxide, or other salt. The solvent for the first coating solution can be selected according to the type of metal salt, and can be water or alcohols such as butanol. Water or a mixture of water and alcohol is preferred as the solvent. The total metal concentration in the first coating solution containing the dissolved metal salt is not particularly limited, but a range of 10–150 g / L is preferred, taking into account the thickness of the coating film formed in a single coating application.

[0766] Methods for applying the first coating liquid to the electrolytic electrode substrate 10 include immersion methods (immersing the electrolytic electrode substrate 10 in the first coating liquid), brush coating methods (coating the first coating liquid with brush bristles), roller coating methods (using a sponge-like roller impregnated with the first coating liquid), and electrostatic coating methods (spraying the electrolytic electrode substrate 10 and the first coating liquid with opposite charges). Among these, roller coating or electrostatic coating methods, which have excellent industrial productivity, are preferred.

[0767] (Drying process, thermal decomposition process)

[0768] After applying a first coating solution to the electrode substrate 100 for electrolysis, it is dried at a temperature of 10–90°C and then thermally decomposed in a firing furnace heated to 350–650°C. During drying and thermal decomposition, pre-firing can be performed at 100–350°C as needed. The drying, pre-firing, and thermal decomposition temperatures can be appropriately selected based on the composition or solvent type of the first coating solution. A longer duration for each thermal decomposition is preferred; from the perspective of electrode productivity, 3–60 minutes is preferred, and 5–20 minutes is more preferred.

[0769] By repeating the above-described cycle of coating, drying, and thermal decomposition, the coating (first layer 20) is formed to a specified thickness. After forming the first layer 20, further heating followed by prolonged firing as needed can further improve the stability of the first layer 20.

[0770] (The formation of the second layer)

[0771] The second layer 30 is formed as needed, for example, by coating a solution containing palladium and platinum compounds or a solution containing ruthenium and titanium compounds (the second coating solution) onto the first layer 20 and then thermally decomposing it in the presence of oxygen.

[0772] (Formation of the first layer of the cathode using thermal decomposition)

[0773] (Coating process)

[0774] The first layer 20 is obtained by coating a solution containing various combinations of metal salts (first coating solution) onto an electrolytic electrode substrate, followed by thermal decomposition (firing) in the presence of oxygen. The metal content in the first coating solution is approximately equal to that in the first layer 20.

[0775] The metal salt can be any of the following: chloride salt, nitrate salt, sulfate salt, metal alkoxide, or other salt. The solvent for the first coating solution can be selected according to the type of metal salt, and can be water or alcohols such as butanol. Water or a mixture of water and alcohol is preferred as the solvent. The total metal concentration in the first coating solution containing the dissolved metal salt is not particularly limited, but a range of 10–150 g / L is preferred, taking into account the thickness of the coating film formed in a single coating application.

[0776] Methods for applying the first coating liquid to the electrolytic electrode substrate 10 include immersion methods (immersing the electrolytic electrode substrate 10 in the first coating liquid), brush coating methods (coating the first coating liquid with brush bristles), roller coating methods (using a sponge-like roller impregnated with the first coating liquid), and electrostatic coating methods (spraying the electrolytic electrode substrate 10 and the first coating liquid with opposite charges). Among these, roller coating or electrostatic coating methods, which have excellent industrial productivity, are preferred.

[0777] (Drying process, thermal decomposition process)

[0778] After the first coating solution is applied to the electrode substrate 10 for electrolysis, it is dried at a temperature of 10–90°C and then thermally decomposed in a firing furnace heated to 350–650°C. During drying and thermal decomposition, pre-firing can be performed at 100–350°C as needed. The drying, pre-firing, and thermal decomposition temperatures can be appropriately selected according to the composition or solvent type of the first coating solution. A longer thermal decomposition time is preferred; from the perspective of electrode productivity, 3–60 minutes is preferred, and 5–20 minutes is more preferred.

[0779] By repeating the above-described cycle of coating, drying, and thermal decomposition, the coating (first layer 20) is formed to a specified thickness. After forming the first layer 20, further heating followed by prolonged firing as needed can further improve the stability of the first layer 20.

[0780] (Formation of the intermediate layer)

[0781] The intermediate layer is formed as needed, for example, by applying a solution containing a palladium or platinum compound (a second coating solution) to the substrate and then thermally decomposing it in the presence of oxygen. Alternatively, the solution can be omitted, and the substrate can be heated to form a nickel oxide intermediate layer on the substrate surface.

[0782] (The formation of the first layer of the cathode using ion plating)

[0783] The first layer 20 can also be formed using ion plating.

[0784] As an example, a method can be described where a substrate is fixed within a chamber and an electron beam is irradiated onto a ruthenium target. Evaporated ruthenium particles become positively charged in the plasma within the chamber and accumulate on a negatively charged substrate. The plasma atmosphere is argon and oxygen, and ruthenium is deposited on the substrate in the form of ruthenium oxide.

[0785] (Utilizing the formation of the first layer of the plated cathode)

[0786] The first layer 20 can also be formed using a plating method.

[0787] As an example, if a substrate is used as the cathode and electroplating is performed in an electrolyte containing nickel and tin, an alloy coating of nickel and tin can be formed.

[0788] (Formation of the first layer of the cathode using thermal spraying)

[0789] The first layer 20 can also be formed using thermal spraying.

[0790] As an example, nickel oxide particles are plasma-sprayed onto a substrate, thereby forming a catalyst layer composed of a mixture of metallic nickel and nickel oxide.

[0791] The electrolysis electrode of this embodiment can be integrated with membranes such as ion exchange membranes or microporous membranes. Therefore, it can be used as a membrane-integrated electrode, eliminating the need for cathode and anode replacement operations when updating electrodes, thus significantly improving operational efficiency.

[0792] Furthermore, by integrating electrodes with membranes such as ion exchange membranes or microporous membranes, the electrolysis performance can be made the same as or even improved compared to that of a new product.

[0793] The following is a detailed description of ion exchange membranes.

[0794] Ion exchange membrane

[0795] The ion exchange membrane comprises: a membrane substrate containing a hydrocarbon polymer or a fluorinated polymer having ion exchange groups; and a coating layer disposed on at least one surface of the membrane substrate. Furthermore, the coating layer comprises inorganic particles and a binder, and the specific surface area of ​​the coating layer is 0.1–10 m². 2 / g. For ion exchange membranes with this structure, the gas generated during electrolysis has little impact on electrolysis performance, and can exhibit stable electrolysis performance.

[0796] The aforementioned membrane with introduced ion-exchange groups refers to a membrane possessing ion-exchange groups derived from sulfonium (-SO3). - The group represented (hereinafter also referred to as "sulfonic acid group") is a sulfonic acid layer, and has an ion exchange group (-CO2) from a carboxyl group. - A film of any one of the carboxylic acid layers (represented by the group, hereinafter also referred to as "carboxylic acid group"). From the perspective of strength and dimensional stability, it is preferable to further have a reinforcing core material.

[0797] Inorganic particles and adhesives are described in detail below in the section on coating.

[0798] Figure 23 This is a cross-sectional schematic diagram illustrating one embodiment of an ion exchange membrane. The ion exchange membrane 1 has: a membrane body 10 comprising a hydrocarbon polymer or a fluorinated polymer having ion exchange groups; and coating layers 11a and 11b formed on both sides of the membrane body 10.

[0799] In the ion exchange membrane 1, the membrane body 10 has ion exchange groups (-SO3) derived from sulfonyl groups. - The group represented herein (hereinafter also referred to as "sulfonic acid group") is a sulfonic acid layer 3, and has an ion exchange group (-CO2) derived from a carboxyl group. - The carboxylic acid layer 2 (represented by the group, hereinafter also referred to as "carboxylic acid group") is reinforced in strength and dimensional stability by the reinforcing core material 4. The ion exchange membrane 1, having a sulfonic acid layer 3 and a carboxylic acid layer 2, is therefore suitable for use as a cation exchange membrane.

[0800] It should be noted that ion exchange membranes can also contain only either a sulfonic acid layer or a carboxylic acid layer. Furthermore, ion exchange membranes do not necessarily require reinforcement with a core material, and the configuration of the core material is not limited to a specific configuration. Figure 23 Examples.

[0801] (Membrane body)

[0802] First, the membrane body 10 constituting the ion exchange membrane 1 will be described.

[0803] The membrane body 10 has the function of selectively permeating cations. It can contain hydrocarbon polymers or fluorinated polymers with ion exchange groups. There are no special limitations on its composition or materials. Suitable composition or materials can be selected appropriately.

[0804] The hydrocarbon polymer or fluorinated polymer with ion exchange groups in the membrane body 10 can be obtained, for example, from a hydrocarbon polymer or fluorinated polymer having an ion exchange group precursor that can be converted into an ion exchange group through hydrolysis or the like. Specifically, for example, a polymer whose main chain is composed of fluorinated hydrocarbons, has groups (ion exchange group precursors) that can be converted into ion exchange groups through hydrolysis or the like as side chains, and is capable of melt processing (hereinafter referred to as "fluorinated polymer (a)" as appropriate) can be used to prepare the precursor of the membrane body 10, and then the ion exchange group precursor can be converted into ion exchange groups to obtain the membrane body 10.

[0805] Fluorinated polymers (a) can be manufactured, for example, by copolymerizing at least one monomer selected from Group 1 below with at least one monomer selected from Group 2 and / or Group 3 below. Alternatively, they can be manufactured by homopolymerization of a monomer selected from any one of Group 1, Group 2 and Group 3 below.

[0806] Examples of monomers in Group 1 include fluorinated vinyl compounds. Examples of fluorinated vinyl compounds include ethylene fluoride, tetrafluoroethylene, hexafluoropropylene, vinylidene fluoride, trifluoroethylene, trifluorochloroethylene, and perfluoroalkyl vinyl ethers. In particular, when using an ion exchange membrane as a membrane for alkaline electrolysis, the fluorinated vinyl compound is preferably a perfluorinated monomer, and more preferably a perfluorinated monomer selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, and perfluoroalkyl vinyl ethers.

[0807] As monomers in Group 2, examples include vinyl compounds having functional groups capable of being converted into carboxylic acid ion exchange groups (carboxylic acid groups). For example, CF2=CF(OCF2CYF) is a vinyl compound having functional groups capable of being converted into carboxylic acid groups. s -O(CZF) t-COOR indicates monomers, etc. (here, s represents an integer from 0 to 2, t represents an integer from 1 to 12, Y and Z each independently represent F or CF3, and R represents a lower alkyl group. Lower alkyl groups are, for example, alkyl groups with 1 to 3 carbon atoms.)

[0808] Of these, CF2 = CF(OCF2CYF) is preferred. n -O(CF2) m -COOR represents the compound. Here, n represents an integer from 0 to 2, m represents an integer from 1 to 4, Y represents F or CF3, and R represents CH3, C2H5, or C3H7.

[0809] It should be noted that when using an ion exchange membrane as a cation exchange membrane for alkaline electrolysis, it is preferable to use at least a perfluorinated compound as a monomer. However, since the alkyl group of the ester group (refer to R above) is removed from the polymer during hydrolysis, the alkyl group (R) may not be a perfluorinated alkyl group in which all hydrogen atoms are replaced by fluorine atoms.

[0810] As for the monomers in the second group, among the above, the monomers indicated below are more preferred.

[0811] CF2=CFOCF2-CF(CF3)OCF2COOCH3,

[0812] CF2=CFOCF2CF(CF3)O(CF2)2COOCH3,

[0813] CF2=CF[OCF2-CF(CF3)]2O(CF2)2COOCH3,

[0814] CF2=CFOCF2CF(CF3)O(CF2)3COOCH3,

[0815] CF2=CFO(CF2)2COOCH3、

[0816] CF2=CFO(CF2)3COOCH3.

[0817] As monomers in Group 3, examples include vinyl compounds having functional groups capable of being converted to sulfonate ion-exchange groups (sulfonic acid groups). As vinyl compounds having functional groups capable of being converted to sulfonic acid groups, monomers represented by CF2=CFO-X-CF2-SO2F (where X represents a perfluoroalkylene group) are preferred. Specific examples include monomers represented below.

[0818] CF2 = CFOCF2CF2SO2F,

[0819] CF2=CFOCF2CF(CF3)OCF2CF2SO2F,

[0820] CF2=CFOCF2CF(CF3)OCF2CF2CF2SO2F,

[0821] CF2=CF(CF2)2SO2F、

[0822] CF2=CFO[CF2CF(CF3)O]2CF2CF2SO2F,

[0823] CF2=CFOCF2CF(CF2OCF3)OCF2CF2SO2F.

[0824] Among these, CF2=CFOCF2CF(CF3)OCF2CF2CF2SO2F and CF2=CFOCF2CF(CF3)OCF2CF2SO2F are preferred.

[0825] The copolymers obtained from these monomers can be manufactured using polymerization methods developed for homopolymerization and copolymerization of fluorinated ethylene, and especially the general polymerization methods used for tetrafluoroethylene. For example, in a non-aqueous method, inert solvents such as perfluorocarbons and chlorofluorocarbons can be used, and polymerization can be carried out in the presence of free radical polymerization initiators such as perfluorocarbon peroxides or azo compounds, at temperatures of 0–200°C and pressures of 0.1–20 MPa.

[0826] In the above copolymerization, the types and proportions of the monomers are not particularly limited, and are selected based on the type and amount of functional groups desired to be imparted to the resulting fluorinated polymer. For example, in the case of forming a fluorinated polymer containing only carboxylic acid groups, at least one monomer from each of the above groups 1 and 2 can be copolymerized. Similarly, in the case of forming a fluorinated polymer containing only sulfonic acid groups, at least one monomer from each of the above groups 1 and 3 can be copolymerized. Furthermore, in the case of forming a fluorinated polymer having both carboxylic acid and sulfonic acid groups, at least one monomer from each of the above groups 1, 2, and 3 can be copolymerized. In this case, copolymers composed of groups 1 and 2 and copolymers composed of groups 1 and 3 are polymerized separately, and then mixed to obtain the target fluorinated polymer. Furthermore, the mixing ratio of each monomer is not particularly limited; to increase the amount of functional groups per unit polymer, simply increase the proportion of monomers selected from groups 2 and 3.

[0827] The total ion exchange capacity of the fluorinated copolymer is not particularly limited, but is preferably 0.5 to 2.0 mg equivalents / g, more preferably 0.6 to 1.5 mg equivalents / g. Here, the total ion exchange capacity refers to the equivalent of exchange groups per unit weight of the dried resin, which can be determined by neutralization titration or the like.

[0828] In the membrane body 10 of the ion exchange membrane 1, a sulfonic acid layer 3 comprising a fluorinated polymer having sulfonic acid groups and a carboxylic acid layer 2 comprising a fluorinated polymer having carboxylic acid groups are laminated. By forming the membrane body 10 with this layered structure, the selective permeability of cations such as sodium ions can be further improved.

[0829] When the ion exchange membrane 1 is placed in an electrolyzer, it is usually arranged such that the sulfonic acid layer 3 is located on the anode side of the electrolyzer and the carboxylic acid layer 2 is located on the cathode side of the electrolyzer.

[0830] The sulfonic acid layer 3 is preferably made of a material with low electrical resistance, and from the perspective of film strength, it is preferable that the film thickness is thicker than that of the carboxylic acid layer 2. The film thickness of the sulfonic acid layer 3 is preferably 2 to 25 times that of the carboxylic acid layer 2, and more preferably 3 to 15 times.

[0831] The carboxylic acid layer 2 preferably exhibits high anion rejection capacity even when the membrane is thin. Anion rejection capacity, as referred to here, means the property of preventing anions from penetrating or permeating into the ion exchange membrane 1. To improve anion rejection capacity, it is effective to configure a carboxylic acid layer or similar layer with a smaller ion exchange capacity compared to the sulfonic acid layer.

[0832] As a fluorinated polymer for sulfonic acid layer 3, for example, a polymer obtained by using CF2=CFOCF2CF(CF3)OCF2CF2SO2F as a monomer of group 3 is suitable.

[0833] As a fluorinated polymer for carboxylic acid layer 2, for example, a polymer obtained by using CF2=CFOCF2CF(CF2)O(CF2)2COOCH3 as a monomer of group 2 is suitable.

[0834] (Coating layer)

[0835] The ion exchange membrane has a coating layer on at least one surface of the membrane substrate. Additionally, as... Figure 23 As shown, in the ion exchange membrane 1, coating layers 11a and 11b are formed on both sides of the membrane body 10, respectively.

[0836] The coating layer contains inorganic particles and adhesives.

[0837] The average particle size of the inorganic particles is more preferably 0.90 μm or more. When the average particle size of the inorganic particles is 0.90 μm or more, not only is the adhesion to gas improved, but the durability against impurities is also greatly enhanced. That is, by increasing the average particle size of the inorganic particles while simultaneously satisfying the above-mentioned specific surface area value, a particularly significant effect can be obtained. Due to satisfying this average particle size and specific surface area, irregularly shaped inorganic particles are preferred. Inorganic particles obtained by melting or by pulverizing raw ore can be used. Preferably, inorganic particles obtained by pulverizing raw ore can be used appropriately.

[0838] Furthermore, the average particle size of the inorganic particles can be 2 μm or less. If the average particle size of the inorganic particles is 2 μm or less, damage to the membrane due to the inorganic particles can be prevented. More preferably, the average particle size of the inorganic particles is 0.90 to 1.2 μm.

[0839] Here, the average particle size can be measured using a particle size analyzer ("SALD2200" Shimadzu Corporation).

[0840] The inorganic particles are preferably irregularly shaped. This further improves their tolerance to impurities. Furthermore, the particle size distribution of the inorganic particles is preferably broad.

[0841] The inorganic particles preferably comprise at least one inorganic material selected from the group consisting of oxides of elements in Group IV of the periodic table, nitrides of elements in Group IV of the periodic table, and carbides of elements in Group IV of the periodic table. From a durability perspective, zirconium oxide particles are more preferred.

[0842] The inorganic particles are preferably inorganic particles manufactured by crushing the raw ore of inorganic particles, or by melting and refining the raw ore of inorganic particles, and using the resulting spherical particles with uniform particle size as inorganic particles.

[0843] There are no particular limitations on the method for crushing raw ore, and examples include ball mills, bead mills, colloid mills, conical mills, disc mills, edge mills, pulverizing mills, hammer mills, particle mills, VSI mills, Wiley mills, roller mills, and jet mills. Furthermore, it is preferable to perform washing after crushing, and acid treatment is preferred as the washing method. This reduces impurities such as iron adhering to the surface of inorganic particles.

[0844] The coating layer preferably includes an adhesive. The adhesive is a component that holds inorganic particles on the surface of the ion exchange membrane to form the coating layer. From the perspective of resistance to electrolyte or electrolysis products, the adhesive preferably includes a fluorinated polymer.

[0845] As an adhesive, fluorinated polymers having carboxylic acid groups or sulfonic acid groups are more preferred from the perspectives of resistance to electrolytes or electrolysis products and adhesion to the surface of ion exchange membranes. When a coating layer is provided on a layer containing a fluorinated polymer with sulfonic acid groups (sulfonic acid layer), a fluorinated polymer with sulfonic acid groups is even more preferred as the adhesive for this coating layer. Furthermore, when a coating layer is provided on a layer containing a fluorinated polymer with carboxylic acid groups (carboxylic acid layer), a fluorinated polymer with carboxylic acid groups is even more preferred as the adhesive for this coating layer.

[0846] In the coating layer, the content of inorganic particles is preferably 40-90% by mass, more preferably 50-90% by mass. Additionally, the content of the binder is preferably 10-60% by mass, more preferably 10-50% by mass.

[0847] The preferred distribution density of the coating layer in the ion exchange membrane is per 1 cm. 2 The concentration is 0.05–2 mg. Furthermore, when the ion exchange membrane has an uneven surface, the preferred coating density is per 1 cm³. 2 The dosage is 0.5–2 mg.

[0848] There are no particular limitations on the method for forming the coating layer, and known methods can be used. For example, the following method can be used: dispersing inorganic particles in a solution containing an adhesive, and applying the resulting coating liquid by spraying or the like.

[0849] (Reinforced core material)

[0850] The ion exchange membrane preferably has a reinforcing core material disposed inside the membrane body.

[0851] The reinforcing core material is a component that enhances the strength and dimensional stability of the ion exchange membrane. By placing the reinforcing core material inside the membrane body, the expansion and contraction of the ion exchange membrane can be controlled within a desired range. This ensures that the ion exchange membrane does not expand or contract beyond the necessary extent during electrolysis, thus maintaining excellent dimensional stability over a long period.

[0852] The composition of the reinforcing core material is not particularly limited; for example, it can be formed by spinning a filament called a reinforcing fiber. The reinforcing fiber, as referred to here, is a component constituting the reinforcing core material, meaning a filament capable of imparting the desired dimensional stability and mechanical strength to the ion exchange membrane and being able to exist stably within the ion exchange membrane. By using a reinforcing core material spun from this reinforcing fiber, the ion exchange membrane can be endowed with superior dimensional stability and mechanical strength.

[0853] The materials for the reinforcing core and the reinforcing filaments used in the reinforcing core are not particularly limited, but materials resistant to acids and alkalis are preferred. Since heat resistance and chemical resistance are required for a long time, fibers made of fluorinated polymers are preferred.

[0854] Examples of fluorinated polymers used as reinforcing core materials include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-ethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene copolymer, trifluorochloroethylene-ethylene copolymer, and vinylidene fluoride polymer (PVDF). Among these, fibers made of polytetrafluoroethylene are particularly preferred from the perspective of heat resistance and chemical resistance.

[0855] The diameter of the reinforcing filaments used to reinforce the core material is not particularly limited, but is preferably 20–300 denier, more preferably 50–250 denier. The weaving density (number of weft threads per unit length) is preferably 5–50 threads / inch. The method of using the reinforcing core material is not particularly limited; for example, woven fabric, nonwoven fabric, or braided fabric can be used, but woven fabric is preferred. Furthermore, regarding the thickness of the woven fabric, a thickness of 30–250 μm is preferred, more preferably 30–150 μm.

[0856] Fabric can be woven or braided using monofilament, multifilament or their yarns, cut film yarns, etc., and various weaving methods can be used, such as plain weave, leno weave, knit, rib weave, crepe stripe weave, etc.

[0857] There are no particular limitations on the weaving method and configuration of the reinforcing core material in the membrane body. The size or shape of the ion exchange membrane, the desired physical properties of the ion exchange membrane, and the usage environment can be taken into account to set a suitable configuration.

[0858] For example, the reinforcing core material can be arranged along a predetermined direction of the membrane body, but from the perspective of dimensional stability, it is preferable to arrange the reinforcing core material along a predetermined first direction and arrange other reinforcing core materials along a second direction that is substantially perpendicular to the first direction. Within the longitudinal interior of the membrane body, by arranging a plurality of reinforcing core materials in a substantially straight manner, superior dimensional stability and mechanical strength can be imparted in multiple directions. For example, it is preferable to weave longitudinally arranged reinforcing core materials (warp) and transversely arranged reinforcing core materials (weft) onto the surface of the membrane body. From the perspectives of dimensional stability, mechanical strength, and ease of manufacture, more preferred are: plain weave, in which warp and weft alternately float and sink; leno weave, in which two warp threads are twisted while being woven with the weft; square plain weave, in which two or more warp threads are aligned and weave the same number of weft threads; and so on.

[0859] It is particularly preferable to arrange the reinforcing core material along both the MD (Machine Direction, longitudinal direction) and TD (Transverse Direction, transverse direction) directions of the ion exchange membrane. That is, it is preferable to weave it flat in both the MD and TD directions. Here, the MD direction refers to the direction (flow direction) in which the membrane body and various core materials (e.g., reinforcing core material, reinforcing wire, sacrificial wire, etc., described later) are conveyed during the manufacturing process of the ion exchange membrane, and the TD direction refers to the direction approximately perpendicular to the MD direction. Furthermore, the filament woven along the MD direction is called an MD filament, and the filament woven along the TD direction is called a TD filament. Typically, ion exchange membranes used for electrolysis are mostly rectangular, with the length direction being the MD direction and the width direction being the TD direction. By weaving in reinforcing core material as MD filament and reinforcing core material as TD filament, superior dimensional stability and mechanical strength can be imparted in multiple directions.

[0860] There are no particular limitations on the spacing of the reinforced core material; the appropriate spacing can be determined by considering the desired physical properties of the ion exchange membrane and the operating environment.

[0861] The opening ratio of the reinforcing core material is not particularly limited, but is preferably 30% or more, more preferably 50% or more and 90% or less. Regarding the opening ratio, from the perspective of the electrochemical properties of the ion exchange membrane, it is preferably 30% or more, and from the perspective of the mechanical strength of the ion exchange membrane, it is preferably 90% or less.

[0862] The aperture ratio of the reinforcing core material refers to the proportion (B / A) of the total surface area (A) through which substances such as ions (electrolyte and cations contained therein, e.g., sodium ions) can pass. The total surface area (B) through which substances such as ions can pass refers to the total area of ​​the ion exchange membrane where cations, electrolytes, etc., are not blocked by the reinforcing core material or similar components contained in the ion exchange membrane.

[0863] Figure 24 This is a schematic diagram illustrating the aperture ratio of the reinforcing core material that constitutes an ion exchange membrane. Figure 24 A portion of the ion exchange membrane is magnified, showing only the configuration of the reinforcing core materials 21 and 22 within that region; other components are omitted from the illustration.

[0864] By subtracting the total area (C) of the reinforcing core material from the area (A) of the region (the region being the area surrounded by the longitudinally arranged reinforcing core material 21 and the transversely arranged reinforcing core material 22, and the area (A) including the area of ​​the reinforcing core material), the total area (B) of the region (A) through which ions and other substances can pass can be calculated. That is, the aperture ratio can be calculated by the following formula (I).

[0865] Opening ratio=(B) / (A)=((A)-(C)) / (A)…(I)

[0866] In terms of chemical resistance and heat resistance, the reinforced core material is particularly preferred to be a flat filament or a highly oriented monofilament containing PTFE. Specifically, more preferred methods include: cutting a high-strength porous sheet made of PTFE into strip-shaped flat filaments; or a reinforced core material made of highly oriented monofilaments of PTFE with a denier of 50 to 300 denier and a weaving density of 10 to 50 threads / inch, with a thickness ranging from 50 to 100 μm. The aperture ratio of the ion exchange membrane containing this reinforced core material is further preferably 60% or more.

[0867] Examples of reinforcing filament shapes include round filaments and ribbon filaments.

[0868] (Connecting hole)

[0869] The ion exchange membrane preferably has interconnecting pores inside the membrane body.

[0870] A connecting pore is a pore that serves as a flow channel for ions and electrolyte generated during electrolysis. Alternatively, a connecting pore can also refer to a tubular pore formed within the membrane matrix, created by the dissolution of the sacrificial core material (or sacrificial wire), described later. The shape and diameter of the connecting pore can be controlled by selecting the shape and diameter of the sacrificial core material (sacrificial wire).

[0871] By forming interconnecting pores in the ion exchange membrane, the mobility of the electrolyte can be ensured during electrolysis. The shape of the interconnecting pores is not particularly limited and can be the shape of the sacrificial core material used to form the interconnecting pores, according to the manufacturing method described later.

[0872] The connecting pores are preferably formed in a manner that alternates between the anode side (sulfonic acid layer side) and the cathode side (carboxylic acid layer side) of the reinforcing core material. With this structure, the portion of the reinforcing core material with connecting pores formed on the cathode side allows ions (e.g., sodium ions) transported through the electrolyte filling the connecting pores to also flow to the cathode side of the reinforcing core material. As a result, the flow of cations is not impeded, thus further reducing the resistance of the ion exchange membrane.

[0873] The connecting pores may be formed only in one specified direction of the membrane body constituting the ion exchange membrane, but from the perspective of achieving more stable electrolysis performance, it is preferable to form them in both the longitudinal and transverse directions of the membrane body.

[0874] [Manufacturing Method]

[0875] As a preferred manufacturing method for ion exchange membranes, a method having the following steps (1) to (6) can be cited.

[0876] (1) Process: The process of manufacturing fluorinated polymers that have ion exchange groups or ion exchange group precursors that can become ion exchange groups by hydrolysis.

[0877] (2) Process: As needed, at least a plurality of reinforcing core materials and sacrificial yarns that are soluble in acid or alkali and form interconnected pores are woven in to obtain a reinforcing material in which sacrificial yarns are arranged between adjacent reinforcing core materials.

[0878] (3) Process: The process of membraneizing the above-mentioned fluorinated polymer having ion exchange groups or ion exchange group precursors that can become ion exchange groups through hydrolysis.

[0879] (4) Process: The process of embedding the above-mentioned reinforcing material into the above-mentioned membrane as needed to obtain a membrane body with the above-mentioned reinforcing material disposed inside.

[0880] (5) Process: The process of hydrolyzing the membrane substrate obtained in (4) (hydrolysis process).

[0881] (6) Process: The process of applying a coating layer to the membrane body obtained in process (5) (coating process).

[0882] The following is a detailed description of each process.

[0883] (1) Process: The process of manufacturing fluorinated polymers

[0884] In step (1), the monomers of the raw materials described in groups 1 to 3 above are used to manufacture a fluorinated polymer. In order to control the ion exchange capacity of the fluorinated polymer, the mixing ratio of the monomers of the raw materials can be adjusted during the manufacturing of the fluorinated polymer that forms each layer.

[0885] (2) Process: Manufacturing process of reinforced materials

[0886] Reinforcing materials refer to fabrics or similar materials woven from reinforcing fibers. By embedding the reinforcing material within the membrane, a reinforcing core material is formed. When manufacturing an ion exchange membrane with interconnected pores, sacrificial fibers are also woven into the reinforcing material. The preferred percentage of sacrificial fibers in this process is 10–80% by mass of the total reinforcing material, more preferably 30–70% by mass. Weaving in sacrificial fibers also helps prevent misalignment of the reinforcing core material.

[0887] The sacrificial fibers are soluble in the membrane manufacturing process or electrolytic environment, and materials such as rayon, polyethylene terephthalate (PET), cellulose, and polyamide are used. Additionally, polyvinyl alcohol with a thickness of 20–50 denier and composed of monofilaments or multifilaments is preferred.

[0888] It should be noted that in process (2), by adjusting the configuration of the reinforcing core material and the sacrificial wire, the opening ratio and the configuration of the connecting holes can be controlled.

[0889] (3) Process: Membrane formation process

[0890] In step (3), the fluorinated polymer obtained in step (1) is film-formed using an extruder. The film can be a single-layer structure, or a two-layer structure consisting of a sulfonic acid layer and a carboxylic acid layer as described above, or a multi-layer structure with three or more layers.

[0891] As a method for performing membrane formation, the following methods can be cited, for example.

[0892] A method for separately membraneizing fluoropolymers with carboxylic acid groups and fluoropolymers with sulfonic acid groups.

[0893] A method for preparing a composite film by co-extrusion of a fluoropolymer with carboxylic acid groups and a fluoropolymer with sulfonic acid groups.

[0894] It should be noted that the membrane can consist of two or more sheets. Furthermore, co-extruding different types of membranes helps improve the interfacial adhesion strength, and is therefore preferred.

[0895] (4) Process: The process of obtaining the membrane substrate

[0896] In step (4), the reinforcing material obtained in step (2) is embedded inside the membrane obtained in step (3), thereby obtaining a membrane body containing the reinforcing material inside.

[0897] Preferred methods for forming the membrane body include: (i) co-extruding a fluorinated polymer having a carboxylic acid precursor (e.g., a carboxylic acid ester functional group) located on the cathode side (hereinafter referred to as the first layer) and a fluorinated polymer having a sulfonic acid precursor (e.g., a sulfonyl fluoride functional group) (hereinafter referred to as the second layer) by means of a co-extrusion process, using a heating source and a vacuum source as needed, and laminating the membrane onto a flat plate or cylinder with numerous fine pores on the surface, separated by a breathable, heat-resistant release paper, in the order of reinforcing material, second layer / first layer composite membrane, and so on. (ii) A method of removing air between layers by depressurization at the melting temperature of the polymer and simultaneously integrating them; (ii) A separate operation with the second / first layer composite film, wherein a fluorinated polymer (third layer) having a sulfonic acid precursor is pre-filmed separately, and a heat source and vacuum source are used as needed, and the third layer film, the reinforcing core material, and the composite film consisting of the second / first layer are laminated in the order of the third layer film, the reinforcing core material, and the composite film consisting of the second / first layer, with the air between layers removed by depressurization at the melting temperature of each polymer and simultaneously integrating them.

[0898] Here, co-extruding the first and second layers helps to improve the bonding strength of the interface.

[0899] Furthermore, compared to the pressure pressing method, the depressurized integration method features an increased thickness of the third layer on the reinforcing material. In addition, since the reinforcing material is fixed to the inner surface of the membrane body, it possesses the ability to adequately maintain the mechanical strength of the ion exchange membrane.

[0900] It should be noted that the lamination transformation pattern described here is an example. Alternatively, one can consider the desired layer composition or physical properties of the membrane body, and choose a suitable lamination pattern (e.g., the combination of layers) before co-extrusion.

[0901] It should be noted that, in order to further improve the electrical performance of the ion exchange membrane, a fourth layer composed of a fluorinated polymer having both carboxylic acid group precursors and sulfonic acid group precursors can be sandwiched between the first layer and the second layer, or, in place of the second layer, a fourth layer composed of a fluorinated polymer having both carboxylic acid group precursors and sulfonic acid group precursors can be used.

[0902] The fourth layer can be formed by mixing a fluorinated polymer having a carboxylic acid precursor and a fluorinated polymer having a sulfonic acid precursor, or by using a substance copolymerized from a monomer having a carboxylic acid precursor and a monomer having a sulfonic acid precursor.

[0903] When the fourth layer is composed of an ion exchange membrane, the first and fourth layers can be co-extruded to form a membrane, while the third and second layers are separately membraneized and laminated using the method described above; alternatively, the first, fourth, and second layers can be membraneized in one step through co-extrusion.

[0904] In this case, the direction of the extruded membrane flow is the MD direction. Thus, a membrane matrix comprising a fluorinated polymer with ion exchange groups can be formed on the reinforcing material.

[0905] Furthermore, the ion exchange membrane preferably has a protruding portion, or convex portion, made of a fluoropolymer with sulfonic acid groups on the surface side composed of a sulfonic acid layer. There is no particular limitation on the method for forming such a convex portion, and known methods for forming convex portions on the resin surface can be used. Specifically, for example, a method of embossing the surface of the membrane body can be employed. For example, when integrating the aforementioned composite membrane and reinforcing material, the aforementioned convex portion can be formed by using a pre-embossed release paper. When the convex portion is formed by embossing, the height and density of the convex portion can be controlled by controlling the embossing shape (the shape of the release paper) used for transfer.

[0906] (5) Hydrolysis process

[0907] In step (5), the following steps are performed: the membrane substrate obtained in step (4) is hydrolyzed to convert the ion exchanger precursor into an ion exchanger (hydrolysis step).

[0908] Additionally, in step (5), the sacrificial fibers contained in the membrane body can be dissolved and removed using acid or alkali, thereby forming dissolution pores in the membrane body. It should be noted that the sacrificial fibers may remain in the interconnecting pores and are not completely dissolved and removed. Furthermore, the sacrificial fibers remaining in the interconnecting pores can be dissolved and removed by the electrolyte when the ion exchange membrane is supplied with electrolyte.

[0909] Sacrificial wires are soluble in acids or bases during the manufacturing process and electrolysis environment of ion exchange membranes. The sacrificial wires dissolve and form interconnecting pores in the corresponding areas.

[0910] (5) The process can be carried out by immersing the membrane body obtained in step (4) in a hydrolysis solution containing an acid or an alkali. For example, a mixed solution containing KOH and DMSO (dimethyl sulfoxide) can be used as the hydrolysis solution.

[0911] The mixed solution preferably contains 2.5–4.0 N KOH and 25–35% by mass DMSO.

[0912] The hydrolysis temperature is preferably 70–100°C. Higher temperatures result in greater apparent thickness. 75–100°C is more preferred.

[0913] The hydrolysis time is preferably 10 to 120 minutes. The longer the time, the greater the increase in apparent thickness. More preferably, it is 20 to 120 minutes.

[0914] Here, the process of dissolving the sacrificial wire to form a connecting hole is explained in more detail. Figure 25 (a) and (b) are schematic diagrams illustrating the method of forming the connecting pores of an ion exchange membrane.

[0915] exist Figure 25 In (a) and (b), only the connecting hole 504 formed by the reinforcing wire 52, the sacrificial wire 504a and the sacrificial wire 504a is shown, and other components such as the membrane body are omitted from the illustration.

[0916] First, a reinforcing material is made by weaving in reinforcing wires 52, which constitute the reinforcing core material in the ion exchange membrane, and sacrificial wires 504a, which are used to form connecting pores 504 in the ion exchange membrane. Then, the connecting pores 504 are formed by dissolving the sacrificial wires 504a in step (5).

[0917] According to the above method, the weaving method of reinforcing wire 52 and sacrificial wire 504a can be adjusted according to the configuration of the reinforcing core material and the connecting holes in the membrane body of the ion exchange membrane, which is very simple.

[0918] exist Figure 25 (a) illustrates a plain-woven reinforcing material formed by weaving reinforcing yarns 52 and sacrificial yarns 504a into the paper surface in both longitudinal and transverse directions, but the configuration of reinforcing yarns 52 and sacrificial yarns 504a in the reinforcing material can be changed as needed.

[0919] (6) Coating process

[0920] In step (6), a coating liquid containing inorganic particles obtained by crushing or melting raw ore and a binder is prepared. The coating liquid is applied to the surface of the ion exchange membrane obtained in step (5) and dried, thereby forming a coating layer.

[0921] As an adhesive, an adhesive obtained as follows is preferred: a fluorinated polymer having an ion-exchange group precursor is hydrolyzed with an aqueous solution containing dimethyl sulfoxide (DMSO) and potassium hydroxide (KOH), and then impregnated in hydrochloric acid to replace the counter ion of the ion-exchange group with H+. + (For example, fluorinated polymers having carboxyl or sulfonyl groups). Therefore, they are readily soluble in water or ethanol, as described later, and are thus preferred.

[0922] The adhesive is dissolved in a solution containing water and ethanol. It should be noted that the preferred volume ratio of water to ethanol is 10:1 to 1:10, more preferably 5:1 to 1:5, and even more preferably 2:1 to 1:2. The inorganic particles are dispersed in the resulting solution using a ball mill to obtain a coating solution. The average particle size can be adjusted by changing the dispersion time and rotation speed. It should be noted that the preferred mixing ratio of the inorganic particles and the adhesive is as described above.

[0923] There are no particular limitations on the concentration of inorganic particles and binders in the coating solution, but a dilute coating solution is preferred. This allows for uniform coating onto the surface of the ion exchange membrane.

[0924] In addition, when dispersing inorganic particles, a surfactant can be added to the dispersion. Nonionic surfactants are preferred, such as HS-210, NS-210, P-210, and E-212 manufactured by Nippon Oil Co., Ltd.

[0925] The obtained coating solution is applied to the surface of the ion exchange membrane by spray coating or roller coating, thereby obtaining the ion exchange membrane.

[0926] [Microporous membrane]

[0927] As described above, there are no particular limitations on the microporous membrane used in this embodiment, as long as it can form a laminate with the electrolysis electrode, and various microporous membranes can be used.

[0928] The porosity of the microporous membrane in this embodiment is not particularly limited, but can be, for example, 20 to 90, preferably 30 to 85. The above porosity can be calculated, for example, using the following formula.

[0929] Porosity = (1 - (Weight of the membrane in dry state) / (Weight calculated based on the volume of the membrane from its thickness, width, and length, and the density of the membrane feedstock)) × 100

[0930] The average pore size of the microporous membrane in this embodiment is not particularly limited, and can be, for example, 0.01 μm to 10 μm, preferably 0.05 μm to 5 μm. Regarding the above average pore size, for example, the membrane is cut perpendicular to the thickness direction, and the cross-section is observed using FE-SEM. The average pore size is calculated by measuring approximately 100 points of the observed pore diameter.

[0931] The thickness of the microporous membrane in this embodiment is not particularly limited, and can be, for example, 10 μm to 1000 μm, preferably 50 μm to 600 μm. The thickness can be measured, for example, using a micrometer (manufactured by Mitutoyo Co., Ltd.).

[0932] Specific examples of the aforementioned microporous membranes include the Zirfon Perl UTP 500 manufactured by Agfa Corporation (also referred to as the Zirfon membrane in this embodiment), International Publication No. 2013-183584, and International Publication No. 2016-203701.

[0933] The reason why the laminated body with the diaphragm in this embodiment exhibits excellent electrolytic performance is speculated as follows. In the prior art, when the diaphragm and electrode are firmly bonded by methods such as thermoforming, the electrode is physically bonded, becoming embedded in the diaphragm. This bonded portion hinders the intramembrane movement of sodium ions, resulting in a significant voltage increase. On the other hand, by contacting the electrolytic electrode with the diaphragm or power supply with a moderate adhesive force as in this embodiment, the problem of hindering the intramembrane movement of sodium ions, which is a problem in the prior art, is eliminated. Therefore, when the diaphragm or power supply is in contact with the electrolytic electrode with a moderate adhesive force, excellent electrolytic performance can be exhibited even though the diaphragm or power supply and the electrolytic electrode become a single unit.

[0934] [Wound Body]

[0935] The wound body of this embodiment includes the laminated body of this embodiment. That is, the wound body of this embodiment is formed by winding the laminated body of this embodiment. As with the wound body of this embodiment, the size is reduced by winding the laminated body of this embodiment, thereby further improving processability.

[0936] Electrolytic cell

[0937] The electrolytic cell of this embodiment includes the laminate of this embodiment. Hereinafter, taking the case of using an ion exchange membrane as a diaphragm for salt electrolysis as an example, one embodiment of the electrolytic cell will be described in detail.

[0938] [Electrolysis Unit]

[0939] Figure 26 This is a cross-sectional view of electrolysis unit 1.

[0940] Electrolysis unit 1 includes an anode chamber 10, a cathode chamber 20, a partition wall 30 disposed between the anode chamber 10 and the cathode chamber 20, an anode 11 disposed in the anode chamber 10, and a cathode 21 disposed in the cathode chamber 20. If necessary, a reverse current absorber 18 disposed in the cathode chamber may also be included. The reverse current absorber 18 has a substrate 18a and a reverse current absorbing layer 18b formed on the substrate 18a. The anode 11 and cathode 21 belonging to one electrolysis unit 1 are electrically connected to each other. In other words, electrolysis unit 1 includes the following cathode structure: Cathode structure 40 includes a cathode chamber 20, a cathode 21 disposed in the cathode chamber 20, and a reverse current absorber 18 disposed within the cathode chamber 20. The reverse current absorber 18 is as follows: Figure 30The cathode 21 has a substrate 18a and a reverse current absorption layer 18b formed on the substrate 18a, and the reverse current absorption layer 18b is electrically connected to the cathode 21. The cathode chamber 20 further includes a current collector 23, a support 24 supporting the current collector, and a metal elastomer 22. The metal elastomer 22 is disposed between the current collector 23 and the cathode 21. The support 24 is disposed between the current collector 23 and the isolation wall 30. The current collector 23 is electrically connected to the cathode 21 via the metal elastomer 22. The isolation wall 30 is electrically connected to the current collector 23 via the support 24. Therefore, the isolation wall 30, the support 24, the current collector 23, the metal elastomer 22, and the cathode 21 are electrically connected. The cathode 21 is electrically connected to the reverse current absorption layer 18b. The cathode 21 and the reverse current absorption layer can be directly connected or indirectly connected via the current collector, the support, the metal elastomer, or the isolation wall. The entire surface of the cathode 21 is preferably covered with a catalyst layer for the reduction reaction. Alternatively, the electrical connection can be achieved by directly mounting the isolation wall 30 and the support 24, directly mounting the support 24 and the current collector 23, or directly mounting the current collector 23 and the metallic elastomer 22, with the cathode 21 laminated on the metallic elastomer 22. Welding is an example of a method for directly mounting these components together. Alternatively, the reverse current absorber 18, the cathode 21, and the current collector 23 can be collectively referred to as the cathode structure 40.

[0941] Figure 27 This is a cross-sectional view of two adjacent electrolysis units 1 within electrolysis cell 4. Figure 28 Electrolytic cell 4 is shown. Figure 29 The process of assembling electrolytic cell 4 is shown. For example... Figure 27 As shown, the electrolysis unit 1, cation exchange membrane 2, and electrolysis unit 1 are arranged in series. An ion exchange membrane 2 is disposed between the anode chamber of one electrolysis unit 1 and the cathode chamber of the other electrolysis unit 1 within two adjacent electrolysis units in the electrolytic cell. That is, the anode chamber 10 of electrolysis unit 1 and the cathode chamber 20 of the adjacent electrolysis unit 1 are separated by the cation exchange membrane 2. Figure 28 As shown, the electrolytic cell 4 is composed of a plurality of electrolytic units 1 connected in series with ion exchange membranes 2 in between. That is, the electrolytic cell 4 is a bipolar electrolytic cell having a plurality of electrolytic units 1 arranged in series and ion exchange membranes 2 disposed between adjacent electrolytic units 1. Figure 29 As shown, the electrolytic cell 4 is assembled by arranging a plurality of electrolysis units 1 in series with ion exchange membranes 2 in between and connecting them with a pressure device 5.

[0942] The electrolytic cell 4 has an anode terminal 7 and a cathode terminal 6 connected to a power source. The anode 11 of the electrolytic unit 1 located at the far end of the plurality of electrolytic units 1 connected in series within the electrolytic cell 4 is electrically connected to the anode terminal 7. The cathode 21 of the electrolytic unit located at the end opposite to the anode terminal 7 of the plurality of electrolytic units 2 connected in series within the electrolytic cell 4 is electrically connected to the cathode terminal 6. During electrolysis, the current flows from the anode terminal 7 side through the anode and cathode of each electrolytic unit 1 to the cathode terminal 6. It should be noted that electrolytic units with only an anode chamber (anode terminal unit) and electrolytic units with only a cathode chamber (cathode terminal unit) can also be configured at both ends of the connected electrolytic unit 1. In this case, the anode terminal 7 is connected to the anode terminal unit located at one end, and the cathode terminal 6 is connected to the cathode terminal unit located at the other end.

[0943] In the case of brine electrolysis, brine is supplied to each anode chamber 10, and pure water or a low-concentration sodium hydroxide aqueous solution is supplied to the cathode chamber 20. Each liquid is supplied to each electrolysis unit 1 from an electrolyte supply pipe (omitted in the figure) via an electrolyte supply hose (omitted in the figure). Furthermore, the electrolyte and electrolysis products are recovered by an electrolyte recovery pipe (omitted in the figure). During electrolysis, sodium ions in the brine move from the anode chamber 10 of one electrolysis unit 1 to the cathode chamber 20 of the adjacent electrolysis unit 1 via the ion exchange membrane 2. Thus, the current in the electrolysis flows along the series connection direction of the electrolysis units 1. That is, the current flows from the anode chamber 10 to the cathode chamber 20 via the cation exchange membrane 2. Accompanying the brine electrolysis, chlorine gas is generated on the anode 11 side, and sodium hydroxide (solute) and hydrogen gas are generated on the cathode 21 side.

[0944] (Anode chamber)

[0945] The anode chamber 10 has an anode 11 or an anode power supply 11. When the electrolysis electrode of this embodiment is inserted into the anode side, 11 functions as an anode power supply. When the electrolysis electrode of this embodiment is not inserted into the anode side, 11 functions as an anode. In addition, the anode chamber 10 preferably has: an anode-side electrolyte supply section for supplying electrolyte to the anode chamber 10; a baffle plate disposed above the anode-side electrolyte supply section and disposed substantially parallel to or inclined to the isolation wall 30; and an anode-side gas-liquid separation section disposed above the baffle plate for separating gas from the electrolyte mixed with gas.

[0946] (anode)

[0947] Without inserting the electrolysis electrode of this embodiment into the anode side, an anode 11 is provided within the frame of the anode chamber 10. The anode 11 can be a metal electrode such as a so-called DSA (registered trademark). DSA refers to an electrode made of a titanium substrate whose surface is coated with an oxide composed of ruthenium, iridium, and titanium.

[0948] As for the shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or so-called woven mesh made by braiding metal wires.

[0949] (Anode power supply)

[0950] When the electrolysis electrode of this embodiment is inserted into the anode side, an anode power supply 11 is provided within the frame of the anode chamber 10. The anode power supply 11 can be a metal electrode such as a so-called DSA (registered trademark), or it can be titanium without catalyst coating. Alternatively, a DSA with a reduced catalyst coating thickness can also be used. Furthermore, a previously used anode can also be used.

[0951] As for the shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or so-called woven mesh made by braiding metal wires.

[0952] (Anode-side electrolyte supply section)

[0953] An anode-side electrolyte supply unit supplies electrolyte to the anode chamber 10 and is connected to an electrolyte supply pipe. The anode-side electrolyte supply unit is preferably located below the anode chamber 10. For example, a pipe (dispersion pipe) with an opening formed on its surface can be used as the anode-side electrolyte supply unit. More preferably, this pipe is arranged parallel to the bottom 19 of the electrolysis unit along the surface of the anode 11. This pipe is connected to an electrolyte supply pipe (liquid supply nozzle) that supplies electrolyte to the electrolysis unit 1. The electrolyte supplied by the liquid supply nozzle is conveyed into the electrolysis unit 1 through the pipe and supplied into the interior of the anode chamber 10 from the opening provided on the surface of the pipe. Arranging the pipe parallel to the bottom 19 of the electrolysis unit along the surface of the anode 11 allows for uniform supply of electrolyte into the interior of the anode chamber 10, which is therefore preferable.

[0954] (Anode-side gas-liquid separation section)

[0955] The anode-side gas-liquid separator is preferably positioned above the baffle plate. In electrolysis, the anode-side gas-liquid separator functions to separate generated gases such as chlorine from the electrolyte. It should be noted that, unless otherwise specified, "above" refers to... Figure 26 In electrolysis unit 1, the upward direction and the downward direction refer to... Figure 26 The downward direction in electrolysis unit 1.

[0956] During electrolysis, if the generated gas and electrolyte produced in electrolysis unit 1 become a mixed phase (gas-liquid mixture) and are discharged outside the system, vibration will occur due to pressure fluctuations inside electrolysis unit 1, sometimes causing physical damage to the ion exchange membrane. To suppress this phenomenon, it is preferable that the electrolysis unit 1 of this embodiment is provided with an anode-side gas-liquid separation section for separating the gas and liquid. A defoaming plate for eliminating bubbles is preferably provided in the anode-side gas-liquid separation section. When the gas-liquid mixture flows through the defoaming plate, the bubbles break, thereby separating into electrolyte and gas. As a result, vibration during electrolysis can be prevented.

[0957] (Baffle plate)

[0958] The baffle is preferably positioned above the electrolyte supply section on the anode side and is arranged substantially parallel or inclined to the isolation wall 30. The baffle acts as a partition to control the flow of electrolyte in the anode chamber 10. By providing the baffle, the electrolyte (such as brine) can circulate internally within the anode chamber 10, resulting in a uniform concentration. To generate this internal circulation, the baffle is preferably arranged to separate the space near the anode 11 from the space near the isolation wall 30. In this respect, the baffle is preferably positioned facing each surface of the anode 11 and the isolation wall 30. In the space near the anode separated by the baffle, as electrolysis proceeds, the electrolyte concentration (brine concentration) decreases, and gases such as chlorine are generated. This creates a gas-liquid density difference between the space near the anode 11 and the space near the isolation wall 30. This density difference promotes internal circulation of the electrolyte in the anode chamber 10, resulting in a more uniform electrolyte concentration distribution within the anode chamber 10.

[0959] It should be noted that, although not shown in Figure 26 However, a current collector can be separately installed inside the anode chamber 10. This current collector can also be made of the same material or structure as the current collector in the cathode chamber, which will be described later. Alternatively, the anode 11 itself can function as a current collector in the anode chamber 10.

[0960] (isolation wall)

[0961] An isolation wall 30 is disposed between the anode chamber 10 and the cathode chamber 20. The isolation wall 30 is sometimes referred to as a separation plate, which divides the anode chamber 10 and the cathode chamber 20. As the isolation wall 30, materials known as separation plates for electrolysis can be used, for example, an isolation wall with a nickel plate welded to the cathode side or a titanium plate welded to the anode side can be cited.

[0962] (Cathode chamber)

[0963] Regarding the cathode chamber 20, when the electrolysis electrode of this embodiment is inserted into the cathode side, 21 functions as a cathode power supply; when the electrolysis electrode of this embodiment is not inserted into the cathode side, 21 functions as a cathode. In the case of a reverse current absorber, the cathode or cathode power supply 21 is electrically connected to the reverse current absorber. Furthermore, the cathode chamber 20, like the anode chamber 10, preferably has a cathode-side electrolyte supply section and a cathode-side gas-liquid separation section. It should be noted that descriptions of the parts constituting the cathode chamber 20 that are the same as those constituting the anode chamber 10 are omitted.

[0964] (cathode)

[0965] Without inserting the electrolysis electrode of this embodiment into the cathode side, a cathode 21 is provided within the frame of the cathode chamber 20. The cathode 21 preferably has a nickel substrate and a catalyst layer coated with the nickel substrate. Examples of components for the catalyst layer on the nickel substrate include metals such as Ru, C, Si, P, S, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Rh, Pd, Ag, Cd, In, Sn, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, as well as oxides or hydroxides of these metals. Examples of methods for forming the catalyst layer include plating, alloy plating, dispersion / composite plating, CVD, PVD, thermal decomposition, and spraying. These methods can also be combined. The catalyst layer can have multiple layers and multiple elements as needed. Additionally, the cathode 21 can be subjected to a reduction treatment as required. It should be noted that nickel, nickel alloys, or nickel-plated iron or stainless steel substrates can also be used as the substrate for the cathode 21.

[0966] As for the shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or so-called woven mesh made by braiding metal wires.

[0967] (Cathode power supply)

[0968] When the electrolysis electrode of this embodiment is inserted into the cathode side, a cathode power supply 21 is provided within the frame of the cathode chamber 20. The cathode power supply 21 may be coated with a catalyst component. This catalyst component may be a substance that was originally used as a cathode and remains there. Examples of catalyst layer components include metals such as Ru, C, Si, P, S, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Rh, Pd, Ag, Cd, In, Sn, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, as well as oxides or hydroxides of these metals. Methods for forming the catalyst layer include plating, alloy plating, dispersion / composite plating, CVD, PVD, thermal decomposition, and spraying. These methods may also be combined. The catalyst layer can have multiple layers and multiple elements as needed. Alternatively, uncoated nickel, nickel alloys, or nickel-plated iron or stainless steel can also be used. It should be noted that the substrate for the cathode power supply body 21 can also be made of nickel, nickel alloys, or nickel-plated iron or stainless steel.

[0969] As for the shape, any one of the following can be used: perforated metal, non-woven fabric, foamed metal, metal mesh, porous metal foil formed by electroforming, or so-called woven mesh made by braiding metal wires.

[0970] (Reverse current absorption layer)

[0971] A material with a lower redox potential than the element used in the catalyst layer of the cathode can be selected as the material for the reverse current absorption layer. For example, nickel and iron can be cited.

[0972] (Current collector)

[0973] The cathode chamber 20 preferably includes a current collector 23. This improves the current collection effect. In this embodiment, the current collector 23 is preferably a perforated plate and is arranged substantially parallel to the surface of the cathode 21.

[0974] The current collector 23 is preferably made of conductive metals such as nickel, iron, copper, silver, and titanium. The current collector 23 can also be a mixture, alloy, or composite oxide of these metals. It should be noted that the shape of the current collector 23 can be any shape, as long as it functions as a current collector; it can be plate-like or mesh-like.

[0975] (Metallic elastomer)

[0976] By providing a metallic elastomer 22 between the current collector 23 and the cathode 21, each cathode 21 of the series-connected plurality of electrolysis units 1 is pressed against the ion exchange membrane 2, shortening the distance between each anode 11 and each cathode 21, thereby reducing the voltage applied to the entire series-connected plurality of electrolysis units 1. By reducing the voltage, power consumption can be reduced. In addition, by providing the metallic elastomer 22, when a laminate containing the electrolysis electrode of this embodiment is disposed in the electrolysis unit, the pressing pressure generated by the metallic elastomer 22 can stably maintain the electrolysis electrode in a fixed position.

[0977] As the metallic elastomer 22, spring components such as helical springs and coils, and cushioning pads can be used. A suitable metallic elastomer can be selected to account for factors such as the stress on the ion exchange membrane. The metallic elastomer 22 can be disposed on the surface of the current collector 23 on the cathode chamber 20 side, or on the surface of the isolation wall on the anode chamber 10 side. Typically, the cathode chamber 20 is divided into two chambers, with the anode chamber 10 being smaller than the cathode chamber 10. Therefore, considering the strength of the frame, it is preferable to place the metallic elastomer 22 between the current collector 23 and the cathode 21 in the cathode chamber 20. Furthermore, the metallic elastomer 23 is preferably made of a conductive metal such as nickel, iron, copper, silver, or titanium.

[0978] (Support structure)

[0979] The cathode chamber 20 preferably includes a support 24 that electrically connects the current collector 23 and the isolation wall 30. This allows for efficient current flow.

[0980] The support 24 is preferably made of a conductive metal such as nickel, iron, copper, silver, or titanium. Furthermore, the shape of the support 24 can be any shape, as long as it can support the current collector 23; it can be rod-shaped, plate-shaped, or mesh-shaped. For example, the support 24 is plate-shaped. A plurality of supports 24 are disposed between the isolation wall 30 and the current collector 23. The plurality of supports 24 are arranged such that their respective faces are parallel to each other. The supports 24 are arranged substantially perpendicular to the isolation wall 30 and the current collector 23.

[0981] (Anode side gasket, cathode side gasket)

[0982] The anode-side gasket is preferably disposed on the surface of the frame constituting the anode chamber 10. The cathode-side gasket is preferably disposed on the surface of the frame constituting the cathode chamber 20. The electrolysis units are connected to each other in such a way that the ion exchange membrane 2 is sandwiched between the anode-side gasket of one electrolysis unit and the cathode-side gasket of the adjacent electrolysis unit (see reference). Figure 26 , 27 These gaskets enable airtightness at the connection points when multiple electrolysis units 1 are connected in series via ion exchange membrane 2.

[0983] A gasket is a component used to seal the connection between the ion exchange membrane and the electrolysis unit. Specific examples of gaskets include frame-shaped rubber sheets with a central opening. Gaskets must be resistant to corrosive electrolytes or generated gases and be usable for extended periods. Therefore, considering chemical resistance and hardness, vulcanized or peroxide-crosslinked products of ethylene propylene diene monomer (EPDM) rubber or diethylene propylene diene monomer (EPM) rubber are commonly used as gaskets. Alternatively, gaskets whose liquid-contact areas (liquid contact portions) are coated with fluorinated resins such as polytetrafluoroethylene (PTFE) or tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) can be used as needed. These gaskets are not particularly limited in shape as long as they have openings that do not obstruct electrolyte flow. For example, frame-shaped gaskets can be adhered with adhesives or similar materials around the periphery of each opening in the anode chamber frame constituting the anode chamber 10 or the cathode chamber frame constituting the cathode chamber 20. Additionally, for example, in the case where two electrolysis units 1 are connected through an ion exchange membrane 2 (see reference). Figure 27 Each electrolysis unit 1, with its gasket attached, is then secured through the ion exchange membrane 2. This prevents the electrolyte, alkali metal hydroxides generated during electrolysis, chlorine gas, hydrogen gas, etc., from leaking to the outside of the electrolysis unit 1.

[0984] (Ion exchange membrane)

[0985] As ion exchange membrane 2, it is as described in the section on ion exchange membranes above.

[0986] (Water electrolysis)

[0987] The electrolytic cell of this embodiment is an electrolytic cell for water electrolysis, and it has the following configuration: the ion exchange membrane in the electrolytic cell for salt electrolysis described above is replaced with a microporous membrane. Furthermore, it differs from the electrolytic cell for salt electrolysis in that the supplied raw material is water. Regarding other configurations, the electrolytic cell for water electrolysis can also adopt the same configuration as the electrolytic cell for salt electrolysis. In the case of salt electrolysis, chlorine gas is generated in the anode chamber, so titanium is used as the material for the anode chamber. However, in the case of water electrolysis, only oxygen is generated in the anode chamber, so the same material as the cathode chamber can be used. For example, nickel can be used. In addition, the anode coating is suitable as a catalyst coating for oxygen generation. Examples of catalyst coatings include platinum group metals and transition metals, oxides, hydroxides, etc. For example, elements such as platinum, iridium, palladium, ruthenium, nickel, cobalt, and iron can be used.

[0988] (Applications of laminates)

[0989] As described above, the laminate of this embodiment can improve the efficiency of electrode replacement in an electrolytic cell, and thus exhibit excellent electrolytic performance even after replacement. In other words, the laminate of this embodiment can be suitably used as a laminate for component exchange in an electrolytic cell. It should be noted that the laminate used for this purpose is specifically referred to as a "membrane electrode assembly".

[0990] (Packaging)

[0991] The laminated body of this embodiment is preferably handled and transported while enclosed in packaging material. That is, the packaging body of this embodiment comprises the laminated body of this embodiment and packaging material for packaging the laminated body. As configured above, the packaging body of this embodiment can prevent dirt adhesion and damage that may occur during handling and other operations of the laminated body of this embodiment. When used for component exchange in an electrolytic cell, handling and other operations in the form of the packaging body of this embodiment are particularly preferred. There are no particular limitations on the packaging material used in this embodiment; various known packaging materials can be used. Furthermore, the packaging body of this embodiment can be manufactured by, but is not limited to, the following methods: for example, packaging the laminated body of this embodiment with clean packaging material and then sealing it; etc.

[0992] <Third Implementation Method>

[0993] Here, refer to Figures 43-62 The third embodiment of the present invention will be described in detail.

[0994] [laminated body]

[0995] The laminate of the third embodiment (hereinafter referred to as "this embodiment" in the section on "the third embodiment") has a diaphragm; and an electrolytic electrode fixed to at least one region (hereinafter also referred to as "fixed region") on the surface of the diaphragm, wherein the proportion of the fixed region on the surface of the diaphragm is greater than 0% and less than 93%. Due to this configuration, the laminate of this embodiment can improve the working efficiency when the electrode is replaced in the electrolytic cell, and thus exhibit excellent electrolytic performance even after replacement.

[0996] That is, according to the laminate of this embodiment, when updating the electrodes, the electrodes can be updated using the same simple operation as the diaphragm update without complicated operations such as peeling off the original electrodes fixed to the electrolysis unit, thus greatly improving work efficiency.

[0997] Furthermore, the laminate according to this embodiment can maintain or improve the electrolytic performance of the original electrolysis unit at the same level as when it was new. Therefore, the electrodes fixed to the original electrolysis unit and functioning as anodes and cathodes only need to function as power supply units, which can significantly reduce or completely eliminate catalyst coating. As for the power supply unit mentioned here, it refers to degraded electrodes (i.e., original electrodes), electrodes that have not been coated with catalyst, etc.

[0998] Electrolysis electrodes

[0999] In this embodiment, the electrode used for electrolysis is not particularly limited as long as it is an electrode used for electrolysis. The area of ​​the surface of the electrode facing the diaphragm (corresponding to the area S2 of the current-carrying surface described later) is preferably 0.01m². 2 The above refers to the surface of the electrolytic electrode on the side where the diaphragm is located. In other words, the surface of the electrolytic electrode facing the diaphragm can also refer to the surface in contact with the diaphragm. The area of ​​the aforementioned surface of the electrolytic electrode facing the diaphragm is 0.01 m². 2 Under the above circumstances, there is a tendency to ensure sufficient productivity, particularly in industrial electrolysis. Therefore, from the perspective of ensuring sufficient productivity and the practicality of the laminate used in the renewal of electrolysis units, the area of ​​the surface of the electrode facing the diaphragm is more preferably 0.1 m². 2 The above, and more preferably 1m 2 The area can be measured, for example, using the method described in the embodiments.

[1000] Regarding the electrolysis electrode in this embodiment, considering its good processability and good adhesion to membranes such as ion exchange membranes or microporous membranes, as well as to the power supply (degraded electrodes and electrodes without catalyst coating), the force applied per unit mass per unit area is preferably 1.6 N / (mg·cm²). 2 ) or less, more preferably less than 1.6 N / (mg·cm 2 Further preferred is less than 1.5 N / (mg·cm). 2 ), and more preferably 1.2 N / mg·cm 2 The following, and more preferably, is 1.20 N / mg·cm 2 The following is a further preferred value: 1.1 N / mg·cm³. 2 The following, and more preferably, is 1.10 N / mg·cm⁻¹ 2 The following, particularly preferred, value is 1.0 N / mg·cm⁻¹ 2 The following, and especially preferred, value is 1.00 N / mg·cm⁻¹. 2 the following.

[1001] From the perspective of further improving electrolysis performance, a value exceeding 0.005 N / (mg·cm⁻¹) is preferred. 2 ), more preferably 0.08 N / (mg·cm 2 ) or higher, and more preferably 0.1 N / mg·cm 2 The above, and more preferably, is 0.14 N / (mg·cm³). 2 The above is preferred because it makes processing larger sizes (e.g., 1.5m × 2.5m) easier. 2 )above.

[1002] The applied force described above can be adjusted to the range described below, for example, by appropriately adjusting the porosity, electrode thickness, arithmetic mean surface roughness, etc. More specifically, for example, increasing the porosity tends to decrease the applied force, while decreasing the porosity tends to increase the applied force.

[1003] Furthermore, considering good processability, good adhesion to membranes such as ion exchange membranes or microporous membranes, deteriorated electrodes, and uncoated power sources, as well as economic efficiency, the preferred mass per unit area is 48 mg / cm². 2 The following, or more preferably, is 30 mg / cm³ 2 The following, and more preferably, is 20 mg / cm³. 2 Furthermore, considering a comprehensive approach that combines processability, adhesion, and economy, the target concentration is 15 mg / cm³. 2 The following is a lower limit value, which is not specifically defined, for example, 1 mg / cm³. 2 about.

[1004] The mass per unit area mentioned above can be adjusted, for example, by appropriately adjusting the aperture ratio, electrode thickness, etc. (described later). More specifically, for the same thickness, increasing the aperture ratio tends to decrease the mass per unit area, while decreasing the aperture ratio tends to increase the mass per unit area.

[1005] The applied force can be measured using either method (i) or (ii) below. The value obtained by method (i) (also referred to as "the applied force (1)") and the value obtained by method (ii) (also referred to as "the applied force (2)") may be the same or different, but preferably both values ​​are less than 1.5 N / mg·cm. 2 .

[1006] [Method(i)]

[1007] A nickel plate (1.2 mm thick, 200 mm square) obtained by sandblasting alumina particle number 320, an ion exchange membrane (170 mm square) with inorganic particles and binder coated on both sides of a membrane containing ion exchange groups of perfluorocarbon polymer, and an electrode sample (130 mm square) were sequentially laminated. The laminate was thoroughly impregnated with pure water, and excess water adhering to the surface was removed to obtain the sample for measurement. It should be noted that the arithmetic mean surface roughness (Ra) of the sandblasted nickel plate is 0.5–0.8 μm. The specific calculation method for the arithmetic mean surface roughness (Ra) is as described in the examples.

[1008] Under conditions of 23±2℃ and 30±5% relative humidity, a tensile compression testing machine was used to raise only the electrode sample in the test sample at a vertical speed of 10 mm / min, and the load when the electrode sample rose 10 mm vertically was measured. This measurement was performed three times, and the average value was calculated.

[1009] Divide this average value by the area of ​​the overlap between the electrode sample and the ion exchange membrane, and the mass of the electrode sample in the overlap portion, to calculate the force applied per unit mass per unit area (1) (N / mg·cm). 2 ).

[1010] Regarding the force (1) applied per unit mass per unit area obtai...

Claims

1. A method for manufacturing an electrolytic cell, which is a method for manufacturing a new electrolytic cell by arranging an electrolytic electrode or a laminate of the electrolytic electrode and a new diaphragm on the surface of an anode or a cathode of an existing electrolytic cell, wherein the existing electrolytic cell comprises an anode, a cathode facing the anode, and a diaphragm arranged between the anode and the cathode, wherein: The method for producing an electrolytic cell uses the electrode for electrolysis or the wound body of the laminate.

2. The method for manufacturing an electrolytic cell according to claim 1, wherein: The method comprises the step (A) of keeping the electrode for electrolysis or the laminated body in a wound state to obtain the wound body.

3. The method for manufacturing an electrolytic cell according to claim 1 or 2, wherein: The method comprises the step (B) of releasing the wound state of the wound body.

4. The method for manufacturing an electrolytic cell according to claim 3, wherein: The method further comprises, after the step (B), the step (C) of disposing the electrolysis electrode or the laminate on at least one surface of the anode and the cathode.

5. A method for updating an electrode, which is a method for updating an existing electrode by disposing an electrolysis electrode on the surface of the existing electrode, wherein: The renewal method uses a wound body of the electrolytic electrode.

6. The electrode renewal method according to claim 5, wherein: The method comprises the step (A') of holding the electrode for electrolysis in a wound state to obtain the wound body.

7. The electrode renewal method according to claim 5 or 6, wherein: The method comprises the step (B') of releasing the wound state of the electrolytic electrode.

8. The electrode renewal method according to claim 7, wherein: The method further comprises, after the step (B'), a step (C') of disposing the electrolysis electrode on the surface of the existing electrode.

Citation Information

Patent Citations

  • Manufacture of caustic alkali

    JP1980148775A

  • Cation exchange membrane for electrolyzing aqueous solution of alkali chloride

    JP1983048686A

  • KANA / kanji converting device

    JP1992333965A

  • Compliance device

    JP2017056524A

  • Robot device robot control method, program, recording medium, and method of manufacturing assembling component

    JP2017056525A

Cited By

  • Method for manufacturing electrolytic cell

    CN120041850A

  • Electrolytic cell, method for manufacturing same, and method for renewing laminate

    CN120041851A